Anthropogenic nutrient discharge and microbial community shifts associated with typhoon-driven runoff in an artificial coastal lake - Seung-Hee Kim; Keonhee Kim; Min-Seob Kim; Dong-Hun Lee; Eun-Ji Won; Kyung-Hoon Shin (Marine Pollution Bulletin, 2026)

Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

Assessment of two-component backfill grouting quality for TBM tail voids via scaled physical modeling: Effects of injection flow rate, hardener dosage, and water-to-cement ratio - Hyun-Jun Kim; JunHyuk Jang; Daehui Kim; Tae-Hyuk Kwon; Tae-Young Kim; Song-Hun Chong; Min-Ji Kim; Tae-Min Oh; Hee-Hwan Ryu (Tunnelling and Underground Space Technology, 2026)

EPB41L3 suppresses epithelial-mesenchymal transition and proliferation by attenuating TGF beta signaling pathways - Min Kyung Kim; Byoung-Whui Choi; Hun Gyu Hwang; Hun Soo Chang; Choon-Sik Park; Jong-Uk Lee (Tissue and Cell, 2026)

Combined toxicity of pyrethroid insecticides and azole fungicides in honey bee larvae - Minju Choi; Kyongmi Chon; Juyeong Kim; Hui-Yeon Ahn; Bo-Seon Kim; Bala Murali Krishna Vasamsetti; Chang-Young Yoon; Sojeong Hwang; Kyeong-Hun Park; Ji-Hoon Lee (Environmental Pollution, 2026)

Unlocking dual-site regulation in perovskite-modified separators for efficient polysulfide conversion in lithium-sulfur batteries - Mingxu Li; Byeong hun Oh; Heejin Kim; Dong-Ho Baek; Ying Liu; Dengzhou Liu; Zabrian Dirfan; SuHyeon Ahn; Rong Yang; Jou-Hyeon Ahn; Inseok Seo; Du-Hyun Lim; et al. (Chemical Engineering Journal, 2026)

Exciplex strength as a design principle for high-performance organic light-emitting diodes - Al Amin; Jee-Hun Jang; Woo-Sam Kim; Hanbeen Lee; Jaeho Lee; Rino Choi; Jeong-Hwan Lee (Chemical Engineering Journal, 2026)

Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Current-controlled electrical stimulation regulates growth, redox adaptation, and lipid accumulation in Chlorella vulgaris - Hyun-Jo Ahn; Nikita Yadav; Kung-Won Choi; Ju-Hyeok Kwon; Jung Rae Kim; Byong-Hun Jeon; Kyoung-Yeol Kim (Bioresource Technology, 2026)

Quantifying wave-induced fuel consumption and CO2 emissions: a high-fidelity free-running CFD approach - Daejeong Kim; Chybyung Park; Sung-Ji Kim; Heeseok Kim; Jong-Hun Im; Sang-Deuk Lee; Seungcheol Kwon; Yoonwon Choi; Chulhyun Hong; Mukyeong Kang; Soonseok Song; Tahsin Tezdogan (Ocean Engineering, 2026)

Interpretable machine learning biodegradation of Direct Black 22 by Lysinibacillus sphaericus: Kinetics, mechanism, and wastewater application - Ihtisham Jamil; Ghulam Mustafa; Muhammad Tariq Zahid; Aliya Alvi; Deok-Won Kim; Tehreem Batool; Ramesh Kumar; Farah Rauf Shakoori; Ju-Hyeok Kwon; Hyun-Jo Ahn; Byong-Hun Jeon (Journal of Environmental Chemical Engineering, 2026)

Impact of electrode modifications on electrochemical ammonia stripping across activated carbon membrane electrodes - Hyun-Jo Ahn; Kung-Won Choi; Alfred Navokhi Apaji; Geon-Soo Ha; Byong-Hun Jeon; Kyoung-Yeol Kim (Journal of Environmental Chemical Engineering, 2026)

Comparative assessment of ammonia recovery processes integrated with electrochemical nitrate reduction: exergy and techno-economic analysis - Minseok Im; Konan Alain Cedric Nzisso; Inhye Kim; Jeongjae Oh; Cheol Hun Park; Sunghyun Cho (Journal of Environmental Chemical Engineering, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Integrated evaluation of thermal, hygrothermal, and energy performance of aged building retrofits using ply-lam cross-laminated timber wall assemblies in humid continental climates - Ji Hun Park; Seong Taek Kang; Yujin Kang; Sumin Kim (Energy and Buildings, 2026)

Photocurable low-dielectric polyimide via acrylate side-chain engineering for 3D-printed RF applications - Subin Jo; Seyeon Park; Gwajeong Jeong; Bo-Young Kim; Yongchan Jang; Ji-Hun Seo; Seong-Dae Park; Sungjoon Lim; Hyunseung Yang (Chemical Engineering Journal, 2026)

High-performance bifunctional alkaline water-splitting textile electrodes using monolayer-enhanced chemical reduction of integrated electrocatalysts - Jeongmin Mo; Hyaemin Kim; Jaemin Kim; Wondo Choi; Jaesung Lyu; Beomjune Kim; Minseo Seo; Taeyoung Jeong; Jong Hun Kim; Jun Hyuk Moon; Yoon Jang Chung; Hyeong Jun Kim; et al. (Chemical Engineering Journal, 2026)

Air mass factor sensitivity to a priori profiles in GEMS formaldehyde retrieval during the ASIA-AQ campaign - Gitaek T. Lee; Rokjin J. Park; Hyeong-Ahn Kwon; Jaein I. Jeong; Seungun Lee; Eunjo S. Ha; Yoonbae Chung; Cheol-Hee Kim; Soontae Kim; Chul H. Song; Chang-Keun Song; Jung‐Hun Woo; et al. (Atmospheric Environment, 2026)

Analysis of thermal-hydraulic and aerosol behavior in the VANAM-M3 experiment using the CINEMA code - Dong-Hun Shin; Jaehyun Ham; Sang Ho Kim; Chae Hyun Kim; Young Hee Kim; Yong Hoon Jeong (Annals of Nuclear Energy, 2026)

Linking biogeochemical signatures to archaeal community structure at active methane seeps in the Tatar trough, far eastern Russia - Dong-Hun Lee; Jung-Hyun Kim; Yung Mi Lee; Alina Stadnitskaia; Helge Niemann; Carme Huguet; Young-Keun Jin; Hirotsugu Minami; Akihiro Hachikubo; Kyung-Hoon Shin (Marine Chemistry, 2026)

Co-hydrothermal carbonization of biopolymer and biomass wastes: Sustainable valorization into solid fuel and thermal filler - Jung-Hun Kim; Zambaga Otgonbayar; Thu-Huong Le; Juwon Kang; Seungmook Jung; Jaewon Cha; Suk Jekal; Jiwon Kim; Hyungseok Nam; Chang-Min Yoon; Doyeon Lee (Journal of Environmental Management, 2026)

Paraprobiotic Lacticaseibacillus paracasei HY7017 restores gut microbiota homeostasis and short-chain fatty acid production in cyclophosphamide-induced immunosuppressed mice - So Jeong Lim; Jae Yeon Joung; Ji Hun Jang; Jin Hwan Kim; Jiangyu Li; Nam Su Oh (Food Bioscience, 2026)

Efficient nutrient recovery from source-separated urine via a hybrid Membrane Bioreactor and Electrodialysis (MBR-ED) system - Hanwei Yu; Weonjung Sohn; Sherub Phuntsho; Youngjin Kim; June-Seok Choi; Jong-Hun Lee; Youngkwon Choi; Ho Kyong Shon (Desalination, 2026)

Carbon-negative footprint in syngas production through aquatic plant pyrolysis - Youngju Kim; Jung-Hun Kim; Doyeon Lee; Man Sig Lee; Eilhann E. Kwon (Chemical Engineering Journal, 2026)

Applicability of conventional genotoxicity test guidelines to mRNA vaccines: a four-battery assessment of a SARS-CoV-2 mRNA vaccine candidate - Jae-Hun Ahn; Yun-Soon Kim; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Seo-Hyeon Bae; Jisun Lee; Jae-Hwan Nam; Byeong-Cheol Kang (Toxicological Research, 2026)
mRNA vaccine formulations are generally considered to pose a lower genotoxic risk than conventional small-molecule pharmaceuticals; however, long-term data regarding their potential genotoxicity remain limited. Furthermore, to date, no standardized genotoxicity testing guidelines specifically tailored to the unique characteristics of mRNA vaccines have been formally established. In this study, we conducted a comprehensive genotoxicity assessment of a SARS-CoV-2 Omicron variant mRNA vaccine candidate using a four-test battery, following a modified regimen that accounted for the unique characteristics of mRNA vaccines while adhering to OECD test guidelines: bacterial reverse mutation test (OECD TG 471), in vitro chromosomal aberration test (OECD TG 473), in vitro micronucleus test (OECD TG 487), and in vivo erythrocyte micronucleus test in mice (OECD TG 474). No significant genotoxic effects of the mRNA vaccine candidate were observed in any of the four assays. However, during the design and conduct of this study in accordance with existing genotoxicity guidelines, ambiguity arose as to whether test concentrations should be determined according to the mRNA component or the LNP component. In addition, we observed that, unlike the LNP administered alone, the mRNA vaccine candidate was associated with a reduction in the proportion of PCEs in the in vivo micronucleus assay. Although our mRNA vaccine candidate showed no significant evidence of genotoxicity, the experimental design and dosing regimen highlight the need to refine current regulatory testing guidelines for mRNA vaccines. We anticipate that our findings will contribute to the development of more appropriate genotoxicity guidelines for advanced therapy medicinal products (ATMPs), including mRNA vaccines.

Residents’ willingness to participate in the management of urban green spaces: The case of Umeå, Sweden - Pedro M. Obregon-Santander; Do-hun Kim; Adan L. Martinez-Cruz (Urban Forestry & Urban Greening, 2026)

Heat shock-induced zinc efflux repurposes Arabidopsis E3 ligase EMR as a molecular chaperone - Ho Byoung Chae; Su Bin Bae; Joung Hun Park; Seol Ki Paeng; Seong Dong Wi; Meiai Zhao; Min Gab Kim; Woe-Yeon Kim; Sang Yeol Lee (Molecular Plant, 2026)

Effect of excess and restricted inorganic carbon on biokinetics, nitrous oxide emissions, and microbial community in a full-nitrification bioreactor - Seongbong Heo; Jong Hun Jeon; Sungman Lee; Hyeongju Park; Meng Wang; Jung-Hyun Lee; Young Mo Kim (Environmental Research, 2026)

Associations between environmental metal mixture exposure and urinary DNA adduct biomarkers of oxidative and alkylative damage in adults - Jang-Hun Jeong; Bo-Ri Kim; Jeong-Kyu Ji; Hyemi Lee; Kyung-Hwa Choi; Yong Min Cho; Woo Jin Kim; Young-Seoub Hong; Heon Kim; Yong-Dae Kim; Sang-Yong Eom (Environmental Research, 2026)

SBR-free high-loading anodes enabled by lithium-substituted CNT/CMC adhesive conductive networks for fast-charging lithium-ion batteries - Min Gi Kang; Hyun Jun Song; Hye Seon Kim; Sihyung Lee; Jaeho Kim; Ji Hun Lim; Jeong Yoon Kim; Hyejeong Jeong; Junyoung Park; Junghyun Nam; Chan-Hwa Chung; Pil J. Yoo (Chemical Engineering Journal, 2026)

Hybrid carbon framework of graphitic carbon and bamboo-like CNTs for stable lithium-metal anodes - SungJu Kim; Jae Hun Choi; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2026)

Upcycling battery scrap into commercial-grade graphite anode materials via coal tar-assisted granulation - Jongyun Choi; Tae Hun Kim; Gyujin Song; Sei-Min Park; Ji Chul Jung; Jung-Chul An; Inchan Yang (Chemical Engineering Journal, 2026)

Impact of microstructure and surface energetics on high-pressure methane adsorption in activated carbons for adsorbed natural gas systems - Hun-Seung Jeong; Byung-Joo Kim (Chemical Engineering Journal, 2026)

Osteological development of the larvae and juveniles of Thryssa kammalensis (Clupeiformes: Engraulidae) from the Southwestern Coasts of Korea - Hyeon-Jun Ryu; Se Hun Myoung; Sang-Chul Yoon; Jeong-Hoon Lee; Jin-Koo Kim (Zoomorphology, 2026)

Salicornia europaea extract regulates inflammatory signaling pathways in LPS-stimulated HaCaT cells - Chae Un Lim; Min Jung Kim; Ye Jin Yang; Ji Woong Heo; Hee Ho Kim; Young Hun Kim; Young Woo Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2026)

Integrating high-fidelity hiPSC-cardiomyocytes with AI-driven modeling for enhanced proarrhythmic risk assessment - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Hwan Choi; Choongseong Han; Muhammad Adnan Pramudito; Ki Moo Lim; Dong-Hun Woo (Archives of Toxicology, 2026)
Cardiotoxicity remains the leading driver of drug attrition; however, its prediction remains suboptimal when conventional hERG assays and animal models are used. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) offer a human-relevant alternative that aligns with the CiPA initiative and ICH E14/S7B guidelines. This study validated an integrated platform that combines high-purity hiPSC-CMs with Artificial Intelligence (AI) to enhance the accuracy of predicting drug-induced proarrhythmic risk. Phenotypic characterization of the hiPSC-CMs demonstrated high cardiac differentiation efficiency (cTnT + > 95%) and a predominant ventricular-like identity (MLC-2 V + , 78–84%), ensuring biological relevance for ventricular arrhythmia assessment. Electrophysiological data from 28 CiPA reference compounds were collected via Multielectrode Array (MEA) to train multiple machine learning models. The Artificial Neural Network outperformed the other architectures, achieving a superior ROC-AUC of 0.982. The utility of the platform was evaluated using 12 anticancer agents. Although most drugs showed dose-dependent reductions in impedance-based viability, four compounds (Idarubicin, Erlotinib, Sunitinib, Cyclophosphamide) did not exhibit overt structural cytotoxicity. However, MEA analysis revealed significant functional perturbations, including FPDcF prolongation, in sunitinib- and erlotinib-treated samples after long-term treatment. The AI model subsequently classified these two agents as high-to-intermediate risk for Torsades de Pointes (TdP), thereby quantifying their time-dependent proarrhythmic liabilities. These findings show the platform’s ability to detect hidden functional cardiotoxicity, often missed by standard viability assays. The AI-hiPSC-CM system offers a high-throughput, early-stage safety screening tool that bridges in vitro data and clinical outcomes with a standardized risk assessment framework.

A new ursane-type triterpene and potent antibacterial alkylbenzoquinones from the aerial parts of M aesa balansae - Hieu Nguyen-Ngoc; Bui Thi Thu Trang; Cuong Quoc Nguyen; Quang De Tran; Dang Ngoc Quang; Vu Dinh Hoang; Nguyen Huu Tung; Ngoc Binh Vo; Duc Trong Nghiem; Minh Thi Tran; Hun Kim; Nguyen Van Minh; et al. (Natural Product Research, 2026)

Nonclinical safety evaluation strategies for mRNA/LNPs platform agents: Evidence from comprehensive animal toxicity studies - Jae-Hun Ahn; Na-Young Lee; Hee-Jin Bae; Jooil Kim; Jina Kwak; Euna Kwon; Gahyun Roh; Seo-Hyeon Bae; Soo-Yeon Lee; Il Kwon Hwang; Jisun Lee; Hyo-Jung Park; et al. (Toxicology Letters, 2026)

Synergistic effects of seaweed powder and rheology modifiers on the reaction mechanism and pore architecture of geopolymer - Hyun-Soo Lee; Joo-Young Kim; Jae-Suk Ryou; Byeong-Hun Woo; Hong-Gi Kim (Journal of Cleaner Production, 2026)

Alkaline-compatible Nb18W16O93/NiHPO4 complementary electrochromic devices for solar heat regulation - Kwang-Mo Kang; Young-Hun Kim; Ji-Hyeong Lee; Woo-Seok Choi; Mina Ryu; Seong-Jong Hwang; Yoon-Chae Nah (Chemical Engineering Journal, 2026)

Tailored medium-entropy Si alloy anodes with multi-element Fe-site substitution for high-performance Li-ion batteries - Byeong Guk Kim; Jung-Hyeok Park; Jihyeon Ryu; Kyungmin Do; Dong Gyun Hong; Tae-Hyun Kwon; Oh Sung Kwon; Insung Jang; Jaeik Hyun; Geon-Hyoung An; Youngoh Kim; Geon-Woong Lee; et al. (Chemical Engineering Journal, 2026)

Simultaneous bioelectricity generation and selective copper recovery via controlled two-step discharge strategy in a two-chamber microbial fuel cell using an unbuffered copper catholyte - Jun Hyun Kim; Hyeong Jae Kim; Dong Hun Lee; Sunghyun Kim (Bioresource Technology, 2026)

Impact of heat on respiratory health: Age- and sex-specific risks in a nationwide Korean study (2014–2019) - Joonho Ahn; Jongmin Oh; Ho-Jang Kwon; Hyungryul Lim; Jonghyuk Choi; Sanghyuk Bae; Kyoung-Nam Kim; Mi-Ji Kim; Jong-Hun Kim; Youn-Hee Lim (International Journal of Biometeorology, 2026)
Respiratory diseases pose a major global public health challenge. With climate change contributing to more frequent and intense heat events, understanding the effects of high temperatures on respiratory health is increasingly critical. However, existing evidence remains inconsistent. A nationwide time-series study was conducted to evaluate the association between daily maximum temperatures and emergency department (ED) visits for cause-specific respiratory diseases across 16 regions in South Korea during the warm season (April–September) from 2014 to 2019. Generalized additive models with quasi-Poisson regressions were applied, adjusting for long-term trends, humidity, day of the week, and air pollutants. Subgroup analyses were performed by age and sex. Each 1 °C increase in maximum temperature was associated with a significant increase in ED visits for total respiratory diseases (relative risk [RR] = 1.008; 95% confidence interval [CI]: 1.006–1.009). Stronger associations were observed for pneumonia (RR = 1.014; 95% CI: 1.012–1.016), COPD (RR = 1.010; 95% CI: 1.007–1.012), asthma (RR = 1.009; 95% CI: 1.007–1.011), and upper respiratory infections (RR = 1.005; 95% CI: 1.003–1.007). Males, children (< 15 years), and the elderly (≥ 65 years) were particularly vulnerable. High ambient temperatures are significantly associated with increased ED visits for respiratory diseases. These findings provide important evidence to guide governmental decision-making in developing heatwave preparedness policies, including targeted interventions, early warning systems, and healthcare resource planning for vulnerable populations.

Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Prediction of Seismic Earth Pressure on Basement Walls of Buildings with Rigid Base Conditions - Quang Thien Buu Nguyen; Tae-Hun Hwang; Sung-Ryul Kim (Bulletin of Earthquake Engineering, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

Simplified analytical method for dropped object assessment in offshore and new fueled ship - Jung Kim; JongWon Kim; Hoki Lee; Jung-Kwan Seo; Jong-Hun Woo (Ocean Engineering, 2026)

Polystyrene nanoplastic-encapsulated extracellular vesicles promote blood–brain barrier breakdown and accumulate in the brain - Min Jae Kim; Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Jae-Eon Lee; Hyeon-Gu Kang; DongJoo Joung; Eui-Man Jung; Beum-Soo An (Journal of Hazardous Materials, 2026)

Evaluation of electrostatic spray technology under varied particle characteristics and spray-solution compositions for particulate matter control - Yong-Hwan Oh; Seo Hee Seo; Sang-Hee Jo; Tae-Hun Kim; Youn-Suk Son (Journal of Environmental Chemical Engineering, 2026)

Pathogenicity and transmission dynamics of Gryllus bimaculatus densovirus (GbDV), a significant pathogen in cricket farms in South Korea - Chan-Ouk Kim; Eunsun Kim; June-Sun Yoon; Kibeom Park; Sangmin Ji; Ji-Young Choi; Jeong-Hun Song (Journal of Asia-Pacific Entomology, 2026)

Ferroelectric field gating-assisted thermoelectric energy conversion - Ji Young Park; Sun-Woo Kim; Byoungjin Yoon; Youngbo Shim; Do-Heon Kim; Seong Wook Cho; Jun Chen; Young Hun Jeong; Sangwoo Ryu; Hak Ki Yu; Zhong Lin Wang; Hyesung Park; et al. (Chemical Engineering Journal, 2026)

Improvement of color purity and operational lifetime for PhOLEDs based on tetradentate Pt (II) complex - Hyunmin Cho; Jinwoong Hong; Young Hun Jung; Se Chan Cha; Mi Young Chae; Soon-Ki Kwon; Yun-Hi Kim; Jang Hyuk Kwon (Chemical Engineering Journal, 2026)

Citrate-enabled process intensification reinforces energy and redox metabolism for sustainable bioproduction using Corynebacterium glutamicum - KwangYoung Park; Hoe-Suk Lee; Dong Young Lee; June-Ho Choi; Yunhee Jeong; SunJoo Park; Yunjeong Song; Jiyoung Park; Chan-Duck Jung; Hoyong Kim; Sung-Hyun Jo; Yun-Gon Kim; et al. (Bioresource Technology, 2026)

Lactobacillus Plantarum Q180 Attenuates Hepatic Lipid Accumulation and Regulates Energy Metabolism in High-Fat Diet-Induced Obese Mice - Minseo Cho; Hyunchae Joung; Hyunsoo Jang; Yeon-Woo Kim; Jaeryang Chu; Yoo Jin Kwon; Chang Hun Shin; Jung-Heun Ha; Jisu Lee (Probiotics and Antimicrobial Proteins, 2026)

Arsenic Removal from Alkaline Mine Drainage Using Waste Sludge: Pilot-Scale Experiments at an Abandoned Mine in South Korea - Chan-Ung Kang; Youn Soo Oh; Hyun-Sung Park; Oh-Hun Kwon; Kang Ho Kim; Ho Young Jo (Mine Water and the Environment, 2026)

Development of a two-dimensional thermal network model for performance prediction of printed circuit steam generators - Hyunjun Cho; Seok Kim; Cheong Bong Chang; Youngmin Bae; Hun Sik Han (Annals of Nuclear Energy, 2026)

Weathered plastic particles negatively affect mouse primary neurons and glial cells - Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Yunsoo Chang; Min Jae Kim; DongJoo Joung; BuHyun Youn; Eun-Hee Lee; Eui-Man Jung (Archives of Toxicology, 2026)

Development of an integrated physiologically based toxicokinetic-toxicodynamic model for quantitative prediction of polyhexamethylene guanidine-induced human toxicity - Ji-Hun Jang; Dae-Han Park; Jong-Jin Kim; Yong Joo Park; Kyu Hyuck Chung; Hye-Jin Kim; Haewon Kim; Seung-Hyun Jeong (Archives of Toxicology, 2026)

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Rare earth elements as tracers of anthropogenic sources and the influence of land-based aquaculture effluent on trace elements in coastal waters of Jeju Island, Korea - Ijin Lim; Jumi Kim; Wonjin Choi; Jiwoo Kim; Seongha Kim; Seung-Hee Kim; Dong-Hun Lee; Seok Jin Oh; Chulin Sun; Sung-Eun Park; Weol Ae Lim; Taejin Kim (Regional Studies in Marine Science, 2026)

Methanotrophic community structure and metabolic potential in the sulfate–methane transition zone of the ARAON mounds, Arctic Chukchi Sea - Jehyun Jeon; Dong-Hun Lee; Ji-Hoon Kim; Yeonjin Choi; Young Keun Jin; Jong Kuk Hong; Yung Mi Lee (Marine Environmental Research, 2026)

Synergistic recruitment of exogenous and endogenous stem cells by an SDF1-mimetic peptide–loaded click-crosslinked hyaluronic acid dressing for enhanced wound healing - Yejin Lee; Young Hun Kim; Sangdun Choi; Moon Suk Kim (Chemical Engineering Journal, 2026)

Oligomeric strategy for ether-free multiblock copolymer anion exchange membranes with ordered ionic channels for efficient alkaline water electrolysis - Jin Hyuk Kim; Eun Woo Lee; Hyuk Jin Roh; Jae Hun Lee; Jong Hak Kim (Chemical Engineering Journal, 2026)

An Integrated Framework for MOSAIC-AQNEA Emission Inventory Development in Northeast Asia - Minwoo Park; Younha Kim; Youjung Jang; Hyejung Hu; Satoru Chatani; Shuxiao Wang; Zbigniew Klimont; Jung-Hun Woo (Asia-Pacific Journal of Atmospheric Sciences, 2026)
Air pollutant emissions in Northeast Asia play a critical role in regional air quality and transboundary pollution. This study presents the development of the MOSAIC-AQNEA emission inventory framework, integrating country-specific emission inventories for six countries: China, South Korea, Japan, North Korea, Mongolia, and the Asian part of Russia. A mosaic approach was applied to combine nationally developed inventories under a unified sectoral classification scheme. The inventory includes major seven pollutants (SO 2 , NOₓ, PM 10 , PM 2.5, NH 3 , NMVOCs and CO) for the base year 2019. While PM 10 and PM 2.5 are explicitly distinguished in the emission inventory and model processing, they are occasionally referred to collectively as PM in the text for brevity. To support air quality modeling, the compiled inventories were processed using the SMOKE-Asia system to generate model-ready inputs. The resulting gridded emissions provide a consistent, high-resolution dataset representing regional emission characteristics. Analysis by sector, pollutant, and intensity metrics (Emissions per GDP and per Population) revealed distinct structural differences among countries, reflecting variations in energy systems, industrial activities, and socioeconomic conditions. This study provides a comprehensively integrated, model-ready emission inventory framework that consistently integrates national inventories across Northeast Asia under a unified processing structure. The framework ensures cross-country comparability through systematic sector mapping, bottom-up emission based downscaling, and consistent chemical speciation. The resulting dataset offers a transparent and directly usable emission input for regional air quality modeling and policy-relevant assessments.

Multimodal Graphical Network Analysis of Small-for-Gestational-Age in Preterm Infants: Integrating Neonatal Brain Volume, Structural Connectivity, and Early Neurodevelopmental Outcome - Se Hyun Lee; Yong Hun Jang; Hyuna Kim; Gang Yi Lee; Hyun Ju Lee; Hyun Ho Kim (Annals of Biomedical Engineering, 2026)
Purpose Infants born Small-for-gestational-age (SGA) face heightened risks for cognitive and language impairments. The neurobiological mechanisms underlying these deficits remain unclear. This study aimed to identify multimodal neuroimaging biomarkers associated with fetal growth restriction and to characterize network-level associations linking SGA to early neurodevelopmental vulnerability using a data-driven graph-based framework. Methods In this prospective cohort of 186 preterm infants, near-term brain magnetic resonance imaging (MRI) and Bayley-III developmental assessments were analyzed. Multimodal imaging features—including volumetric indices from T2-weighted MRI and diffusion metrics from diffusion tensor imaging—were integrated with perinatal data. A sparse partial-correlation network was estimated using the Graphical Lasso algorithm (λ optimized via cross-validation) to infer conditional dependencies among features. Variables directly connected to birthweight Z-scores were identified as candidate biomarkers and validated for SGA classification and developmental outcomes using logistic regression and correlation analyses. Results Network analysis identified eight neuroanatomical correlates of birthweight Z-scores, including increased cerebrospinal fluid (CSF) volume; elevated axial, mean, and radial diffusivity in the left inferior longitudinal fasciculus (ILFL); higher axial diffusivity in the inferior fronto-occipital fasciculus; and altered degree centrality in the right precentral and posterior cingulate cortices (PCC). Logistic regression revealed CSF volume and ILFL diffusivity as independent predictors of SGA. Infants with language delay showed trend-level increases in ILFL diffusivity and reduced PCC centrality after FDR correction, suggesting possible associations between microstructural and connectomic alterations and language vulnerability. Conclusion By integrating volumetric and diffusion MRI with graph-based modeling, this study uncovers latent neurobiological markers of SGA and provides clinically interpretable biomarkers for early risk stratification and individualized intervention.

Multi-Scale Temporal Uncertainty-Aware Hierarchical Adaptive Ensemble for Intelligent Ship Emission Monitoring and Prediction - Duc-Anh Pham; Kyeong-Ju Kong; Jung-Min Kim; Hee-Sung Yoon; Seung-Hun Han (Journal of Marine Science and Engineering, 2026)
This paper presents a novel Multi-Scale Temporal Uncertainty-aware Hierarchical Adaptive Ensemble (MSTU-HAE) algorithm for intelligent ship emission monitoring and prediction in maritime environmental compliance applications. The maritime shipping industry contributes approximately 3% of global CO2 emissions and significant amounts of nitrogen oxides and sulfur oxides, necessitating advanced predictive monitoring systems. The proposed MSTU-HAE algorithm integrates three key innovations: multi-scale temporal feature extraction using causal convolutions at short-term (5 samples), medium-term (20 samples), and long-term (60 samples) windows; gas-specific attention mechanisms that automatically weight temporal scales based on individual emission gas characteristics; and three-level hierarchical uncertainty quantification encompassing individual model uncertainty, ensemble disagreement, and regulatory compliance risk assessment. Experimental validation was conducted using emission data collected from a fishing vessel over 3 operational days (1732 original samples), augmented to 17,320 samples via controlled replication with noise injection to support model training. Rigorous temporal data splitting with 70%/15%/15% train/validation/test partitioning ensures no data leakage. Comparative analysis against six baseline methods (XGBoost, LSBoost, AdaBoost, Ridge Regression, Random Forest, and K-Nearest Neighbors) demonstrates that MSTU-HAE achieves superior average performance, with R2 = 0.9670 and NSE = 0.9670 across all emission gases. This research contributes a robust, interpretable, and scalable prediction framework that advances the state of the art in maritime environmental monitoring through novel algorithmic innovations in temporal feature learning and uncertainty quantification.

Quantitative Assessment of Third Molar Extraction Difficulty and Nerve Injury Risk Using Artificial Intelligence and Image Processing - Jihyeong Ko; Sasi Sooksatra; Seungmin Kim; Shaohua Tang; Jung-Eun Ha; Dong-Hun Han; Kyu Hwan Lee; Young-jin Jung; Min-Ji Kim (Annals of Biomedical Engineering, 2026)

pH-dependent behavior of uranium(VI) removal by indigenous bacteria under deep geological repository conditions - Dawoon Jeong; Min Hoon Baik; Euo Chang Jung; Hee-Kyung Kim; Myoung-Soo Ko; Ji-Hun Ryu (Journal of Environmental Chemical Engineering, 2026)

Integrated electrode-electrolyte Interface engineering strategy using potassium trimethoxy (trifluoromethyl) borate for lithium-metal batteries - Thi Huong Pham; Van-Chuong Ho; Hun-Gi Jung; Jung-Gu Kim; Jung Ho Kim; Junyoung Mun (Chemical Engineering Journal, 2026)

Sustainable production of high-yield torch ginger nanocellulose using a one-step H2SO4/H2O2 method - Herman Marius Zendrato; Nanang Masruchin; Siti Nikmatin; Nam Hun Kim; Seung Hwan Lee; Nyoman Jaya Wistara (Biomass and Bioenergy, 2026)

Microbial markers of resilience and its correlation with reproductive performance in lactating sows under heat stress condition - Abdolreza Hosseindoust; Jun Young Mun; Sang Hun Ha; Habeeb Tajudeen; Priscilla Neves Silvestre; Jae Cheol Jang; Jin Soo Kim (Tropical Animal Health and Production, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

White ginseng ethanol extract inhibits melanogenesis in B16F10 cells by regulating the microphthalmia-associated transcription factor/tyrosinase pathway - Min Jung Kim; Ye Jin Yang; Ji Woong Heo; Han Nim Choi; Chae Un Lim; Se Hyo Jeong; Hun Hwan Kim; Gon Sup Kim; Young Hun Kim; Ju-Hye Yang; Kwang Il Park (Molecular & Cellular Toxicology, 2026)

Analysis of genetic relationships between five sheep breeds using microsatellite markers - Won-Sok Ri; Song-Hyok Kim; Song-Hyok Pak; Sam-Rang Song; Un-Hyang Ho; Song-Hun Jang; Chung-Il Yo (Agricultural Research, 2026)

Age-related increase of NLRC4 inflammasome and TGF-β1 signaling exacerbates airway inflammation and remodeling in asthma - Jin-Hwa Kim; Hyun-Tae Kim; Jeong-Won Kim; Ji-Soo Jeong; Su-Ha Lee; Kwan-Hoo Kim; Na-Young Kim; Young-Hun Kim; Je-Won Ko; Tae-Won Kim (GeroScience, 2026)

Environmental factors on microalgal resuspension and dynamics in tidal flats on the west coast of Korea - Hosang Kim; Junghyun Lee; Hun Jun Ha; Sun Min Choi; Yangrae Rho; Jinsoon Park; Ho Kyung Ha; Bong-Oh Kwon; Jong Seong Khim (Marine Pollution Bulletin, 2026)

Dual-function of nitrogen removal and autoinducer-2 quorum quenching improves MBR performance in treating TMAH-containing wastewater - Hyunjung Kim; Seung-Hun Baek; Gyeongho Choi; Jinju Han; Chang Hyun Nahm; Kibaek Lee (Journal of Hazardous Materials, 2026)

Electron beam-induced decomposition of nitrous oxide (N2O) and the critical role of oxygen - Jieun Son; Sang-Hee Jo; Yong-Hwan Oh; Tae-Hun Kim; Tak-Hyun Kim; Seungho Yu (Journal of Environmental Management, 2026)

Translational toxicokinetics of chloromethylisothiazolinone/methylisothiazolinone: Radioactivity-associated materials-physiologically based toxicokinetic modeling and human dose extrapolation - Ji-Hun Jang; Chi-Ho Lee; Yong Joo Park; Kyu Hyuck Chung; Hye-Jin Kim; Haewon Kim; Seung-Hyun Jeong (Environmental Research, 2026)

Thermal-responsive nanohole surface with active antibacterial properties against Staphylococcus aureus - Hee-Kyeong Kim; Se Hun Kim; Rigoberto Lopez Reyes; Dongyan Chen; Batzorig Buyantogtokh; Seungbum Hong; Young-Sam Cho; Hyun-Ha Park (Chemical Engineering Journal, 2026)

Integrating IAM-based CO2 projections and traffic demand forecasting for regional CO2 emission mapping in the transport sector - Hyejung Hu; Min-Young Choi; Bomi Kim; Minje Choi; Sunggu Kang; Hyejin Park; Minwoo Park; Jinseok Kim; Jung-Hun Woo (Atmospheric Pollution Research, 2026)

Biological upcycling of conditionally biodegradable plastics: enzymatic depolymerization to microbial valorization and consolidated bioprocessing frameworks - Yunhee Jeong; Sol Min Han; Jieun Wu; KwangYoung Park; Yunjeong Song; Yung-Hun Yang; Kyung-Jin Kim; Jungoh Ahn; Kyungmoon Park; See-Hyoung Park; Si Jae Park; Eun Ju Yun; et al. (Systems Microbiology and Biomanufacturing, 2026)

Long-Term Variability and Ecological Structure of Macrobenthic Polychaete Communities in Korean Coastal Waters: A 30-Year (1993–2022) Data-Based Assessment - Geon Kim; Kyeong Hun Lim; Jung Ho Lee; Sung Wan Park; Hyun Chool Shin (Ocean Science Journal, 2026)

Effect of Foliar Treatment with Organic Acids and Inorganic Nutrients on Yield Retention and Secondary Metabolite Profiles under Heat Stress in Soybean - Hakyung Kwon; Hong-Ju Lee; Dong Yeol Song; Sang Hun Kim; Chan Hui Lee; Kyung-Hee Kim; Byung-Moo Lee; Sung Don Lim; Jungmin Ha (Journal of Plant Growth Regulation, 2026)
Foliar application of inorganic nutrients and organic acids can affect the metabolic profile of soybean leaves and enhance soybean productivity. In this study, we investigated whether foliar application of 12 inorganic nutrients [N, P, K (10 g L −1 each); Ca, Mg, B, Zn, Fe, Cu, Mo, Si (200 g L −1 each); Se (20 g L −1 )] and five organic acids [acetic, ascorbic, citric, formic, and malic acids (200 mM each)] could alter secondary metabolite pathways and improve yield under heat stress. Treatment with Fe, Ca, and Mg induced accumulation of 3,4-dihydroxybenzoic acid, with subsequent increases in downstream isoflavones, while application of Se, Mo, Zn, P, and acetic acid led to a decrease in biochanin A, along with correlated changes in other metabolites including caffeic acid and daidzin. N and Si treatment independently increased cinnamic acid content. Ca and P treatment enhanced the accumulation of glycitin and genistein, while acetic acid treatment increased the accumulation of glycitin and daidzin. Treatment significantly altered secondary metabolite profiles in soybean leaves and alleviated yield loss under heat stress, although individual metabolite concentrations showed no significant correlations with this effect. Heat-stress tolerance mediated by metabolites appears to arise from comprehensive changes in the metabolic profile rather than the effect of a single metabolite. Overall, foliar applications reshaped leaf metabolite networks and improved yield retention under heat stress, with the largest profile shifts under P, Ca, and Mg. Follow-up physiological and enzymatic assays are recommended to establish causality for heat stress mitigation and metabolite enhancement. These findings suggest soybean leaves as a valuable source of beneficial secondary metabolites and indicate new options for soybean use and cultivation value.

Evolution and spread of H8Nx avian influenza viruses from wild birds in East Asia, 2019-2024 - Sae-hyeon Park; Sun-Hak Lee; Ye-Ram Seo; Dong-Ju Kim; Young-Jae Si; Hyesung Jeong; Suwoong Lee; Chang-Seon Song; Dong-Hun Lee (Archives of Virology, 2026)

Fatigue Behavior of 66 kV Wet-Type Submarine Cable for a Flexible Pull-In Installation System - Yun-Jae Kim; Dong-Suk Hong; Hyun-Kyung Kim; Yong-Hun Jung; Sung-Woong Choi (Journal of Marine Science and Engineering, 2026)
This work focuses on evaluating the fatigue characteristics of a 66 kV wet-type submarine cable. The analysis incorporates realistic offshore environmental conditions and considers installation through a flexible pull-in system. The target system was deployed at the Southwest Offshore Wind Farm in Korea, where the structural response of the cable is governed by combined wave- and wind-induced loading. To determine the ultimate limit state (ULS) behavior of the cable arranged in the flexible pull-in installation configuration, a global dynamic analysis was initially performed, from which time-dependent displacement histories were extracted under site-specific metocean conditions. The results indicate that lateral wave-induced loading dominates the global response owing to the vertically suspended configuration of the flexible pull-in installation system. A detailed local fatigue analysis was performed based on the critical loading scenarios identified from the global analysis. Prior to the fatigue evaluation, a numerical modeling approach for the local analysis of the 66 kV wet-type submarine cable was developed and validated through comparisons with experimental tensile test results. The developed numerical model successfully captured the axial stiffness characteristics and deformation response of the cable, demonstrating a discrepancy of less than 1% between the numerical predictions and experimental measurements. Fatigue analyses were performed for 120 displacement-based time-history loading cases derived from the global dynamic response. The results show that the fatigue damage is predominantly concentrated in the steel-wire armor, particularly near the fixed boundary region, identifying it as the governing fatigue-critical component. In addition, a parametric study of the wire-armor helix angle revealed that increasing the helix angle significantly improved the fatigue life by enhancing the bending flexibility and reducing the stress concentration under transverse loading. These findings provide practical insights into the fatigue-resistant design and optimization of wet-type submarine cables installed using flexible pull-in installation systems in floating offshore wind applications.

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Lantapenoids A–C from the aerial parts of Vietnamese Lantana camara - Tran Thi Minh; Tran Thi Minh Trang; Duong Hoang Thuc; Vu Dinh Hoang; Le Dang Quang; Hun Kim; Minh Van Nguyen; Gyung Ja Choi (Phytochemistry Letters, 2026)

Antiviral potential and mode of action of Metarhizium pinghaense 15R-derived polysaccharide against baculovirus - Jiwon Jang; Gui Hwan Han; Seong Hun Im; Jeong Won Kim; Soo Dong Woo; Tae Young Shin (Journal of Invertebrate Pathology, 2026)

Polydeoxyribonucleotides isolated from the food fermentation strain Enterococcus faecium mitigate neuroinflammation via MAPK-mediated BMP/SMAD/Wnt regulation under neuro-oxidative stress - Da Hye Song; Yu-Rim Lee; Seung Min Yu; Soo Youn Lee; Sae-Hun Kim; Jeung Hee An (Food Bioscience, 2026)

Gaussian process-based data augmentable deep Bayesian neural network: Application to estimate the stress transfer length in pretensioned concrete beams - Byeong-Hun Woo; Dong-Hun Choi; Chan-Hyuk Park; Jee-Sang Kim; Jae-Suk Ryou; Kyung-Suk Yoo (Engineering Structures, 2026)

Tuning surface oxygen functionalities for high-efficiency NO removal via improved metal dispersion on porous carbon fibers - Hun-Seung Jeong; Byung-Joo Kim (Chemical Engineering Journal, 2026)

Targeting antifungal therapy with Dectin-1-coated solid lipid nanoparticles in a rat model of spinal fungal infection - Gi-Beom Ju; Gong Ho Han; Seong Jun Kim; Daye Lee; Min Je Kim; Seung Hun Sheen; Min Jai Cho; Seil Sohn (Chemical Engineering Journal, 2026)

Single-tube total analysis system for ratiometric detection of exosomal miRNAs in breast cancer diagnosis - Myeong-Jun Lee; Jeong-Hyeop Shin; Seung-Hun Jung; Ha Rim Ahn; Young Jo Kim; Jeong-Woo Choi; Jin-Ha Choi; Byung-Keun Oh (Chemical Engineering Journal, 2026)

Enhanced aromatics production via catalytic pyrolysis of poly(3-hydroxybutyrate) using ZSM-5 catalysts - Haneul Shim; Jong Hun Kang; Kanghee Cho; Jeong-Chul Kim; Yong Jun Choi; Young-Kwon Park (Bioresource Technology, 2026)

Integrating thermal bridge analysis with life-cycle assessment: energy and environmental performance of Ply-Lam CLT envelopes in ZEB-Level apartments - Ji Hun Park; Hyeonseong Yuk; Seong Taek Kang; Sumin Kim (Building and Environment, 2026)

Indoor Environmental and Energy Performance Analysis of Horizontal BIPV Windows and Their Potential to Meet South Korean ZEB Standards - A Young Kim; Bo Rang Park; Yong Gi Jung; Sang Hun Yeon; Yongseok Jun; Jin Woo Moon (Building and Environment, 2026)

Pilot-scale assessment of slag reactors for manganese removal from mine drainage - Dae-Gyu Im; Duk-Min Kim; Hye-Lim Kwon; Joon-Hak Lee; Oh-Hun Kwon; Seong-Taek Yun (Environmental Geochemistry and Health, 2026)

Predicting the invasion potential of unintroduced alien plants in Korea using connectivity indices and ecological niche models - Hyungsoon Jeong; Joung Hun Park; Yun Jeong Cho; Dayeong Kim; A-Ram Jo (Biological Invasions, 2026)

A new alkaloid glycoside and antifungal metabolites from the aerial parts of Argemone mexicana Linn. collected in Vietnam - Thi Minh Tran; Minh Hieu Do; Thuy Nga Nguyen; Hoang Chung Nguyen; Thi Phuong Anh Dinh; The Vinh La; Dang Quang Le; Hun Kim; Nguyen Minh Van; Gyung Ja Choi; Dinh Hoang Vu (Natural Product Research, 2026)

Phylogenetic Position of the Morphologically Ambiguous Genus Leiochrides (Annelida: Capitellidae) Revealed by Its First Complete Mitogenome - Dae-Hun Kim; Junsang Youn; Junil Ko; Hyeryeong Oh; Haelim Kil; Seong-il Eyun; Man-Ki Jeong (Journal of Marine Science and Engineering, 2026)
The family Capitellidae performs critical roles in bioturbation and sediment remediation within global marine benthic ecosystems. However, they are a taxonomically challenging group due to their simple morphology and a ‘morphological mosaic’, where traditional classificatory traits, such as thoracic chaetiger counts, appear convergently across genera. Previous multi-locus studies (using 18S, 28S, H3, and COI) first highlighted this conflict, revealing the polyphyly of major genera like Notomastus and even Leiochrides itself (based on unidentified specimens). More recently, mitogenomic studies uncovered massive gene order rearrangements and a conflicting topology but did not include Leiochrides. Critically, with no complete mitogenome reported for a formally identified Leiochrides species, its true phylogenetic position and the validity of its polyphyly remain unresolved. To address this critical gap, we sequenced and characterized the first complete mitochondrial genome from a formally identified species, Leiochrides yokjidoensis, recently described from Korean waters. The complete mitogenome was 17,933 bp in length and included the typical 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), and 22 transfer RNAs (tRNAs). Gene order (GO) analysis revealed the occurrence of gene rearrangements in Capitellidae and in its sister clade, Opheliidae. A phylogenomic analysis using the amino acid sequences of 13 PCGs from 30 species established the first robust systematic position for the genus Leiochrides (based on this formally identified species). Phylogenetic results recovered Leiochrides as a sister group to the clade comprising Mediomastus, Barantolla, Heteromastus, and Notomastus hemipodus (BS 99%). This distinct placement confirms that Leiochrides represents an independent evolutionary lineage, phylogenetically separate from the polyphyletic Notomastus complex, despite their morphological similarities. Furthermore, our analysis confirmed the polyphyly of Notomastus, with N. hemipodus clustering distinctly from other Notomastus species. Additionally, signatures of positive selection were detected in ND4, and ND5 genes, suggesting potential adaptive evolution to the subtidal environment. This placement provides a critical, high-confidence anchor point for the genus Leiochrides. It provides a reliable reference to investigate the unresolved polyphyly suggested by previous multi-locus studies and provides compelling evidence for the hypothesis that thoracic chaetiger counts are of limited value for inferring phylogenetic relationships. This study provides the foundational genomic cornerstone for Leiochrides, representing an essential first step toward resolving the systematics of this taxonomically challenging family.

Erythropoietin-derived Non-erythropoietic Peptides Conferring Oxidative Stress Resistance to Keratinocytes and Fibroblasts - Min Ae Han; Janbolat Ashim; Youngheum Ji; Eunho Kang; Minchan Jeong; Sung Jae Kim; Wookyung Yu; Jin Hae Kim; Cheil Moon; Chang-Hun Lee (Cell Biochemistry and Biophysics, 2026)

Semantic segmentation of plastic greenhouse frames and its application to finite element model reconstruction for structural response assessment - Byung-hun Seo; Sangik Lee; Jong-hyuk Lee; Yejin Seo; Dongwoo Kim; Yerim Jo; Jeongmin Lee; Won Choi (Computers and Electronics in Agriculture, 2026)

Non-ionic detergent-based screening method for poly (butylene adipate-co-terephthalate) (PBAT)-degrading microorganisms - Yebin Han; Jinok Oh; Ayeon Kim; Jong-Min Jeon; Baeksoo Park; Jeong-Jun Yoon; Shashi Kant Bhatia; Yung-Hun Yang (Waste Management, 2026)

Methane decomposition and characterization of conversion products in a continuous process via electron beam irradiation - Sang-Hee Jo; Jieun Son; Tae-Hun Kim; Tak-Hyun Kim; Seungho Yu (Process Safety and Environmental Protection, 2026)

Integrated MEA for polymer electrolyte membrane fuel cells enabled by freeze–casting and direct membrane deposition - Hyeon-Seung Jung; Seung Tae Lee; Seung-Hyeon Moon; Chanho Pak; Jae-Hun Kim (Chemical Engineering Journal, 2026)

Enhancing sulfur tolerance in Pt/TiO2 catalysts: Effect of H2O in CO oxidation - Haneul Kim; Kwang Hyun Kim; Joonwoo Kim; Ja Hun Kwak (Chemical Engineering Journal, 2026)

Comparative analysis of hydrodynamic and reactor design effects on performance in bioreactors - Parth Shah; Satchit Nagpal; Dong Hun Kwak; Jung Ho Kim; Jae Hoon Cho; Jun-Woo Kim; Kosan Roh; Sang Min Park; Joseph Sang-II Kwon (Chemical Engineering Journal, 2026)

Critical interplay between PAF receptor and PKCδ is involved in dopaminergic insult evoked by methamphetamine in mice - Quynh Dieu Trinh; Ji Hoon Jeong; Naveen Sharma; Yen Nhi Doan Nguyen; Jung Hoon Park; Duc Toan Pham; Hoang-Yen Phi Tran; Duy-Khanh Dang; Dae-Joong Kim; Dae-Hun Park; Toshitaka Nabeshima; Hyoung-Chun Kim; et al. (Chemico-Biological Interactions, 2026)

Development of a Polycyclic Aromatic Hydrocarbons (PAHs) emission inventory in Korea - Min-Young Choi; Jinseok Kim; Hyejung Hu; Jiyi Lee; Ahn Lee; Jaeyoon Lee; Younha Kim; Jung-Hun Woo (Atmospheric Environment, 2026)

Environmental Risk Assessment of Dinoseb in Freshwater, Sediment, and Soil Media in Korea - Inhye Lee; Daeyeop Lee; Hun-Je Jo; Hyun Soo Kim; Kyung Sook Woo; Kyunghee Ji (Bulletin of Environmental Contamination and Toxicology, 2026)

Field‐Usable Lateral Flow Immunochromatographic Assay for Rapid Detection of Infectious Haematopoietic Necrosis Virus ( IHNV ) - Choon‐Sup Kim; Kyoung‐Hui Kong; Sung‐Hun Lee; Wi‐Sik Kim (Journal of Fish Diseases, 2026)
A lateral flow immunochromatographic assay (LFIA) was developed for the rapid detection of infectious haematopoietic necrosis virus (IHNV, genogroups JRt‐N and JRt‐S) in rainbow trout ( Oncorhynchus mykiss ). The assay utilises the monoclonal antibody (mAb) IHNV‐3, which serves as both the detector antibody in a colloidal gold‐mAb conjugate and the capture antibody on the test line. The LFIA strip demonstrated a detection limit ranging from 10 5.05 to 10 5.8 TCID 50 /100 μL for six IHNV isolates (genogroups JRt‐N and JRt‐S) and showed no cross‐reactivity with other fish viruses. Field validation using spleen samples from 81 IHNV‐infected and 102 non‐infected rainbow trout revealed a specificity of 100%, a sensitivity of 97.5%, and an overall diagnostic effectiveness of 98.9%. These results highlight the LFIA strip as a reliable tool for the rapid (within 10 min) on‐site detection of IHNV in rainbow trout at aquaculture facilities.

Modulation of tofacitinib pharmacokinetics by isosakuranetin in streptozotocin-induced diabetic rats - Hyeon Gyeom Choi; Sung Hun Bae; So Yeon Park; Hyoungsu Kim; Sun-Young Chang; So Hee Kim (Journal of Pharmaceutical Investigation, 2025)

Long-range transport of short-lived nitrogen dioxide in East Asia - Seung-Hee Baek; Hyo-Jung Lee; Hyun-Young Jo; Cheol-Hee Kim; Min-Jun Park; Jong-Min Kim; Juseon Bak; Hanlim Lee; Yeonjin Jung; Junsung Park; Jung-Hun Woo; Jinseok Kim; et al. (Science of The Total Environment, 2025)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Reduction of viability, heat resistance, and biofilm formation and persistence of Bacillus cereus spores in beef stew broth by herb and spice extracts - Gyeong-Jong Kim; Young Hun Jin; Jae-Hyung Mah (Food Research International, 2025)

Bioprinting of cardiac patches with gold-nanowires and tri-culture system for the treatment of myocardial infarction - WonJin Kim; Jung Won Yoon; Woo-Sup Sim; Ye Seul Kim; SooJung Chae; Byungjoon Choi; Hun-Jun Park; Jae Ho Kim; GeunHyung Kim (Chemical Engineering Journal, 2025)

Visualization of two-phase mass transport using a prism-embedded operando cell in membrane-electrode assembly-based electrochemical devices - Ok-Hee Kim; Hyuckjae Choi; Junho Kim; Jongwon Yang; Cheunho Chu; Hosung Choi; Hee Ji Choi; WooKeon Yang; Tae-Ho Kim; Yong-Hun Cho; Ilchai La; Yung-Eun Sung (Chemical Engineering Journal, 2025)

Comparative study of the stability of composite cathodes based on sulfide solid electrolytes for all-solid-state lithium-ion batteries - Jae-Ho Park; Jiwon Jeong; Daseul Han; Jun Tae Kim; Hun-Gi Jung; Woo Young Yoon; Kyung-Wan Nam; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Locking of dendrites in potassium metal batteries: A potassiophilic 3D host discovered with machine learning screening - Jimin Park; Min-Gi Jeong; Muhammad Hilmy Alfaruqi; Muhamad Kurniawan; Shizhao Xiong; Shivam Kansara; Hyerim Kim; Hyeona Park; Jaekook Kim; Chan-Woo Lee; Hun-Gi Jung; Jang-Yeon Hwang (Chemical Engineering Journal, 2025)

Synergistic improvement of biohydrogen yield from food wastewater using Clostridium puniceum and magnetite-biochar - Jinok Oh; Yebin Han; Gaeun Lim; Shashi Kant Bhatia; Yun-Gon Kim; Sang-Ho Lee; Jae-Seok Kim; Yung-Hun Yang (Bioresource Technology, 2025)

Heat-killed Lactiplantibacillus plantarum WB3813 and Lactiplantibacillus plantarum WB3814 Alleviate LPS-Induced Inflammatory Damage and Apoptosis in A549 Cells - Ji-Yeon Baek; Ji Hun Kim; Na-Kyoung Lee; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2025)

Enhancing cell growth and EPA production in the marine microalga Pavlova lutheri via phytohormone treatment and LED light modulation - So Hee Kim; Ui Hun Lee; Sang Baek Lee; Gwi-Taek Jeong (Journal of Applied Phycology, 2025)

Sustainable lithium extraction from liquid ores using membrane-based technologies: a review - Ramesh Kumar; Kung-Won Choi; Moonis Ali Khan; Goutam Biswas; SoonHo Cho; Sankha Chakrabortty; Suraj K. Tripathy; Kyoung-Yeol Kim; Byong-Hun Jeon (Environmental Chemistry Letters, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Photoreceptors and Circadian Clock Regulators Control Growth and Flowering Under Ionizing Radiation Stress - Sung Won Cho; Wonbok Lee; Seung Sik Lee; Jeong-Il Kim; Young Hun Song (Journal of Plant Biology, 2025)
Plants have evolved mechanisms to optimize flowering time in response to adverse environments, ensuring reproductive success and survival. Although diverse regulatory networks controlling flowering have been identified, the molecular mechanisms by which environmental stresses influence flowering remain poorly understood. In particular, little is known about the impact of ionizing radiation (IR) such as γ-rays. Here, we show that photoreceptors and circadian clock components are crucial for growth and flowering regulation of Arabidopsis thaliana under IR stress. Exposure to 125 Gy of γ-radiation accelerated flowering in wild-type plants, primarily through elevated expression of the floral activator FT , rather than its upstream regulator CO . Plants lacking the blue-light photoreceptor FKF1 exhibited heightened sensitivity to IR. At the same time, the cry1 cry2 mutant, in which a different type of blue light photoreceptor is impaired, exhibited promotion of flowering by IR, although weaker than that observed in fkf1 . Unlike fkf1 and cry1 cry2 , the cry1 cry2 fkf1-2 mutant showed an IR-insensitive flowering phenotype. Similarly, the flowering time of ZTL mutant and overexpression plants was unaffected by IR. The cca1 lhy mutant lost IR-induced flowering promotion and accumulated high H 2 O 2 levels, implicating ROS regulation in IR-responsive flowering. Interestingly, the phyA-211 mutant exhibited extreme growth sensitivity, with severe retardation and anthocyanin accumulation. In contrast to phyA-211 , the phyB-9 mutant showed no significant differences in growth or anthocyanin accumulation compared with the wild type. These findings reveal distinct roles of photoreceptors and circadian clock regulators in coordinating flowering and growth under IR, providing insights into plant adaptation to radiation stress.

Regulation of Autonomic Motility in Human Gastric Muscle and the Gastroepiploic Artery by Stretch and pH - Dae Hoon Kim; Seung Myoung Son; Woong Choi; Chan Hyung Kim; Hun Sik Kim; Ki Bae Kim; Wen-Xie Xu; Sang Jin Lee; Young Chul Kim; Hyo-Yung Yun (Journal of Muscle Research and Cell Motility, 2025)

Application of multi-element isotopes for assessing sedimentary quality within aquaculture systems - Chung-Sook Kim; Young-Shin Go; Min-Seob Kim; Weol-Ae Lim; Dong-Hun Lee (Marine Environmental Research, 2025)

Impact of precipitation station density and homogeneous regions on hydrological modeling performance - Jung-Hun Song; Hakkwan Kim (Journal of Hydrology, 2025)

Intranasal nanophotosensitizer enables safe and broad-spectrum photodynamic inactivation of respiratory viruses - Sunmi Han; Assel Seitkazina; Jeongyun Heo; Se-young Kim; SuJin Kim; Sung-Ho Jeon; Yung Hun Park; Taehun Lim; Bohyeon Kim; Shivani Rajoriya; Quy Son Luu; Youngbok Lee; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Development of scalable precision fermentation and chemical-grade purification of 5-aminovaleric acid for high-value valorization - Yunhee Jeong; Younghoon Kim; Kyung-An Kim; Yu Jung Sohn; KwangYoung Park; Eunchae Song; Kyungmoon Park; See-Hyoung Park; Yung-Hun Yang; Jong Hyun Choi; Seojin Shin; Wangyun Won; et al. (Chemical Engineering Journal, 2025)

Infection protective biomimetic wearable strain sensor for laryngeal and articular movement monitoring inspired by epidermal protection and dermal motion detection - Dae Yang Oh; Mun Hwan Lee; Byung Ku Jung; Hyung Jin Choi; Taesung Park; Sang Yeop Lee; Young Kyun Choi; Yoonji Yang; Awais Ali; Seongkeun Oh; Junhyeok Park; Hanseok Seo; et al. (Chemical Engineering Journal, 2025)

Identification of candidate genes associated with resistance to Heterodera sojae in soybean - Heonil Kang; Jiyong Song; Hyoung-Rai Ko; Jae Eun Jo; Ji-Hun Hwang; Yeon-Ki Kim; Soo-Kwon Park; Gyu Tae Park; Tae-Hwan Jun; Bo-Keun Ha; Zenglu Li; Kyung Do Kim (Theoretical and Applied Genetics, 2025)

Analytical method for estimating dynamic earth pressure on basement walls considering building inertia and soil–structure interaction - Quang Thien Buu Nguyen; Byong-Youn Hwang; Tae-Hun Hwang; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2025)

New insights into the olfactory development disrupted by 4-tert-Octylphenol in offspring mice - Dong Hun Lee; Hyun Seung Shin; Yun Hee So; Seung Hyun Lee; Jin Yeop Kim; BuHyun Youn; Eun-Hee Lee; Eui-Man Jung (Journal of Hazardous Materials, 2025)

Preventive effects of fermented soy protein isolate with Limosilactobacillus fermentum on D-galactose-induced senile osteoporosis in rats via gut microbiome modulation - Jae Yeon Joung; Siyeon Shin; Sae Hun Kim (Food Bioscience, 2025)

Arsenic removal using foundry dust: Characterization, adsorption mechanisms, and application in acid mine drainage treatment - Hyunsoo Kim; Bum-jun Kim; Myoung-soo Ko; Oh-hun Kwon; Soonjae Lee; Nagchoul Choi; Kanghee Cho (Environmental Research, 2025)

Green solvent-based highly permeable PES membranes for virus filtration in bioprocesses - Chang-Hun Kim; Eunwoo Jung; In-Chul Kim; Mi-Hee Ryu; Jung-Hyun Lee; Youngbin Baek; Young Hoon Cho (Chemical Engineering Journal, 2025)

Heat-Killed Lactilactobacillus sakei WB2305 and Lactiplantibacillus plantarum WB2324 Inhibited LPS-Induced Inflammation in Human Airway Epithelial Cells - Ji Hun Kim; Cho Eun Kang; Na-Kyoung Lee; Hyun-Dong Paik (Probiotics and Antimicrobial Proteins, 2025)

Impacts of consecutive typhoons (Maysak and Haishen in 2020) on the benthic processes of a mega-tidal flat in highly developed area - Seong Woon Jeong; Hun Jun Ha; Hosang Kim; Beomgi Kim; Jong Seong Khim; Ho Kyung Ha (Marine Pollution Bulletin, 2025)

Asymmetric evolution of incised-valley deposits in response to sea-level changes since the Penultimate Glacial Maximum, southeastern Korea - Seok-Hwi Hong; Dong-Geun Yoo; Woo Hun Ryang; Jin Cheul Kim; Gwang-Soo Lee (Quaternary Science Reviews, 2025)

Lacuna-mimic human-derived nasal septal chondrocyte clusters encapsulated in click chemistry-based hydrogel for in vivo cartilage regeneration - Jung Ho Jeon; Seo Young Cheon; Sun Hwa Park; Hyunji Lee; Seung-Yeon Yoo; Min Young Ahn; Donghyun Lee; Man Soo Kim; Jeong Hun Park; Scott J. Hollister; Heebeom Koo; Sung Won Kim (Chemical Engineering Journal, 2025)

Synergistic interaction between Ni and K2CO3 on γ-Al2O3 for integrated direct CO2 capture and methanation under varying humidity conditions - Do Yeong Kim; Kyeong-Hun Ryu; Jihyeon Kang; Hui Won Choi; Haehyun Min; Young Jin Kim; Paul Worn Park; Sung Bong Kang (Chemical Engineering Journal, 2025)

Advanced catalytic support materials featuring polymeric short-side chains for PEM water electrolysis anodes - Jae-Hun Kim; Hye Jin Lee; Soo Youn Lee; Min Su Noh; Eun Jeong Shin; Hwi Jong Jung; Yuri Kim; Hee-Young Park; Hee Soo Kim; Jiye Lee; Eunjik Lee; Eunsung Kan; et al. (Chemical Engineering Journal, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

Exercise-Induced Hippocampal Neurogenesis Is Attenuated by Inhibition of Monocarboxylate Transporter 2 - Deunsol Hwang; Taeho Kim; Sunghwan Kyun; Inkwon Jang; Jisu Kim; Hun-Young Park; Sung-Woo Kim; Kiwon Lim (Molecular Neurobiology, 2025)

FDA-hydrolysis activity: A pre-screening tool for optimizing compost selection in standardized plastic biodegradation testing - Hyuni Jung; Sohyeon Park; Seul-A Park; Hyeri Kim; Minkyung Lee; Cheol Hun Park; Jonggeon Jegal; Giyoung Shin; Hyo Jeong Kim (Waste Management, 2025)

Age-specific associations between ambient temperature and hospitalizations or emergency department visits for intestinal infectious diseases in the Republic of Korea - Jisun Sung; Ho-Jang Kwon; Jong-Hun Kim (Urban Climate, 2025)

Ionomer-driven selectivity control in natural sunlight-powered CO₂ electrolysis using Ag electrodes in seawater - Sang Youn Chae; Jae Hong Kim; Jung Hun Maeng; Bohyeon Hwang; Gun Sik Yang; Minki Jun; Jin Young Kim; Eun Duck Park (Chemical Engineering Journal, 2025)

Fungal-bacterial interactions leading to increased insect mortality: Trichoderma xixiacum enhances the pathogenicity of Serratia marcescens in Protaetia brevitarsis larvae - Abdelaziz Mansour; Taeho Jeong; Duyoung Lee; Jeong-Hun Song; Eunsun Kim; Dae-Weon Lee; Mohamed Mannaa; Young-Su Seo (Journal of Invertebrate Pathology, 2025)

Genome-wide association mapping of scuticociliatosis resistance in a vaccinated population of olive flounder (Paralichthys olivaceus) - Yasara Kavindi Kodagoda; Gaeun Kim; D.S. Liyanage; W.K.M. Omeka; Cheonguk Park; Jeongeun Kim; Ji Hun Lee; H.A.C.R. Hanchapola; M.A.H. Dilshan; D.C.G. Rodrigo; David B. Jones; Cecile Massault; et al. (Fish & Shellfish Immunology, 2025)

Legacy and emerging persistent organic pollutants in sea turtles from Korean waters: Levels, profiles, and interspecies differences - Yelim Moon; Won Joon Shim; Sung Yong Ha; Gi Myung Han; Mi Jang; Il-Hun Kim; Hae-Rim Lee; Sang Hee Hong (Environmental Research, 2025)

Seasonal variation of groundwater quality and potential risks in U-bearing formations revealed from hydrogeological-microbiological investigation - Jaeyeon Kim; Ye Ji Kim; Suh-Ho Lee; Jiyoon Kim; Won-Tak Joun; Seung-Wook Ha; Sanghoon Lee; Ji-Hun Ryu; Sung-Wook Jeen; Kang-Kun Lee (Environmental Research, 2025)

Mechanically robust and recyclable CO2-derived poly(carbonate) vitrimers: The role of crosslinking density in mechanical and rheological properties - Jinhyun Hwang; Younghan Song; Hoesun Hwang; Suhnue Kim; Hyungsup Kim; Ki Wan Bong; Hyeonyeol Jeon; Cheol Hun Park; Jongbeom Na; Jin Young Seo (Chemical Engineering Journal, 2025)

A novel electro-sorption and acidic capturing method for continuous volatile fatty acid recovery - Kyoung-Yeol Kim; Jaegyu Shim; Moon Son; Kyung Hwa Cho; Byong-Hun Jeon (Chemical Engineering Journal, 2025)

Corneal Endothelium Regeneration with Decellularized Porcine Corneal Extracellular Matrix Scaffolds - Cha Yeon Kim; Cholong Jeong; Hun Lee; Changmo Hwang (Tissue Engineering and Regenerative Medicine, 2025)

Integrated source identification of particulate and dissolved organic matter related to anthropogenic activities in an artificial lake system - Seung-Hee Kim; Min-Seob Kim; Jin Hur; Dong-Hun Lee; Kyung-Hoon Shin (Marine Pollution Bulletin, 2025)

Optimization of an electrostatic spray system for control of particulate matter generated from electron beam flue gas treatment processes - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Hui-Bom Jeong; Seo Hee Seo; Tae-Hun Kim; Youn-Suk Son (Process Safety and Environmental Protection, 2025)

Thermochemical conversion of grape marc into carbon-negative syngas - Jung-Hun Kim; Taewoo Lee; Yiu Fai Tsang; Wei-Hsin Chen; Eilhann E. Kwon (Journal of Environmental Management, 2025)

Impact of the 2050 carbon-neutral emission scenario on air quality in South Korea - Hyungah Jin; Soyoung Yeo; Jung-Hun Woo; Minjoong J. Kim; Miae Seong; Do Hyun Seo; Jiwon Baek; Sang-Seok Oh; Cheol-Hee Kim (Journal of Environmental Management, 2025)

Comprehensive life cycle assessment of powder- vs. granule-form L-lysine production: Evaluating climate impact and sustainability - Danbee Park; Hyunwoo Kim; Sangmin Park; Jina Lee; Dong Hun Kwak; Kwang Soo Shin; Yongchan Lee; Hyaekyoung Kim; Jun-Woo Kim; Wangyun Won (Chemical Engineering Journal, 2025)

Assessment of hygrothermal performance of ply-lam CLT wall assemblies in a dry-winter humid continental climate region - Ji Hun Park; Yujin Kang; Seong Taek Kang; Sumin Kim (Building and Environment, 2025)

Evaluation of biohydrogen production potential in sludge by phospholipid fatty acid analysis of microbial communities - Jeong Hyeon Hwang; Suwon Kim; Yeda Lee; Yuni Shin; Suhye Choi; Jinok Oh; Sang-Hyoun Kim; Jeong-Hoon Park; Shashi Kant Bhatia; Yung-Hun Yang (Biomass and Bioenergy, 2025)

The role of tight junctions in the pathogenesis of inflammatory bowel disease: immune modulation and barrier dysfunction - Ji Woong Heo; Min Jung Kim; Ye Jin Yang; Han Nim Choi; Kwang Youn Kim; Tae Woo Oh; Ju-Hye Yang; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Prevalence and virulence profiles of ESBL-producing Escherichia coli in urinary and blood infections in South Korea - Jong-Hun Ha; Jeong-Ih Shin; Kyu-Min Kim; Jeong-Gyu Choi; Minh Phuong Trinh; Won Jun Anh; Kyung-Min Kang; Hyung-Lyun Kang; Jung-Hyun Byun; Wongwarut Boonyanugomol; Kee Woong Kwon; Myung Hwan Jung; et al. (Folia Microbiologica, 2025)

Effect of soil-structure interaction on seismic earth pressure acting on building basements using 1g shaking table tests - Byong-Youn Hwang; Nghiem Xuan Tran; Tae-Hun Hwang; Seongho Hong; Quang Thien Buu Nguyen; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2025)

Exposure risk assessment through toxicodynamics assessment of 4-tert-octylphenol and estimation of new reference values based on human tissue toxicity - Dae-Han Park; Ji-Hun Jang; Jong-Jin Kim; Seung-Hyun Jeong (Environmental Pollution, 2025)

Functional microbiota reconstruction using acclimatized consortium and trace metal supplementation facilitates process recovery in organic-overloaded anaerobic digesters - Bikram Basak; Rahul S. Tanpure; Hyun-Jo Ahn; Yongtae Ahn; Kung-Won Choi; Min Jang; Jung Rae Kim; Sang-Un Oh; Byong-Hun Jeon (Chemical Engineering Journal, 2025)

Rational electrode design for balanced and enhanced ionic and electronic conduction in high-loading all-solid-state batteries - Yunho Lee; Jaecheol Choi; Seok Hun Kang; Young-Gi Lee; Joonwon Lim; Hyeong Min Jin; Ju Young Kim (Chemical Engineering Journal, 2025)

Rational design strategy of co-self-assembled monolayers for high-efficiency and stable inverted perovskite solar cells - Haoran Zhou; Jung Jae Do; Young Hun Jung; Hoon Kang; Soyeon Kwon; Gyung Hyun Kim; Yekyung Kim; Tae Hoon Park; Eun Joong Kim; Chang Woo Byun; Jang Hyuk Kwon; Sungyeop Jung; et al. (Chemical Engineering Journal, 2025)

Multi-index-dependent decellularization processes for scalable tissue-specific bioink production - Hye Jin Kim; Ikbum Park; Yoo-mi Choi; Hwanyong Choi; Seong Hun Jeong; Jungbin Yoon; Daekeun Kim; Bo Ram Lee; Jinah Jang (Chemical Engineering Journal, 2025)

Fundamental modeling of microbial electrosynthesis system using porous electrodes for CO2-to-acetate conversion - Minji Kim; Jiin Yoo; Minsoo Kim; Ji Hun Kim; Yonghyun Lee; Huiwon Lee; Hyoung-il Kim; Jungho Jae; Jung Rae Kim; Sang Hwan Son (Bioresource Technology, 2025)

Synergistic effects of synoptic and quasi-biweekly timescale atmospheric circulation patterns on PM2.5 concentration in South Korea - Seyeong Lee; Jeong-Hun Kim; Maeng-Ki Kim; Sang-Hyun Lee; Cheol-Hee Kim (Atmospheric Environment, 2025)

Classification and Key Factors for the Snowfall over the Eastern Part of the Korean Peninsula - Byeong-Hun Hwang; Soojin Yoo; Eun-Chul Chang; Francisco J. Tapiador; Kwonil Kim; GyuWon Lee (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Correction: Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Innovative electrostatic spray technology for control of particulate matter emitted from electron beam flue gas treatment process - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Hui-Bom Jeong; Seo Hee Seo; Tae-Hun Kim; Youn-Suk Son (Process Safety and Environmental Protection, 2025)

Efficient NOx and SO2 removal using NaOH additive in electron beam flue gas treatment process - Yong-Hwan Oh; Sang-Hee Jo; Jieun Son; Tak-Hyun Kim; Tae-Hun Kim; Youn-Suk Son (Journal of Environmental Chemical Engineering, 2025)

Bioremediation of reactive blue 19 dye by laccase-producing Serratia marcescens AY4 strain - Ghulam Mustafa; Ammara Younas; Muhammad Tariq Zahid; Deok-Won Kim; Ihtisham Jamil; Nikita Yadav; Mayur B. Kurade; Shouvik Saha; Karishna Kumar Yadav; Byong-Hun Jeon (Journal of Environmental Chemical Engineering, 2025)

Inhibitory effects of garlic, cinnamon, and rosemary on viability, heat resistance, and biofilm formation of Bacillus cereus spores in the broth of a fermented soybean paste stew, Cheonggukjang jjigae - Sohyeon Kim; Young Hun Jin; Jae-Hyung Mah (Food Research International, 2025)

Effects of dietary mineral level and creep feed provision on lactating sows during heat stress - Sang Hun Ha; Min Ju Kim; Jun Young Mun; Abdolreza Hosseindoust; Tajudeen Habeeb Temitope; So Dam Choi; Seon Ah Park; Priscilla Neves Silvestre; Sang Sik Lee; Jin Soo Kim (Tropical Animal Health and Production, 2025)

Efficacy of Human-Induced Pluripotent Stem Cell-Derived Neural Progenitor Cell Replacement Therapy in a Vascular Dementia Animal Model - Jang Hun Kim; Ho-Young Kang; Jihun Lee; Jong-Hoon Kim; Dongho Geum; Dong-Hyuk Park (Tissue Engineering and Regenerative Medicine, 2025)
Background Cell replacement therapy is the only treatment that restores or repairs the function of impaired tissues in neurodegenerative diseases, including vascular dementia (VaD); however, current VaD treatments focus on slowing or mitigating the underlying small vessel disease progression. We aimed to verify the improvement in neurocognition after administering human-induced pluripotent stem cell (hiPSC)-derived neural progenitor cells (NPCs) from in a VaD animal model. Methods After anesthesia, 10–12-week-old male C5BL/6 mice underwent sham or bilateral carotid artery stenosis (BCAS) surgeries. For BCAS, 0.18-mm micro-coils were wound around the bilateral common carotid arteries to induce chronic vascular insufficiency in the global brain. One day after surgery, the mice were administered phosphate buffer solution or NPC from hiPSCs via the tail vein for 15 d, and divided into sham (n = 6), VEH (n = 6), and NPC (n = 7) groups. Three months after the surgery, neurobehavioral tests including the Y-maze test (YMT), passive avoidance test (PAT), and novel object recognition test (NORT) were performed. Finally, mice brains were sectioned for evaluating microglia (Iba-1), astrocyte (GFAP) activation, and myelin (MBP) degeneration through immunohistochemistry (IHC). Results PAT latency ( p = 0.01) and discrimination index in the NORT ( p = 0.043) increased considerably in the NPC group than in the VEH group. However, alterations in YMT were not considerably higher in the NPC group than in the VEH group ( p = 0.65). IHC tests revealed that the GFAP- and IBA-1-positive cell number was remarkably lower in the NPC group than in the VEH group ( p < 0.05). Moreover, MBP density was higher in the NPC group. Conclusion hiPSC-derived NPCs have therapeutic potential in cerebral hypoperfusion VaD mice; it improves the working memory of VaD animals by diminishing inflammatory reactions and protecting them from demyelination.

Temporospatial expression of neurogranin in the rat molar development - Jung-Sun Moon; Dong-Wook Yang; Dong-Hoo Kim; Jee-Hae Kang; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2025)

The Roles of MYC2 Transcription Factor in JA-Signaling Pathway in Plants - Young-Hun Kim; Chan-Woo Park; Kwang Min Lee; Chang-Oh Hong; Hong-Joo Son; Keun Ki Kim; Hyeon Cheal Park; Yu-Jin Kim (Journal of Plant Biology, 2025)

Correction to: Development of a lateral flow immunochromatographic assay for the detection of Lactococcus garvieae in grey mullet (Mugil cephalus) - Choon-Sup Kim; Sung-Hun Lee; Myoung Sug Kim; Kyoung-Hui Kong; Hwi-Jin Kim; Gee-Wook Shin; Wi-Sik Kim (Aquaculture International, 2025)

Influence of temperature on growth and reproduction of keystone species, Crangon hakodatei (Caridea, Crangonidae) in the East Sea of Korea - In Ok Lee; Hyeong-Gi Kim; Junsung Noh; Jong Hun Na; Chul-Woong Oh; Jong Seong Khim (Marine Pollution Bulletin, 2025)

Expression profiling and functional role of cyclooxygenase-2 in the immune and inflammatory responses of red-spotted grouper (Epinephelus akaara) - Yasara Kavindi Kodagoda; H.A.C.R. Hanchapola; D.C.G. Rodrigo; Chaehyun Lim; D.S. Liyanage; W.K.M. Omeka; G.A.N.P. Ganepola; M.A.H. Dilshan; Jeongeun Kim; Ji Hun Lee; Taehyug Jeong; Qiang Wan; et al. (Fish & Shellfish Immunology, 2025)

Biofilm comes back: Controlling regrowth by mitigating the cell-matrix interaction - Yu-Heng Deng; Joo Hun Lee; Myung-Joo Kim; Hyunjoon Kong (Chemical Engineering Journal, 2025)

Combined Treatment of Metformin and Resveratrol Promotes Myogenesis Through Increased Irisin Release in C2C12 Cells - Eun Ji Seong; Yejin Kim; Zheng-Yuan Su; Hee-Taik Kang; Jong Hun Lee (Pharmaceutical Research, 2025)

Ecological risk assessment of p-toluidine in freshwater, sediment, and soil media - Inhye Lee; Daeyeop Lee; Hun-Je Jo; Hyun Soo Kim; Kyung Sook Woo; Kyunghee Ji (Ecotoxicology, 2025)

Single-cell nanoencapsulation enables fabrication of probiotics-loaded hydrogel dressing with improved wound healing efficacy in vivo - Jung Suk Kim; Beom Jin Kim; Sang Min Lee; Insung S. Choi; Ji Hun Park; Han-Gon Choi; Sung Giu Jin (Journal of Pharmaceutical Investigation, 2025)

Stiffness evaluation of semi-rigid connection using steel clamps in plastic greenhouse structure - Sangik Lee; Jong-hyuk Lee; Byung-hun Seo; Dong-su Kim; Dongwoo Kim; Yerim Jo; Won Choi (Biosystems Engineering, 2025)

Water and gas geochemistry of springs in Ulleungdo volcano, South Korea: Implications for degassing of upper mantle-derived volatiles in Northeast Asia - Wonhee Lee; Hyunwoo Lee; Heejun Kim; Jung-Hun Song; Jungpyo Hong; Jonghoon Park; Hyejung Jung; Jeonghoon Lee; Naoto Takahata; Yuji Sano; Tobias P. Fischer (Journal of Hydrology, 2025)

Applicability of plant–clay mineral composite for rapid algae removal from eutrophic freshwaters at the laboratory and field scales - Byeong-Hun Han; Hyo Gyeom Kim; Young-Hyo Kim; In-Hwan Cho; Ha-Kyung Kim; Sungwon Hong; Baik-Ho Kim (Environmental Research, 2025)

Effects of long-term treatment with low concentration butylparaben on prostate organoids - Yujin Hwang; Yejin Kim; Dongkyu Choi; Jong Hun Lee (Environmental Pollution, 2025)

CO2-intensified dry reforming of methane over oxygen-defective Ni-CeO2 catalysts: Synergistic coupling with reverse water-gas shift reaction - Beom-Jun Kim; Ho-Ryong Park; Su-Jin Ryu; Byong-Hun Jeon; Hyun-Seog Roh (Chemical Engineering Journal, 2025)

Demonstrating the use of absolute pressure sensors for monitoring stack-driven pressure differences in high-rise buildings - Jiajun Jing; Sungmin Yoon; Jaewan Joe; Eui-Jong Kim; Young-Hum Cho; Jae-Hun Jo (Building and Environment, 2025)

Assessment of feeding grounds for loggerhead and green turtles in Korean water through stranding and bycatch data - Il-Kook Park; Daesik Park; Il-Hun Kim (Biological Conservation, 2025)

Impact of administration routes and dose frequency on the toxicology of SARS-CoV-2 mRNA vaccines in mice model - Jae-Hun Ahn; Jisun Lee; Gahyun Roh; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Kang-Min Han; Ji-Eun Kim; Hyo-Jung Park; Soyeon Yoo; Sung Pil Kwon; Eun-Kyoung Bang; et al. (Archives of Toxicology, 2025)
The increasing use of SARS-CoV-2 mRNA vaccines has raised concerns about their potential toxicological effects, necessitating further investigation to ensure their safety. To address this issue, we aimed to evaluate the toxicological effects of SARS-CoV-2 mRNA vaccine candidates formulated with four different types of lipid nanoparticles in ICR mice, focusing on repeated doses and administration routes. We conducted an extensive analysis in which mice received the mRNA vaccine candidates intramuscularly (50 μg/head) twice at 2-week intervals, followed by necropsy at 2 and 14 dpsi (days post-secondary injection). In addition, we performed a repeated dose toxicity test involving three, four, or five doses and compared the toxicological outcomes between intravenous and intramuscular routes. Our findings revealed that all vaccine candidates significantly induced SARS-CoV-2 spike protein-specific IgG and T cell responses. However, at 2 dpsi, there was a notable temporary decrease in lymphocyte and reticulocyte counts, anemia-related parameters, and significant increases in cardiac damage markers, troponin-I and NT-proBNP. Histopathological analysis revealed severe inflammation and necrosis at the injection site, decreased erythroid cells in bone marrow, cortical atrophy of the thymus, and increased spleen cellularity. While most toxicological changes observed at 2 dpsi had resolved by 14 dpsi, spleen enlargement and injection site damage persisted. Furthermore, repeated doses led to the accumulation of toxicity, and different administration routes resulted in distinct toxicological phenotypes. These findings highlight the potential toxicological risks associated with mRNA vaccines, emphasizing the necessity to carefully consider administration routes and dosage regimens in vaccine safety evaluations, particularly given the presence of bone marrow and immune organ toxicity, which, though eventually reversible, remains a serious concern.

Development of a lateral flow immunochromatographic assay for the detection of Lactococcus garvieae in grey mullet (Mugil cephalus) - Choon-Sup Kim; Sung‑Hun Lee; Myoung Sug Kim; Kyoung-Hui Kong; Hwi-Jin Kim; Gee-Wook Shin; Wi-Sik Kim (Aquaculture International, 2025)

The Complete Mitochondrial Genome of the Korean Endemic Polychaete Phyllodoce koreana (Lee & Jae, 1985) from Jindong Bay, Korea, with Additional Morphological and Ecological Features - Dae-Hun Kim; So Jin Ryu; Jong Rae Kim; Seong-il Eyun; Man-Ki Jeong (Journal of Marine Science and Engineering, 2025)
Phyllodoce koreana was first described in 1985 in Gwangyang Bay, a semi-enclosed bay in Korea affected by significant organic input from the Seomjin River and dredging activities near the Gwangyang Port. Since then, this Korean endemic species has received limited attention in taxonomic and ecological studies. Phyllodoce koreana is known for its resilience to mild disturbances but is vulnerable to severe environmental changes. In this study, P. koreana specimens were collected from organically polluted Asian stalked tunicate aquaculture farms at eight sites in Jindong Bay, a location with environmental conditions similar to those of Gwangyang Bay, over the course of five sampling events from March to November. Both bays experience benthic hypoxia in summer due to elevated water temperatures and organic matter accumulation. Phyllodocid specimens were primarily collected in March and November 2023, non-hypoxic periods, suggesting potential seasonal adaptations to environmental fluctuations. The morphological features of the collected specimens were consistent with the original description of P. koreana, confirming their identification. Additionally, we reported previously overlooked morphological details, contributing to a more comprehensive taxonomic understanding of the species. We also present, for the first time, the complete mitochondrial genome of this species, comprising 15,559 bp, which provides essential genetic data for future taxonomic and phylogenetic studies. The phylogenetic analysis of protein-coding genes shows that, among 17 related polychaete species, P. koreana (family Phyllodocidae) is closely related to the family Goniadidae. Future research should expand our knowledge of polychaete taxonomy by integrating additional mitochondrial genomes and investigating the role of conserved gene synteny within Polychaeta.

Role of factors controlling diurnal variation of cold-season formaldehyde during Satellite Integrated Joint Monitoring of Air Quality 2021 campaign - Lim-Seok Chang; Soi Ahn; Min-Suk Bae; Seung-Myung Park; Junsu Gil; Kwang-Rae Kim; Gangwoong Lee; Taehyoung Lee; Jung-Hun Woo; Rokjin Park; Hyeong-Ahn Kwon; Gyo-Hwang Choo; et al. (Science of The Total Environment, 2025)

Limosilactobacillus fermentum MF10 promotes hair growth through upregulation of Wnt/β-catenin signaling in C57BL/6 mice - Jae-Young Kim; Sejin Jang; Seokyoung An; Sae Hun Kim (Food Bioscience, 2025)

Highly activated phosphate-derived oxyhydroxide overlayer for enhancing photoelectrochemical ammonia oxidation-boosted hydrogen evolution - Phuong Thi Pham; Jong Hun Kim; Won Tae Hong; Hyungu Han; Seung Hun Roh; Xu Yu; Heeyeop Chae; Jongwook Park; Min-Cheol Kim; Chang Hyuck Choi; Jung Kyu Kim (Chemical Engineering Journal, 2025)

Symmetric and asymmetric non-fullerene acceptors cooperate synergistically for ternary optoelectronic devices - Minyoung Lim; Xiaoling Ma; Yelim Kang; Min Hun Jee; Soonyong Lee; Sang Young Jeong; Tae Hyuk Kim; Jae Won Shim; Fujun Zhang; Han Young Woo (Chemical Engineering Journal, 2025)

Active metal cation exchanged in ZSM-5 for enhanced direct air capture of CO2 - Do Yeong Kim; Kyeong-Hun Ryu; Wo Bin Bae; Haehyun Min; Sungjoon Kweon; Min Bum Park; Dohyung Kang; Young Jin Kim; Sung Bong Kang (Chemical Engineering Journal, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Thermochemical processing for the sustainable disposal of spent filter waste - Taewoo Lee; Jung-Hun Kim; Jaewon Lee; Eilhann E. Kwon (Chemosphere, 2024)

Apportioning sources of natural and anthropogenic organic matter in sediment from Lake Shihwa: An integrated approach using molecular ratios and compound-specific stable-isotope analysis - Rincheon Jeon; Seung-Hee Kim; Dong-Hun Lee; Yusang Cho; Youngnam Kim; Seongjin Hong; Kyung-Hoon Shin (Marine Pollution Bulletin, 2024)

Development of a 6-degrees-of-freedom measurement system using a robotic total station for a free-running model test - Dong-Han Kim; Kunhang Yun; Si-Woong Choi; Jung-Hyeon Kim; Chan-Young Yeo; Hui-Hun Son; Do-Kyun Kim; Jong-Yong Park (Ocean Engineering, 2024)

Corrigendum to: “Association between ambient temperature and thyroid-stimulating hormone and free thyroxine levels in Korean euthyroid adults” [Environ. Res. Volume 262, Part 2, 1 December 2024, Article Number 119918] - Jisun Sung; Jong-Hun Kim (Environmental Research, 2024)

Association between ambient temperature and thyroid-stimulating hormone and free thyroxine levels in Korean euthyroid adults - Jisun Sung; Jong-Hun Kim (Environmental Research, 2024)

Inter-annual changes in transboundary air quality from KORUS-AQ 2016 to SIJAQ 2022 campaign periods and assessment of emission reduction strategies in Northeast Asia - Min-Jun Park; Seung-Hee Baek; Hyo-Jung Lee; Hyun-Young Jo; Cheol-Hee Kim; Jin-Seok Kim; Jung-Hun Woo; Rokjin Park; Jong-Jae Lee; Chang-Keun Song; Jung-Woo Yoo; Lim-Seok Chang; et al. (Environmental Pollution, 2024)

Optimizing active chilled beam systems in the South Korean Climate: Comparative analysis of cooling energy and thermal comfort by set-point temperature - Jun Kyu Park; Sang Hun Yeon; Chul Ho Kim; Yeobeom Yoon; Jin Woo Moon; Kwang Ho Lee (Energy and Buildings, 2024)

Enhancing the methodology for calculating emission reductions in air quality policies - Bomi Kim; Hyejung Hu; Youjung Jang; Junhee Park; Minwoo Park; Jinseok Kim; Younha Kim; Seung Jick Yoo; Jung-Hun Woo (Atmospheric Pollution Research, 2024)

Discriminative characteristics of hydrochemical components and sedimentary organic matter in Korean coastal aquaculture systems during summer - Seung-Hee Kim; Sung-Eun Park; Chung-Sook Kim; Dong-Hun Lee (Frontiers in Marine Science, 2024)
Understanding the spatial distribution and sources of sedimentary organic matter (OM) in coastal environments is crucial for effective water quality management and the preservation of ecosystem health. Although extensive research has been conducted on OM dynamics, there remains a gap in understanding the ongoing biogeochemical processes in Korean coastal aquaculture zones, particularly during the summer season. To address this gap, we investigated the spatial variation of water chemical properties and isotopic composition of sedimentary OM to trace the composition, source, and reactivity of mixed OM in aquaculture systems along the Korean coast during the summer season. The isotopic approach was applied to surface sediments from five sections: western (W)-1, W-2, southern (S)-1, S-2, and eastern (E)-1. With respect to increased nutrients (mainly nitrate; 1.2 ± 0.6 mg/L) by dam-water discharge near W sections, our isotopic signatures revealed that a substantial fraction of sedimentary OM might dominantly originated from autochthonous OM source (algae; 36.5%) related to the increase of terrestrial nutrients. Simultaneously, the deposition of allochthonous OM (aquacultural feces; 44%) was predominant in the S-2 sections. The 34 S-depleted patterns (approximately -7.2‰) in the S-2 section was indicative of active sulfate reduction occurring at the sedimentary boundary. Therefore, together with the precise determination of ongoing OM, our isotopic results provide valuable insights for effectively managing water-sedimentary qualities under the increase of anthropogenic contamination.

Effect of soil-building interaction on dynamic earth pressure on basement walls - Quang Thien Buu Nguyen; Byong-Youn Hwang; Tae-Hun Hwang; Sung-Ryul Kim (Soil Dynamics and Earthquake Engineering, 2024)

Hydrogen-bonded QSEBS/ZrO2 mixed matrix anion exchange membranes for water electrolyzer - Ji Eun Kim; Young Hwa Yun; Hyeonjung Park; Justin Albers; Gisu Doo; Sechan Lee; Jongsu Seo; Changsoo Lee; MinJoong Kim; Hyun-Seok Cho; Sang-Kyung Kim; Jae Hun Lee; et al. (Fuel, 2024)

Nanometer-scale tunable mesopores in silica fillers for facile enhancement of epoxy adhesion - Chae Yeon Lee; Min Jeong Kim; Sun Hwan Jeong; Dai-Hwan Kim; Jennifer Kezia Soegijopranoto; Hui Hun Cho; Jun Hyuk Heo; Jung Heon Lee (Chemical Engineering Journal, 2024)

Prediction of total organic acids concentration based on FOS/TAC titration in continuous anaerobic digester fed with food waste using a deep neural network model - Soyoung Park; Gi-Beom Kim; Ashutosh Kumar Pandey; Jong-Hun Park; Sang-Hyoun Kim (Biomass and Bioenergy, 2024)

Removal of livestock odor gas ammonia, hydrogen sulfide, methanethiol by electron beam in a continuous flow system - Dong-Woo Kim; Sang-Hee Jo; Jieun Son; Seungho Yu; Tae-Hun Kim; Meehye Lee; Tak-Hyun Kim (Journal of Environmental Chemical Engineering, 2024)

Prediction of food materials for the management of respiratory symptoms targeting PDE4B and NMDAR via machine learning approach - Jihyeon Jung; Seo Hyun Shin; Jong Hun Kim; Jung Han Yoon Park; Ki Won Lee (Food Bioscience, 2024)

Sustainable use of historic campus buildings: Retrofit technology to improve building energy performance considering preservation of interior finishing material - Won Duk Suh; Hyeonseong Yuk; Ji Hun Park; Ho Hyeon Jo; Sumin Kim (Energy and Buildings, 2024)

Innovative construction of amine-functionalized lignin-based hydrogel for ultrafast and selective dye remediation - Ji Won Heo; Min Soo Kim; Do Hun Oh; Yong Sik Kim (Chemical Engineering Journal, 2024)

Advancement of biocrude valorization to fuels: A comprehensive review - Jung-Hun Kim; Minyoung Kim; Gyeongnam Park; Jee Young Kim; Jechan Lee; Eilhann E. Kwon (Chemical Engineering Journal, 2024)

Enhancing flood wave modelling of reservoir failure: a comparative study of structure-from-motion based 2D and 3D methodologies - Jong-hyuk Lee; Sang-ik Lee; Youngjoon Jeong; Byung-hun Seo; Dong-su Kim; Ye-jin Seo; Younggu Her; Won Choi (Natural Hazards, 2024)
Predicting flood wave propagation from reservoir failures is critical to practical flood hazard assessment and risk management. Flood waves are sensitive to topography, channel geometry, structures, and natural features along floodplain paths. Thus, the accuracy of flood wave modelling depends on how precisely those features are represented. This study introduces an enhancing approach to flood wave modelling by accurately representing three-dimensional objects in floodplains using the structure-from-motion (SfM). This method uses an unmanned aerial vehicle to capture topographic complexities and account for ground objects that impact flood propagation. Using the three-dimensional volume of fluid numerical approach significantly improves an enhanced representation of turbulent flow dynamics and computational efficiency, especially in handling large topography datasets. Reproductions from this enhanced three-dimensional approach were validated against recent reservoir failure observations and contrasted with traditional two-dimensional models. The results revealed that the suggested three-dimensional methodology achieved a significant 84.4% reproducibility when juxtaposed with actual inundation traces. It was 35.5%p more accurate than the two-dimensional diffusion wave equation (DWE) and 17.1%p more than the shallow water equation (SWE) methods in predicting flood waves. This suggests that the reproducibility of the DWE and SWE decreases compared to the three-dimensional approach when considering more complex floodplains. These results demonstrate that three-dimensional flood wave analysis with the SfM methodology is optimal for effectively minimising topographic and flood wave reproduction errors across extensive areas. This dual reduction in errors significantly enhances the reliability of flood hazard assessments and improves risk management by providing more precise and realistic predictions of flood waves.

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

Dual suppressive effect of p-coumaric acid on pigmentation in B16F10 cells - Sohee Jang; Chang-Woo Ha; Sung-Hyeok Kim; Jung Hun Choi; Seung Namkoong; Sungsil Hong; Hyun Jung Koo; Youn-Kyu Kim; Mediana Hadiwidjaja; Sung Ryul Lee; Eun-Hwa Sohn (Molecular & Cellular Toxicology, 2024)

Functional use of carbon dioxide for the sustainable valorization of orange peel in the pyrolysis process - Jung-Hun Kim; Taewoo Lee; Yiu Fai Tsang; Deok Hyun Moon; Jechan Lee; Eilhann E. Kwon (Science of The Total Environment, 2024)

Fabrication of granular three-dimensional graphene oxide/UiO-66 adsorbent for high uranium adsorption: Density functional theory and fixed bed column studies - Choe Earn Choong; Yoon-Young Chang; Jae-kyu Yang; Jung Rae Kim; Sang-Eun Oh; Yeomin Yoon; Byong-Hun Jeon; Eun Ha Choi; Min Jang (Journal of Hazardous Materials, 2024)

Conversion of toxic pyrogenic products into syngas through catalytic pyrolysis of insulation material waste under the presence of CO2 - Jung-Hun Kim; Taewoo Lee; Jaewon Lee; Hyeseung Choi; Eilhann E. Kwon (Journal of Hazardous Materials, 2024)

A new integrated framework to fault detection and diagnosis of air handling unit: Emphasizing the impact of symptoms - Jae Hwan Cha; Jun Kyu Park; Chang Hyeon Chi; Sang Hun Yeon; Chul Ho Kim; Jin Woo Moon; Kwang Ho Lee (Energy and Buildings, 2024)

Single atom catalyst induced by redox reaction between iron ion and aniline monomer - Yeongeun Choi; T.B. Ngoc Huynh; Seungmin Lee; Jongmin Lee; Yung-Eun Sung; Hyukjae Choi; Yong-Hun Cho; Seunghoe Koo; Kyeongtae Kim; Oh Joong Kwon (Chemical Engineering Journal, 2024)

Functional cellulose interfacial layer on zinc metal for enhanced reversibility in aqueous zinc ion batteries - Van-Chuong Ho; Hai Yen Nguyen Thi; Thi Huong Pham; Hun-Gi Jung; Jung Ho Kim; Jeong F Kim; Junyoung Mun (Chemical Engineering Journal, 2024)

Metabolite analysis of 14C-labeled chloromethylisothiazolinone/methylisothiazolinone for toxicological consideration of inhaled isothiazolinone biocides in lungs - Jung Eun Park; Seung-Hun Ryu; Satoshi Ito; Hyunil Shin; Young-Hee Kim; Jongho Jeon (Chemosphere, 2024)

Enhanced oxidation of parabens in an aqueous solution by air-assisted cold plasma - Hee-Jun Kim; Tae-Hun Lee; Youngpyo Hong; Jae-Cheol Lee; Hyun-Woo Kim (Chemosphere, 2024)

Efficient two-way fluid–structure interaction simulation for performance prediction of pressure-compensating emitter - Byung-hun Seo; Sangik Lee; Jong-hyuk Lee; Dong-su Kim; Ye-jin Seo; Dong-woo Kim; Won Choi (Biosystems Engineering, 2024)

Exploring green solvents for the sustainable fabrication of bio-based polylactic acid membranes using nonsolvent-induced phase separation - Tunmise Ayode Otitoju; Chang-Hun Kim; Mihee Ryu; Jaesung Park; Tae-Kyung Kim; Youngmin Yoo; Hosik Park; Jung-Hyun Lee; Young Hoon Cho (Journal of Cleaner Production, 2024)

Valorization of battery manufacturing wastewater: Recovery of high-value metal ions through reaction-enhanced membrane cascade - Jeong Han Shin; Seung Hwan Kim; Cheol Hun Yoo; Ho Jun Lee; Bao Tran Duy Nguyen; Go Gi Lee; Jeong F. Kim; Jong Suk Lee (Chemical Engineering Journal, 2024)

Animal-free scaffold from brown algae provides a three-dimensional cell growth and differentiation environment for steak-like cultivated meat - Heejae Lee; Dasom Kim; Kyeong Hun Choi; Sangmin Lee; Minguk Jo; Song-Yi Chun; Yebin Son; Jong Ha Lee; Kwanhyeong Kim; TaeByung Lee; Joonho Keum; Min Yoon; et al. (Food Hydrocolloids, 2024)

Improvement of 1,3-propanediol production from glycerol using formate as an intermediary metabolite for NADH regeneration in Klebsiella oxytoca - Eun Joo Park; Minsoo Kim; Da Seul Kong; Eunseo Kim; Won Gyeong Park; Jungho Jae; Min Jang; Byong-Hun Jeon; Jung Rae Kim (Biomass and Bioenergy, 2024)

Investigating the impact of control strategies on the sulfur dioxide emissions of South Korean industrial facilities using an aircraft mass balance approach - Gracie Wong; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; Beom-Keun Seo; et al. (Atmospheric Environment, 2024)

Efficacy and Safety Evaluation of Tacrolimus-Eluting Stent in a Porcine Coronary Artery Model - Dae Sung Park; Mi Hyang Na; Myung Ho Jeong; Doo Sun Sim; Yu Jeong Jin; Hae Jin Kee; Mun Ki Kim; Jeong Ha Kim; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Association between sickness presenteeism and depressive symptoms: a cross-sectional study using the 6th Korean working conditions survey - Myeong-Hun Lim; Min-Seok Kim; Seong-Uk Baek; Tae-Yeon Kim; Jong-Uk Won; Jin-Ha Yoon (International Archives of Occupational and Environmental Health, 2024)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

In silico identification and expression analysis of superoxide dismutases in Tenebrio molitor - Ho Am Jang; Hyeonjun Shin; Seo Jin Lee; Sung Min Ku; Jae Hui Kim; Dong Woo Kang; So Yeon Choi; Sang Mok Jung; Hyun Woung Shin; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Hydrophobicity and membrane distillation performance of glass fiber membranes modified by dip coating of pure PDMS - Minsu Pyo; Sanghyun Jeong; Jae Hun Kim; Min Jung Jeon; Eui-Jong Lee (Journal of Environmental Chemical Engineering, 2024)

Psychological distances to climate change and public preferences for biodiversity-augmenting attributes in family-owned production forests - Do-hun Kim; Hanne K. Sjølie; Francisco X. Aguilar (Forest Policy and Economics, 2024)

A sustainable bioprocessing system leveraging gas fermentation and bipolar membrane electrodialysis system for direct recovery of acetic acid - Mungyu Lee; Jae-Hun Kim; Muhammad Yasin; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2024)

Algal biomass-based zero-waste biorefinery for producing optically pure (R)-γ-valerolactone and carbonaceous electrodes applicable for energy storage devices - Jaehyun Cha; Chang-Hun Lim; Jeongmi Lee; Jin-Kyu Lim; Minyoung Kim; Won-Kun Park; Changmin Sung; Hyun-Kyung Kim; Kyoungseon Min (Chemical Engineering Journal, 2024)

Photo-crosslinking and layer-by-layer processed organic photodetectors with remarkably suppressed dark current - Min Hun Jee; Byoungwook Park; Ah Young Lee; Seunghyun Rhee; Minyoung Lim; Jung Min Ha; Nayoung Kim; Fujun Zhang; Jong‐Woon Ha; Hyungju Ahn; Jong H. Kim; Mijeong Han; et al. (Chemical Engineering Journal, 2024)

Impact of typhoons on anthropogenic nitrogen sources in Lake Sihwa, South Korea - Seung-Hee Kim; Min-Seob Kim; Dong-Hun Lee; Kyung-Hoon Shin (Marine Pollution Bulletin, 2024)

Improvement of the anthropogenic emission rate estimate in Ulaanbaatar, Mongolia, for 2020–21 winter - Hyung-Min Lee; Eunlak Choi; Yong Pyo Kim; Tseren-Ochir Soyol-Erdene; Amgalan Natsagdorj; Zhijun Wu; Mijung Song; Changhyuk Kim; Kyoung-Soon Jang; Junyoung Ahn; Atsushi Matsuki; Esmatullah Torabi; et al. (Environmental Pollution, 2024)

Design of a flow channel with vortex generators for performance improvement of flow-electrode capacitive mixing under low pressure drop conditions - Hwabhin Kwon; Donghyun Kim; Dong Gyeong Kim; Hyeryang Choi; Jeong Geun Park; Jung-Hun Son; Ehtesham Ali; Heesung Park; SeungCheol Yang (Desalination, 2024)

Selective in-situ water removal by polybenzoxazole hollow fiber membrane for enhanced CO2 methanation - Eun-Young Kim; Myeong-Hun Hyeon; Hyun Wook Hwang; Ji Young Lee; Seok Ki Kim; Youn-Sang Bae; Su-Young Moon (Chemical Engineering Journal, 2024)

In silico identification and expression analyses of peroxidases in Tenebrio molitor - Ho Am Jang; Sung Min Ku; Jae Hui Kim; Sang Mok Jung; Jongdae Lee; Yong Seok Lee; Yeon Soo Han; Yong Hun Jo (Genes & Genomics, 2024)

Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Su In Kim; Jun Young Seo; Jae-Hun Park; Pyeong Joong Kim; In Gwon Kim; Kyung Man Kim; Ho Kyung Ha (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominantly seaward due to tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry between flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.

Adsorption effects of electron scavengers and inorganic ions on catalysts for catalytic oxidation of sulfamethoxazole in radiation treatment - Kang Lee; Tae-Hun Kim; Sang-Hee Jo; Seungho Yu (Chemosphere, 2024)

North Korean CO emissions reconstruction using DMZ ground observations, TROPOMI space-borne data, and the CMAQ air quality model - Eunhye Kim; Byeong-Uk Kim; Hyun Cheol Kim; Yang Liu; Yoon Hee Kang; Daniel J. Jacob; Yong Pyo Kim; Jung-Hun Woo; Jhoon Kim; Shuxiao Wang; Chul Yoo; Changhan Bae; et al. (Science of The Total Environment, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Ultrasound-assisted sustainable recycling of valuable metals from spent Li-ion batteries via optimisation using response surface methodology - Theoneste Nshizirungu; Masud Rana; Young Tae Jo; Eugenie Uwiragiye; Jaepil Kim; Jeong-Hun Park (Journal of Environmental Chemical Engineering, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Maximizing light olefin production via one-pot catalytic cracking of crude waste plastic pyrolysis oil - Xuan Tin Tran; Dae Hun Mun; Jiho Shin; Na Young Kang; Dae Sung Park; Yong-Ki Park; Jungkyu Choi; Do Kyoung Kim (Fuel, 2024)

Evaluation of acute, 28-day, 13-week repeated dose oral toxicity and genotoxicity of a herbal extract (HemoHIM G) from Angelica sinensis, Ligusticum chuanxiong, and Peaonia lactiflora - Su-Bin Bak; Hansol Choi; Gyoung-Deuck Kim; Ju Gyeong Kim; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2024)
HemoHIM G is a functional food ingredient composed of a triple herbal combination of Angelica sinensis , Ligusticum chuanxiong , and Paeonia lactiflora , to improve impaired immune function. Considering the pharmacological benefits of its constituent herbal components, HemoHIM G is anticipated to have various health benefits; however, its toxicity has not been thoroughly evaluated. Here, we conducted a comprehensive study to assess the safety of HemoHIM G in terms of acute oral toxicity, 13-week repeat-dose toxicity, and genotoxicity. In the oral acute toxicity study, Sprague–Dawley rats were orally administered a single dose of HemoHIM G at 5000 mg/kg/day, the limit dose for the acute study. No abnormal findings or adverse effects were observed in this study, as confirmed by gross pathology. A 13-week repeated-dose toxicity study was conducted with HemoHIM G at doses of 1250, 2500, and 5000 mg/kg/day to examine the subchronic toxicity in both male and female rats after 28 days of dose-range finding study. No test substance-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology were within normal ranges, further supporting the safety of HemoHIM G. Therefore, the NOAEL of HemoHIM G was considered to be at 5000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronuclei test were conducted to identify the potential genotoxicity of HemoHIM G. HemoHIM G is non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence for the safe use of HemoHIM G as a functional food ingredient.

Regulatory role of N-myc downregulated genes in amelogenesis in rats - Dong-Wook Yang; Jee-Hae Kang; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2024)

Pharmacological effects of pentacyclic triterpenoids isolated from Centella asiatica - Dong-Hyun Min; Young-Beom Yu; Tae-Hun Kim; Hoon Kim; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2024)
Centella asiatica (CA) is one of the most popular traditional herbal medicines worldwide. It has been used for centuries in many countries, especially for curing skin damage, and is now applied to treat various human diseases. There are various types of triterpenoids from Centella asiatica , with four pentacyclic triterpenoids with the main properties being shown by four pentacyclic triterpenoids: asiaticoside, madecassoside, asiatic acid, and madecassic acid. These terpenoids have similar structures, however each has a slightly different properties. Asiaticoside, madecassoside, asiatic acid, and madecassic acid are synthesized through the isoprenoid pathway known as mevalonate pathway to produce hydrophobic triterpenoid structures (aglycone) which contain hydrophilic sugar chains (glycone). Furthermore, asiaticoside and madecassoside are distinguished by a glycone, and asiatic acid and madecassic acid are distinguished by a aglycone. These pentacyclic triterpenoids have a wide spectrum of beneficial effects and have been used as anti-inflammatories, skin wound treatments, scar treatments, and cosmetics agents. This review aimed to provide a description of the four compounds, of their structure, pharmacological properties, applications in the treatment of various diseases, known mechanisms of action, and commentary on industrial applications.

Overview of the population genetics and connectivity of sea turtles in the East Asia Region and their conservation implications - Connie Ka Yan Ng; Takashi Ishihara; Tomoko Hamabata; Hideaki Nishizawa; Min Liu; Jia-hao Song; Tsung Hsien Li; Chia-Ling Fong; Dae Yeon Moon; Il Hun Kim (Frontiers in Marine Science, 2024)
Understanding the current status and recent development of the population genetics and connectivity of sea turtles is crucial for effective conservation management of the species. Five sea turtle species, green turtle ( Chelonia mydas ), loggerhead turtle ( Caretta caretta ), hawksbill turtle ( Eretmochelys imbricata ), olive ridley turtle ( Lepidochelys olivacea ) and leatherback turtle ( Dermochelys coriacea ), are recorded in the East Asia Region situated in the western side of the North Pacific Ocean. We compiled information from 35 published genetic studies on the five sea turtle species, with a focus on green turtle and loggerhead turtle, which are the most studied species (in 30 studies) in view of their commonness and occurrence of nesting populations. We provided an overview of the key methods and findings of these previous studies, addressing two main objectives on genetic structure of the rookeries and their differences compared to other populations, and connectivity of the rookeries and foraging aggregations. By identifying information gaps and conservation needs, we discussed future developments for sea turtle genetic studies and conservation implications in the region.

Corrigendum to “Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea” [Sci. Total Environ. vol. 912, 169204] - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

Arctic/North Atlantic atmospheric variability causes Severe PM10 events in South Korea - Jeong-Hun Kim; Maeng-Ki Kim; Seong-Joong Kim; Joo-Hong Kim; Sang-Wook Yeh; Sang-Hyun Lee; Youngseok Lee (Science of The Total Environment, 2024)

Urinary metabolite biomarkers of pregnancy complications associated with maternal exposure to particulate matter - Sunwha Park; Minki Shim; Gain Lee; Young-Ah You; Soo Min Kim; Young Min Hur; Hyejin Ko; Mi Hye Park; Sung Hun Na; Young-Han Kim; Geum Joon Cho; Jin-Gon Bae; et al. (Reproductive Toxicology, 2024)

Seasonal and geographical variations in the community structure of environmentally-transmitted symbiotic bacteria in Riptortus pedestris (Hemiptera: Alydidae) - Joo-Young Kim; Do-Hun Gook; Minhyung Jung; Doo-Hyung Lee (Journal of Asia-Pacific Entomology, 2024)

Wearable ion gel based pressure sensor with high sensitivity and ultra-wide sensing range for human motion detection - Ji Eun Hyun; Taehwan Lim; Seong Hun Kim; Joo Hyung Lee (Chemical Engineering Journal, 2024)

Positive effect of phasin in biohydrogen production of non polyhydroxybutyrate-producing Clostridium acetobutylicum ATCC 824 - Jeong Hyeon Hwang; Hyun Joong Kim; Suwon Kim; Yeda Lee; Yuni Shin; Suhye Choi; Jinok Oh; Sang-Hyoun Kim; Jeong-Hoon Park; Shashi Kant Bhatia; Yun-Gon Kim; Kyoung-Soon Jang; et al. (Bioresource Technology, 2024)

Estimating three-dimensional current fields in the Yeosu Bay using coastal acoustic tomography system - Yerin Hwang; Eun-Joo Lee; Hajin Song; Byoung-Nam Kim; Ho Kyung Ha; Yohan Choi; Jae-Il Kwon; Jae-Hun Park (Frontiers in Marine Science, 2024)
Observation of current speeds in coastal seas is crucial because it can provide useful information for ship operations, fishing activities, and rapid responses to marine disasters. Coastal acoustic tomography (CAT) is a technology that can continuously monitor environmental changes such as current velocity and water temperature using reciprocal acoustic signals between CAT stations in coastal seas. This technology is different from traditional pointwise or intermittent sectional observations in that it can produce time-varying two- or three-dimensional current fields. The results of previous studies using CAT systems have been limited to reproducing horizontal maps of depth-averaged two-dimensional current fields. Utilizing results from a high-resolution coastal ocean model, this study developed a novel technique for estimating three-dimensional (3-D) current fields by combining the inverse method with an artificial intelligence (AI) model. Following three steps are the procedure for the test of estimating the 3-D current fields. First, utilizing the ray tracing model ‘Bellhop,’ reciprocal travel times among five CAT stations using the coastal ocean model outputs are computed. These five stations correspond to the locations where in-situ CAT systems were established for continuous monitoring of current changes in Yeosu Bay, Korea. Subsequently, the range-averaged currents at the five layers were estimated by incorporating this travel time difference data into an AI model trained using the same coastal ocean model outputs. Finally, the inverse method is applied to each layer to estimate the 3-D current fields. The validation results revealed that the newly developed method performed well in both summer and winter. Time-varying two-layer-like current fields were reasonably produced, occasionally revealing an out-of-phase relationship between the upper and lower layers depending on the tidal phases. This method yielded average root-mean-squared errors of less than 4 cm/s on six simulation paths for acoustic signal propagation. Furthermore, when the same method was applied to in-situ CAT observations, the average correlation coefficient (R) of the along-channel current of each layer was found to be approximately 0.9 or higher. These results suggest that this novel method can be effectively applied to the continuous monitoring of 3-D current fields in coastal seas using a CAT system.

Enhancing polyethylene terephthalate conversion through efficient microwave-assisted deep eutectic solvent-catalyzed glycolysis - Geon-Soo Ha; Md Al Mamunur Rashid; Jeong-Myeong Ha; Chun-Jae Yoo; Byong-Hun Jeon; Keunhong Jeong; Kwang Ho Kim (Chemosphere, 2024)

Integrating experimental and computational approaches for deep eutectic solvent-catalyzed glycolysis of post-consumer polyethylene terephthalate - Geon-Soo Ha; Md Al Mamunur Rashid; Da Hae Oh; Jeong-Myeong Ha; Chun-Jae Yoo; Byong-Hun Jeon; Bonwook Koo; Keunhong Jeong; Kwang Ho Kim (Waste Management, 2024)

Ellagic acid treatment during in vitro maturation of porcine oocytes improves development competence after parthenogenetic activation and somatic cell nuclear transfer - Han-Bi Lee; Seung-Eun Lee; Min-Jee Park; Dong-Hun Han; Eun-Seo Lim; Bokyeong Ryu; Eun-Young Kim; Se-Pill Park (Theriogenology, 2024)

Optimizing an airborne mass-balance methodology for accurate emission rate quantification of industrial facilities: A case study of industrial facilities in South Korea - Gracie Wong; Hui Wang; Minwoo Park; Jinsoo Park; Joon-Young Ahn; Minyoung Sung; Jinsoo Choi; Taehyun Park; Jihee Ban; Seokwon Kang; Taehyoung Lee; Jongho Kim; et al. (Science of The Total Environment, 2024)

Unveiling microplastics with hyperspectral Raman imaging: From macroscale observations to real-world applications - Wooseok Sim; Si Won Song; Subeen Park; Jin Il Jang; Jae Hun Kim; Yeo-Myoung Cho; Hyung Min Kim (Journal of Hazardous Materials, 2024)

Degradation of micropollutants by gamma irradiation: Insight of transformation product formation explored by suspect and non-target screening using LC-HRMS - Heewon Jang; Tae-Hun Kim; Junho Jeon (Journal of Environmental Chemical Engineering, 2024)

Acid-site control of ZSM-5 zeolites using quaternary ammonium hydroxides for shale gas dehydroaromatization - Yangho Jeong; Yong Hyun Lim; Eun Ji Choi; Hae Won Ryu; Jangeon Roh; Susung Lee; Minkee Choi; Do Heui Kim; Jong Hun Kang (Chemical Engineering Journal, 2024)

Correlation between the particle size of Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte and lithium-ion transport in composite cathodes for all-solid-state lithium-ion batteries - Jae-Ho Park; Mingony Kim; Min-Young Kim; Jiwon Jeong; Hun-Gi Jung; Woo Young Yoon; Kyung Yoon Chung (Chemical Engineering Journal, 2024)

Atelocollagen Scaffold Enhances Cartilage Regeneration in Osteochondral Defects: A Study in Rabbits - Ji-Chul Yoo; Man Soo Kim; Sueen Sohn; Sang Hun Woo; Yu Ri Choi; Andrew S. Kwak; Dong Shin Lee (Tissue Engineering and Regenerative Medicine, 2024)

Correction: Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)

Predicting rapid intensification of tropical cyclones in the western North Pacific: a machine learning and net energy gain rate approach - Sung-Hun Kim; Woojeong Lee; Hyoun-Woo Kang; Sok Kuh Kang (Frontiers in Marine Science, 2024)
In this study, a machine learning (ML)-based Tropical Cyclones (TCs) Rapid Intensification (RI) prediction model has been developed by using the Net Energy Gain Rate Index ( NGR ). This index realistically captures the energy exchanges between the ocean and the atmosphere during the intensification of TCs. It does so by incorporating the thermal conditions of the upper ocean and using an accurate parameterization for sea surface roughness. To evaluate the effectiveness of NGR in enhancing prediction accuracy, five distinct ML algorithms were utilized: Decision Tree, Logistic Regression, Support Vector Machine, K-Nearest Neighbors, and Feed-forward Neural Network. Two sets of experiments were performed for each algorithm. The first set used only traditional predictors, while the second set incorporated NGR . The outcomes revealed that models trained with the inclusion of NGR exhibited superior performance compared to those that only used traditional predictors. Additionally, an ensemble model was developed by utilizing a hard-voting method, combining the predictions of all five individual algorithms. This ensemble approach showed a noteworthy improvement of approximately 10% in the skill score of RI prediction when NGR was included. The findings of this study emphasize the potential of NGR in refining TC intensity prediction and underline the effectiveness of ensemble ML models in RI event detection.

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Development of a duplex qPCR assay for the detection of coinfection in eels by Japanese eel endothelial cell-infecting virus and Anguillid herpesvirus-1 - Hyoun Joong Kim; S.D.N.K. Bathige; Hyung-Bae Jeon; Seung-Hyeon Kim; Chen Yu; Woonchul Kang; Kangrae Noh; Eunil Lee; Byeong Seong Lim; Dong Hun Shin (Aquaculture, 2024)

Development of surface observation-based two-step emissions adjustment and its application on CO, NOx, and SO2 emissions in China and South Korea - Eunhye Kim; Hyun Cheol Kim; Byeong-Uk Kim; Jung-Hun Woo; Yang Liu; Soontae Kim (Science of The Total Environment, 2024)

Remote impacts of low-latitude oceanic climate on coastal upwelling in a marginal sea of the Northwestern Pacific - Seongho Lee; Jeong-Yeob Chae; Jae-Hun Park; Young Taeg Kim; Boonsoon Kang; Chang-Woong Shin; Ho Kyung Ha (Regional Studies in Marine Science, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

Modified toxic potential of multi-walled carbon nanotubes to zebrafish (Danio rerio) following a two-year incubation in water - Youn-Joo Jung; Thillaichidambaram Muneeswaran; Jin Soo Choi; Sumin Kim; Jong Hun Han; Wan-Seob Cho; June-Woo Park (Journal of Hazardous Materials, 2024)

Field evaluation of carbon injection method for in-situ biological denitrification in groundwater using geochemical and metataxonomic analyses - Yongtae Ahn; Sanghyun Park; Hoo Hugo Kim; Bikram Basak; Seong-Taek Yun; Byong-Hun Jeon; Jaeyoung Choi (Environmental Pollution, 2024)

Rapid and facile preparation of freestanding dense polymer membranes from high-boiling-point solvents for anion exchange membrane water electrolyzers - Du Ru Kang; Gi Hyo Sim; So Youn Lee; Jae Hun Lee; Ki Chul Kim; Jong Hak Kim (Chemical Engineering Journal, 2024)

A stress-adaptive interlinked 3D network binder for silicon anodes via tailored chemical bonds and conformation of functionalized poly(vinylidene fluoride) (PVDF) terpolymers - Young Je Kwon; Ji-Oh Kim; E. Vivek; Eunji Kim; Se Hun Kim; Taekyun Kwon; Eunyoung Lim; Seongwook Chae; Minjoon Park; Youngho Eom; Ji-Hoon Baik; Jin Hong Lee; et al. (Chemical Engineering Journal, 2024)

Assessing the impact of climate and air quality policies on future emissions in Korea through quantification of control and co-control effects - Youjung Jang; Hyejung Hu; Bomi Kim; Younha Kim; Seung-Jick Yoo; Kyungae Jang; Yoon-Kwan Kim; Hyungah Jin; Jung-Hun Woo (Atmospheric Pollution Research, 2024)

Improvement and Analysis for Accuracy of Baseflow Using SWAT-CUP Premium in the Yongjeon Stream, South Korea - Jong-Tae Kim; Chang-Hun Lee; Namjoo Lee (Pure and Applied Geophysics, 2024)
Here, the results of Soil and Water Assessment Tool (SWAT) simulation are calibrated and validated using SWAT-CUP Premium, and the R 2 (coefficient of determination) values of simulated and observed flows are compared. According to the SWAT analysis of the Cheongsong Yongjeon stream basin, low accuracy of 0.40 was the R 2 value for simulated and observed flows, and the baseflow was calculated at an annual average of 46.659 m 3 /s. During the same period, after calibration and validation using SWAT-CUP Premium, the R 2 value of simulated and observed flows was improved to 0.71, and the evaluation indexes showed 0.51 for Nash–Sutcliffe efficiency (NS), 37.1 for percent bias (PBIAS), 0.73 for P-factor, and 0.33 for R-factor, indicating that the relationship between observed and simulated flows was improved. In addition, after calibration and validation, the baseflow was 56.951 m 3 /s, which was a more accurate value than the one before calibration and validation.

Water-rock interactions of uranium deposits: A field investigation and laboratory batch experiment - Hakyung Cho; Jaeyeon Kim; Seong-Sun Lee; Kang-Kun Lee; Jaeguk Jo; Dongbok Shin; Ji-Hun Ryu; Sung-Wook Jeen (Applied Geochemistry, 2024)

Novel rearrangements in the mitochondrial genomes of the Ceramiales (Rhodophyta) and evolutionary implications - Min Ho Seo; Shin Chan Kang; Kyeong Mi Kim; Min Seok Kwak; Jihoon Jo; Han-Gu Choi; Ga Hun Boo; Hwan Su Yoon (Algae, 2023)
The Ceramiales is the most diverse and species-rich group (2,669 spp.) of red algae, and it is widely distributed from tropical to polar oceans. Mitochondrial genomes (mitogenomes) and other genes have contributed to our knowledge regarding the classification and phylogeny of this diverse red algal group; however, the mitogenome architecture remains understudied. Here, we compared 42 mitogenomes, including 19 newly generated in this study, to expand our knowledge. The number of genes in mitogenome varied from 43 to 68 due to gene duplication. The mitogenome architecture was also variable, categorized into four types (A–D): type A = ancestral type with a basic composition; type B = those with inverse transpositions; type C = those with inverted duplications; and type D = those with both inversion and duplication. T﻿he palindromic and inverted repeats were consistently found in flanking regions of the rearrangement, especially near the cob and nad6 genes. The three rearranged mitogenome architectures (types B, C, D) are the first report of these in red algae. Phylogenetic analyses of 23 protein-coding genes supported the current familial classification of the Ceramiales, implying that the diversity of mitogenome architecture preceded the phylogenetic relationships. Our study suggests that palindromic and inverted repeats may drive mitogenome architectural variation.

Micro-grinding–based production for sulforaphene-enriched radish seeds extract via facilitating glucosinolates-myrosinase reaction, and evaluation of its anti-adipogenic effects - Tae Kyung Lee; Gihyun Hur; Jong Hun Kim; Jung Han Yoon Park; Hee Yang; Ki Won Lee (Food Chemistry, 2023)

Tuning cyclopropanecarboxaldehyde clathrate hydrates for enhancement of methane storage - Ki Hun Park; Dong Hyun Kim; Ji-Ho Yoon; Minjun Cha (Chemical Engineering Journal, 2023)

Screening for Lactic Acid Bacterial Strains as Probiotics Exhibiting Anti-inflammatory and Antioxidative Characteristic Via Immune Modulation in HaCaT Cell - Min Jae Shin; Chul Sang Lee; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2023)

Comparison of photosynthetic efficiency and growth characteristics of paprika in semi-closed vs. conventional greenhouses - Eun ji Kim; Beom Seon Lee; Yong Hwan Jeon; Se Hun Ju; Yoon Go; Jin Sub Park; Joonwoo Lee; Huijun Yang; Haeyoung Na (Horticulture, Environment, and Biotechnology, 2023)

Personal exposure of PM2.5 and metabolic syndrome markers of pregnant women in South Korea: APPO study - Yeonseong Jeong; Sunwha Park; Eunjin Kwon; Young Min Hur; Young-Ah You; Soo Min Kim; Gain Lee; Kyung A. Lee; Soo Jung Kim; Geum Joon Cho; Min-Jeong Oh; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2023)
We examined the association between exposure to PM 2.5 , focused on individual exposure level, and metabolic dysfunction during pregnancy. APPO study (Air Pollution on Pregnancy Outcome) was a prospective, multicenter, observational cohort study conducted from January 2021 to March 2023. Individual PM 2.5 concentrations were calculated using a time-weighted average model. Metabolic dysfunction during pregnancy was assessed based on a modified definition of metabolic syndrome and its components, accounting for pregnancy-specific criteria. Exposure to PM 2.5 during pregnancy was associated with worsened metabolic parameters especially glucose metabolism. In comparison to participants exposed to the low PM 2.5 group, those exposed to high PM 2.5 levels exhibited increased odds of gestational diabetes mellitus (GDM) after adjusting for confounding variables in different adjusted models. Specifically, in model 1, the adjusted odds ratio (aOR) was 3.117 with a 95% confidence interval (CI) of 1.234–7.870; in model 2, the aOR was 3.855 with a 95% CI of 1.255–11.844; in model 3, the aOR was 3.404 with a 95% CI of 1.206–9.607; and in model 4, the aOR was 2.741 with a 95% CI of 0.712–10.547. Exposure to higher levels of PM 2.5 during pregnancy was associated with a tendency to worsen metabolic dysfunction markers specifically in glucose homeostasis. Further research is needed to investigate the mechanisms underlying the effects of ambient PM 2.5 on metabolic dysfunction during pregnancy.

Investigating the Mesh Size Selectivity of Olive Flounder (Paralichthys olivaceus) Gillnets for Fisheries Resource Management in the East Sea - Hyun-Ji Yu; Young Il Seo; Jae-Hyeong Yang; Jeong-Ik Baek; Seong hun Kim (Fishes, 2023)
This study aimed to evaluate the mesh selectivity of gillnets used in olive flounder (Paralichthys olivaceus) fishing by examining the distribution of total length (TL) across various mesh sizes. A marine fishing experiment was conducted at Gajin Harbor in Goseong County, Gangwon Province, employing experimental gear with four different mesh sizes: 90, 105, 135, and 150 mm. Mesh selectivity analysis involved a comparative assessment of selectivity curve methods through normal, log-normal, and bi-normal functions. Among these, the bi-normal function demonstrated the best fit for estimating the mesh selectivity curve within the SELECT model. The critical finding was the net size at which 50% of the minimum landing size (35 cm in TL) of olive flounder was selected, ranging from 108.7 to 121.1 mm. According to the bi-normal function curve, this size was estimated as 114.0 mm. Our findings indicate that using a mesh size larger than the theoretically estimated size in mesh selectivity analysis can further decrease the catch of immature individuals. These findings provide essential data for devising strategies to efficiently utilize and manage olive flounder resources.

Biofloc Application Using Aquaponics and Vertical Aquaculture Technology in Aquaculture: Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Sung Won Han; Song-Hun Han; Hee Jae Choi; Cheol Young Choi; Ju-Chan Kang; EunYoung Min; Jun-Hwan Kim (Fishes, 2023)
Some aspects of traditional aquaculture have negative impacts on the aquatic environment, leading to pollution and disease outbreaks in farmed organisms. Biofloc technology (BFT) is a closed aquaculture system that utilizes specific microbial communities to remove ammonia emitted from aquaculture organisms or adds carbon to the aquaculture system to improve water quality. BFT has benefits, such as increasing production and improving water quality, and reducing disease spread and pollution, without the need for water exchange. However, there are disadvantages, such as rapid changes in water quality due to accumulation of dissolved nutrients and total suspended soils (TSS) and the requirement for expensive aeration equipment to maintain dissolved oxygen. BFT can be enhanced in value and efficiency by combining it with other aquaculture technologies, such as aquaponics and vertical aquaculture to overcome the disadvantages. The integration of biofloc with technologies from the fourth industrial revolution holds potential for further development, while aquaponics and vertical farming can eliminate geographical limitations and accelerate the urbanization of aquaculture. The integration of aquaponics and vertical aquaculture with BFT has potential for development, accelerating the urbanization of aquaculture and removing geographic limitations.

Otolith morphology as a tool for stock discrimination of three rockfish species in the East Sea of Korea - Joo Myun Park; Min Gu Kang; Jong Hun Kim; Laith A. Jawad; Samroz Majeed (Frontiers in Marine Science, 2023)
The shape and structure of otoliths play a vital role in studying fish populations because otolith shape indices are often applied to discriminate fish species. This study focused on examining inter- and intra-specific variations in otolith shape and size among three species of rockfish ( Sebastes inermis , Sebastiscus marmoratus , and Sebastes zonatus ) collected from the Dokdo and Ulleungdo regions of the East Sea in Korea. A total of 35 S. inermis specimens, 19 S. marmoratus specimens, and 59 S. zonatus specimens were collected between April 2021 and August 2022. The otolith shape was visualized using wavelet coefficients in the shapeR package. Otolith size indices, such as length, width, perimeter, and area, and shape indices, including form factor, aspect ratio, ellipticity, circularity, roundness, rectangularity, and squareness, were calculated for each species. Otolith size and shape indices significantly differed among the three rockfish species (p< 0.05). Compared with the other two species, S. marmoratus possessed more elongated otoliths, whereas S. zonatus had the largest otolith area, perimeter, and length. Average shape analysis based on wavelet coefficients revealed significant differences in otolith shape, particularly on the rostrum and posterior sides. A canonical analysis of principal components (CAP) confirmed the complete separation of otolith shapes among the three rockfish species, with 92.5% of the variation explained by the first axis (CAP1). The findings of this study enhance our understanding of the fish species in the Korean East Sea.

Benthic sediment disturbances by episodic human-controlled discharge in an altered estuary - Seong Woon Jeong; Hun Jun Ha; Kyung Man Kim; Ho Kyung Ha (Marine Geology, 2023)

Biogenic amine reduction by vasoactive amine-degrading Bacillus licheniformis CH7P22 in Enterococcus faecium-contaminated Cheonggukjang, Korean fermented soybean paste - Dabin Kim; Young Hun Jin; Jae-Hyung Mah (Food Control, 2023)

Extremely high selective Si1−xGex-film wet etchant generating highly dissolved oxygen via peracetic acid oxidant for lateral gate-all-around FETs with a logic node of less than 3-nm - Seung-Jae Lee; Ji-Eun Lee; Chang-Jin Lee; Ji-Hoon Kim; Ji-Hun Kim; Min-Won Kim; Ji-Ho Choi; Ui-Hyun Jeong; Jea-Gun Park (Chemical Engineering Journal, 2023)

Review of technology and materials for the development of cultured meat - Da Young Lee; Seung Yun Lee; Jae Won Jung; Jae Hyun Kim; Dong Hun Oh; Hyun Woo Kim; Ji Hyeop Kang; Jung Seok Choi; Gap-Don Kim; Seon-Tea Joo; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2023)

Bioaccumulation and in vivo fate of toxic benzylalkyldimethylammonium chloride in rats via the radiotracer analysis - Jung Eun Park; Seung-Hun Ryu; Satoshi Ito; Mi-Kyung Song; Eun Ji Gu; Hyunil Shin; Young-Hee Kim; Jongho Jeon (Chemosphere, 2023)

Real-time morphological detection of label-free submicron-sized plastics using flow-channeled differential interference contrast microscopy - Jiyun Han; Subeen Park; Mingizem Gashaw Seid; Byeongho Park; Soo Hyun Lee; Hyung Min Kim; Changha Lee; Jaesang Lee; Jae Hun Kim; Seok Won Hong (Journal of Hazardous Materials, 2023)

Efficient chemo-catalytic transformation of spent coffee grounds into lactic acid using erbium triflate - Geon-Soo Ha; Ho Seung Song; Da Hae Oh; Mark Mba-Wright; Jeong-Myeong Ha; Chun-Jae Yoo; Jae-Wook Choi; Chang Soo Kim; Byong-Hun Jeon; Hanseob Jeong; Kwang Ho Kim (Journal of Environmental Chemical Engineering, 2023)

Vibration detection of stay-cable from low-quality CCTV images using deep-learning-based dehazing and semantic segmentation algorithms - Hun Lee; Hyungchul Yoon; Sunjoong Kim (Engineering Structures, 2023)

Development and performance evaluation of novel silica gel-coated heat exchanger with high durability and conductivity to improve adsorption water treatment - Seong-Yong Woo; Kyung-Hun Kim; Jun-Sik Kim; Young-Deuk Kim (Desalination, 2023)

Antioxidant-Coated multifunctional whitlockite scaffold for the treatment of Steroid-Induced osteonecrosis of the femoral head - Jung Hun Kim; QuanZhe Liu; Uk-Jae Lee; Arun Kumar Rajendran; MinJoon Cho; Sivashanmugam Amirthalingam; Tae Hoon Kang; Beom Seok Kim; Gyeong-Guk Park; Byung-Gee Kim; Jae Hyup Lee; Nathaniel S. Hwang (Chemical Engineering Journal, 2023)

Biological characterization of mulberry leaves bioconverted with Viscozyme L - Young Wook Kim; Sun Nyoung Yu; Kwang Youn Kim; Sang Hun Kim; Bo Bae Park; Hyun Cheol Oh; Dong Seob Kim; Kwang Il Park; Soon Cheol Ahn (Molecular & Cellular Toxicology, 2023)

A novel membrane-integrated sustainable technology for downstream recovery of molybdenum from industrial wastewater - Ramesh Kumar; Chengjia Liu; Geon-Soo Ha; Kwang Ho Kim; Sankha Chakrabortty; Suraj K. Tripathy; Young-Kwon Park; Moonis Ali Khan; Krishna Kumar Yadav; Marina M.S. Cabral-Pinto; Byong-Hun Jeon (Resources, Conservation and Recycling, 2023)

Internal carbon loop strategy for methanol production from natural gas: Multi-objective optimization and process evaluation - Sung-Jong Jo; Tae-Ha Kang; Beom-Ju Shin; Ji-Hun Mun; Sijan Devkota; Jin-Young Cha; Shaukat Ali Mazari; Kyung-Min Kim; Ung Lee; Chae-Ho Shin; Jong-Ho Moon (Journal of Cleaner Production, 2023)

Evaluating the phototactic behavior responses of the diamondback moth, Plutella xylostella, to some different wavelength LED lights in laboratory and field - Chol-Nam Yun; Il-Song Maeng; Son-Hui Yang; Un-Jo Hwang; Kil-Nam Kim; Kyong-Chol Kim; Kum-Chol Ho; Chung-Song Ri; Hyon-Son Yang; Song-Hun Jang (Journal of Asia-Pacific Entomology, 2023)

Intensified intrusion and retention of saltwater in the Sumjin River Estuary, South Korea - Hoi Soo Jung; Dhongil Lim; Ji Hun Kim; Jun-Ho Lee; Joo Bong Jeong; Han Jun Woo (Estuarine, Coastal and Shelf Science, 2023)

The production of debrominated aromatics via the catalytic pyrolysis of flexible printed circuit boards - Sumin Pyo; Avnish Kumar; Moonis Ali Khan; Byong-Hun Jeon; Siyoung Q. Choi; Young-Min Kim; Young-Kwon Park (Chemical Engineering Journal, 2023)

Macroalgae as a source of sugar and detoxifier biochar for polyhydroxyalkanoates production by Halomonas sp. YLGW01 under the unsterile condition - Shashi Kant Bhatia; Jeong Hyeon Hwang; Suk Jin Oh; Hyun Jin Kim; Nara Shin; Tae-Rim Choi; Hyun-Joong Kim; Jong-Min Jeon; Jeong-Jun Yoon; Yung-Hun Yang (Bioresource Technology, 2023)

Frequency Shift Keying-Based Long-Range Underwater Communication for Consecutive Channel Estimation and Compensation Using Chirp Waveform Symbol Signals - Jongmin Ahn; Dong-Hun Lee; Sangkug Lee; Wanjin Kim (Journal of Marine Science and Engineering, 2023)
Currently, the demand for long-range underwater communication (UWC) is increasing. Conventional long-range UWC studies utilize vertical line array (VLA) and equalization techniques such as TRM and DFE to mitigate the long multi-path delay. However, recently developed underwater platforms such as unmanned underwater vehicles (UUVs) utilize a single hydrophone, and it is hard to apply the conventional long-range UWC system to these platforms. This paper proposes frequency shifting-based modulation to overcome the large multi-path delay without any optimization or training symbol. Unlike FSK, the proposed modulation method transmits the data using linear frequency modulation (LFM). The proposed demodulation method estimates the multi-path delay using data-modulated LFM and utilizes the estimated multi-path to compensate for the subsequent data signal. Therefore, the proposed method has better BER performance than FSK, and it is demonstrated through a simulation and ocean experiment with a single hydrophone.

Enhanced oxidation of urea by pH swing during chlorination: pH-dependent reaction mechanism - Ji Won Lee; Donghyun Lee; Hye-Jin Lee; Soojin Shim; Je Hun Kim; Changha Lee (Water Research, 2023)

Droplet digital PCR method for the absolute quantitative detection and monitoring of Lacticaseibacillus casei - Eiseul Kim; Seung-Min Yang; Changs Hun Choi; Min-Ki Shin; Hae-Yeong Kim (Food Microbiology, 2023)

A versatile hybrid catalyst platform of Na/ZnFe2O4 and zeolite for selective hydrocarbon production from CO2 hydrogenation - Eun Cheol Ra; Sejin Jang; Dong Gun Oh; Ju Hyeong Lee; Hyo Eun Kim; Eun Hyup Kim; Kwang Young Kim; Min Hee Lee; Kwang Hyun Kim; Ja Hun Kwak; Jae Sung Lee (Chemical Engineering Journal, 2023)

Sustainable recovery of high-valued resources from spent lithium-ion batteries: A review of the membrane-integrated hybrid approach - Ramesh Kumar; Sankha Chakrabortty; Prasenjit Chakrabortty; Jayato Nayak; Chengjia Liu; Moonis Ali Khan; Geon-Soo Ha; Kwang Ho Kim; Moon Son; Hyun-Seog Roh; Suraj K. Tripathy; Byong-Hun Jeon (Chemical Engineering Journal, 2023)

Investigating the effect of blending of diamine and alkanolamine for CO2 capture: Experiment and thermodynamic modeling of CO2-AEEA-DEA-H2O system - Shaukat Ali Mazari; Tae-Ha Kang; Sijan Devkota; Jin-Young Cha; Beom-Ju Shin; Ji-Hun Mun; Kyung-Min Kim; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2023)

Investigating the impact of relative humidity and air tightness on PM sedimentation and concentration reduction - Minju Kim; Su-Gwang Jeong; Jongil Park; Sumin Kim; Jeong-Hun Lee (Building and Environment, 2023)

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

A stable isotopic approach for quantifying aquaculture-derived organic matter deposition dynamics in the sediment of a coastal fish farm - Young-Shin Go; Chung-Sook Kim; Won Chan Lee; Dong-Hun Lee (Marine Pollution Bulletin, 2023)

Greener homes: Factors underpinning Europeans' intention to live in multi-storey wooden buildings - Do-hun Kim; Florencia Franzini; Bo Jellesmark Thorsen; Sami Berghäll; Francisco X. Aguilar (Sustainable Production and Consumption, 2023)

Multi-organ metastases of primary chondrosarcoma of the mammary gland of a spayed Toy Poodle - Seung-Won Yi; A-Ra Cho; Yoon Jung Do; Young-Hun Jung; Han Gyu Lee; Eun-Yeong Bok; Tai-Young Hur; Sung-Lim Lee; Eunju Kim (Journal of Comparative Pathology, 2023)

Iridin abrogates LPS-induced inflammation in L6 skeletal muscle cells by inhibiting NF-κB and MAPK signaling pathway - Pritam Bhagwan Bhosale; Sang Eun Ha; Hun Hwan Kim; Abuyaseer Abusaliya; Min Yeong Park; Gon Sup Kim; Jin-A. Kim (Molecular & Cellular Toxicology, 2023)

Wintertime sea surface temperature variability modulated by Arctic Oscillation in the northwestern part of the East/Japan Sea and its relationship with marine heatwaves - Se-Yong Song; Yoo-Jun Kim; Eun-Joo Lee; Sang-Wook Yeh; Jae-Hun Park; Young-Gyu Park (Frontiers in Marine Science, 2023)
The northwestern part of the East/Japan Sea (EJS) is a region with large sea surface temperature (SST) variability and is known as a hotspot of marine heatwaves (MHW) stress for marine environments that peaked in boreal winter (January-February-March). This could have profound impacts on the marine ecosystems over the EJS. Here, we used a set of high-resolution satellite and reanalysis products to systematically analyze the spatiotemporal SST variations and examine their linkage to a large-scale mode of climate variability, such as the Arctic Oscillation (AO). The results show that AO-related wind forcing modulates the SST variability over the EJS via the oceanic dynamic adjustment processes. In particular, the abnormally warm SSTs in the northwestern part of the EJS are driven by the anomalous anticyclonic eddy-like circulation and Ekman downwelling during a positive AO phase. This physical linkage between a positive AO and the abnormally warm SST could be conducive to MHW occurrences in the EJS as in the extremely positive AO event during the winter of 2020. These results have implications that the MHW occurrences in the EJS could be amplified by natural climate variability along with long-term SST warming.

Seasonal Variability of the Deep Western Boundary Current in the Philippine Sea - Hajin Song; Xiao-Hua Zhu; Ze-Nan Zhu; Jeong-Yeob Chae; Chanhyung Jeon; Dong-Guk Kim; Hong-Sik Min; Jae-Hak Lee; Jae-Hun Park (Journal of Marine Science and Engineering, 2023)
The deep western boundary current (DWBC) in the Philippine Sea has been expected to play a crucial role in transporting lower circumpolar deep water and to contribute to regional and global climate regulation. Two-year-long near-bottom current measurements reveal a southward-flowing DWBC with a mean velocity of 5 cm/s and seasonal variations—weaker in summer and stronger in winter. Seasonal variability in the DWBC is hypothesized to be induced by changes in the North Equatorial Current bifurcation latitude (NECBL) and upper pycnocline depth through potential vorticity conservation. Data-assimilated reanalysis model (GLORYS12V1) outputs, which reproduce the seasonal variability of DWBC similarly to the observation, are used for further analysis. During the seasonal period, the NECBL displays significant coherence (>0.9) with the first-mode empirical orthogonal function principal component of the simulated along-slope DWBC. The upper pycnocline depth, varying seasonally within a range of approximately 27 m, induces seasonal variability in a deep anticyclonic eddy trapped by topography. In summer, the intensified deep anticyclonic eddy obstructs the adjacent southward-flowing DWBC, weakening its strength, whereas in winter, the southward flow of the DWBC is enhanced due to the weakening of the deep anticyclonic eddy.

Application of the CPFD method to analyze the effects of bed material density on gas-particle hydrodynamics and wall erosion in a CFB boiler - Byoung-Hwa Lee; Yoon-Ho Bae; Kang-Min Kim; Yu Jiang; Young-Hun Ahn; Chung-Hwan Jeon (Fuel, 2023)

Purification of phenoloxidase from Haliotis discus hannai and its anti-inflammatory activity in vitro - Seung-Yub Song; Dae-Hun Park; Sung-Ho Lee; Han-Kyu Lim; Jin-Woo Park; Chae-Rim Jeong; Soo-Jung Kim; Seung-Sik Cho (Fish & Shellfish Immunology, 2023)

Multiscale strategy to predict the fracture toughness and crack extension behavior of ozone-functionalized carbon nanotube/epoxy nanocomposites - Haolin Wang; Jihun Lee; Jae Hun Kim; Hyunseong Shin (Chemical Engineering Journal, 2023)

True self-reinforced composites enabled by tuning of molecular structure for lightweight structural materials in future mobility - Hyeseong Lee; Ji-un Jang; Jaewoo Kim; Yoon Sang Kim; Jaehyun Cho; Mi Na Kim; Jung Tae Lee; Woo Hyuk Choi; Jong Man Song; Won June Song; Dong Hui Won; Deok Woo Yun; et al. (Chemical Engineering Journal, 2023)

Cutting-edge technological advancements in biomass-derived hydrogen production - Shouvik Saha; Amita Mondal; Mayur B. Kurade; Yongtae Ahn; Priyabrata Banerjee; Hyun-Kyung Park; Ashok Pandey; Tae Hyun Kim; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2023)

Sensitivity Analysis of Forecasting Performance for ST6 Parameterization in High-Resolution Wave Model Based on WAVEWATCH III - Min Roh; Sang-Myeong Oh; Pil-Hun Chang; Hyun-Suk Kang; Hyung-Suk Kim (Journal of Marine Science and Engineering, 2023)
A regional wave forecasting system in East Asia, including the Korean Peninsula, was built based on WAVEWATCH III using offshore wind forecast data from the Global Data Assimilation Prediction System. The numerical simulations were performed on the sensitivity of the interaction between input wind and wave development. The forecasts for each condition were compared and verified with the observational data of marine meteorological buoys from 1 August to 30 September 2020. The sensitivity conditions were configured to have a specific range of variables related to the directional distribution of input winds (SINA0) and variables indicating the development of input wind–wave (CDFAC) in the ST6. The results were presented by calculating the mean error and root mean square error for all observation points. Overall, as the CDFAC increased, the mean error tended to decrease according to the forecast time and the root mean square error increased. Although the effect of SINA0 at the same CDFAC was insignificant, when SINA0 increased in sections where the significant wave height decreased rapidly, the significant wave height tended to decrease. In addition, the main variables that affect the physical process of wind–wave interaction should be considered to improve wave model forecasting performance and accuracy.

Systematic tracing of nitrate sources in a complex river catchment: An integrated approach using stable isotopes and hydrological models - Seung-Hee Kim; Dong-Hun Lee; Min-Seob Kim; Han-Pil Rhee; Jin Hur; Kyung-Hoon Shin (Water Research, 2023)

Protocol for efficient ginseng transformation - Young-Hun Kim; Chan-Woo Park; Woo-Jong Hong; Ick Hyun Jo; Keun Ki Kim; Yu-Jin Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Sodium arsenite-induced cytotoxicity is regulated by BNIP3L/Nix-mediated endoplasmic reticulum stress responses and CCPG1-mediated endoplasmic reticulum-phagy - Sang-Hun Kim; Seon-Hee Oh (Environmental Toxicology and Pharmacology, 2023)

Intensified near-field by localizing surface plasmon for enhancing photoelectrochemical responses via periodically patterned Au assemblies - Young Moon Choi; Seung Hun Roh; Eujin Kwak; Dae-Geun Choi; Seok Joon Kwon; Jung Kyu Kim; Jong Hyeok Park (Chemical Engineering Journal, 2023)

Thermocatalytic conversion of wood-plastic composite over HZSM-5 catalysts - Jihyeon Seo; Hyunjin Kim; Sugyeong Jeon; Soheil Valizadeh; Yasin Khani; Byong-Hun Jeon; Gwang Hoon Rhee; Wei-Hsin Chen; Shiung Lam; Moonis Ali Khan; Young-Kwon Park (Bioresource Technology, 2023)

Decrease in population of swans (Cygnus spp.) due to the development of areas adjacent to the wintering site - Suk-Hwan Hong; Jung-Hun Yeum; Si-Hwan Kim; June-Log Park (Wetlands Ecology and Management, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

ATF4-activated parkin induction contributes to deferasirox-mediated cytoprotection in Parkinson’s disease - Sangwoo Ham; Ji Hun Kim; Heejeong Kim; Jeong-Yong Shin; Yunjong Lee (Toxicological Research, 2023)

Evaluation of dryout region in a heap-like debris bed formed in an APR1400 pre-flooded reactor cavity - Hanbee Na; Ji-Hun Kim; Dong-Ho Shin; Han-Chul Kim; Sok Chul Kim (Annals of Nuclear Energy, 2023)

First report of pitaya virus X infecting dragon fruit (Selenicereus undatus) in Korea - Nam-Yeon Kim; Yong Hun Jo; Young Min Bae; Kyung-Pyo Lee; Rae-Dong Jeong; Yeon Soo Han; KiBeom Park (Journal of Plant Pathology, 2023)

Evaluation of the ventilation and pollutant exposure risk level inside 3D street canyon with void deck under different wind directions - Chung Hyok Sin; Kwang Song Jon; Gyong Ho Un; Yong Il Thae; Hun Kim; Jun Tokgo; Hyon Mu Ri (Environmental Science and Pollution Research, 2023)

Evaluating the sources and fate of nitrate in riparian aquifers under agricultural land using in situ-measured noble gases, stable isotopes, and metabolic genes - YeoJin Ju; Dong-Chan Koh; Dong-Hun Kim; Bernhard Mayer; Hong-il Kwon (Water Research, 2023)

Associations of cold exposure with hospital admission and mortality due to acute kidney injury: A nationwide time-series study in Korea - Kyoung-Nam Kim; Moon-Kyung Shin; Youn-Hee Lim; Sanghyuk Bae; Jong-Hun Kim; Seung-Sik Hwang; Mi-Ji Kim; Jongmin Oh; Hyungryul Lim; Jonghyuk Choi; Ho-Jang Kwon (Science of The Total Environment, 2023)

MOF-derived carbon/ZnS nanoparticle composite interwoven with structural and conductive CNT scaffolds for ultradurable K-ion storage - Song-Gue Choi; Young Hwan Kim; Geon-Woo Lee; Hun Seok Choi; Kwang-Bum Kim (Chemical Engineering Journal, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Evaluation of biogenic emissions from three different vegetation distributions in South Korea - Jinhyeok Yu; Kyung M. Han; Chul H. Song; Kyunghwa Lee; Sojin Lee; Younha Kim; Jung-Hun Woo; Saewung Kim; Armin Wisthaler (Atmospheric Environment, 2023)

The trend of ammonia levels in patients with glufosinate ammonium poisoning with respect to neurotoxicity - Joochan Kim; Yong Soo Cho; Byeong Jo Chun; Jeong Mi Moon; Dong Ki Kim; Byung Kook Lee; Dong Hun Lee; Seok Jin Ryu; Eujene Jung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Morphology and stability of mineralized carbon influenced by magnesium ions - Kung-Won Choi; Yongtae Ahn; Chan-Ung Kang; Chul-Min Chon; Subbaiah Muthu Prabhu; Do-Hyeon Kim; Yoon-Hee Ha; Byong-Hun Jeon (Environmental Science and Pollution Research, 2023)

Semi-mechanistic analysis of emergency planning zones for 20 MWe lead-cooled fast reactor by hypothetical accidents during Korea's arctic exploration - Chanki Lee; Seung Hun Shin; Hee Reyoung Kim; Il Soon Hwang (Journal of Environmental Radioactivity, 2023)

Molecular characterization, immune expression, and functional delineation of peroxiredoxin 1 in Epinephelus akaara - Subothini Ganeshalingam; Kishanthini Nadarajapillai; Sarithaa Sellaththurai; Gaeun Kim; Jeongeun Kim; Ji Hun Lee; Taehyug Jeong; Qiang Wan; Jehee Lee (Fish & Shellfish Immunology, 2023)

Conversion of toxic chemicals into flammable gases through the thermolysis of polyurethane foam using CO2 - Taewoo Lee; Jung-Hun Kim; Yiu Fai Tsang; Wei-Hsin Chen; Doyeon Lee; Min-Woong Jung; Sungyup Jung; Eilhann E. Kwon (Chemical Engineering Journal, 2023)

Li reaction pathways in Ge and high-performance Ge nanocomposite anodes for Li-ion batteries - Dong-Hun Lee; Do-Hyeon Kim; Heechul Jung; Cheol-Min Park (Chemical Engineering Journal, 2023)

Hydrophobic sulfur core–shell layered metallic iron for nitrate reduction with nearly 100% dinitrogen selectivity: Mechanism and field studies - Choe Earn Choong; So Yeon Yoon; Kien Tiek Wong; Minhee Kim; Gooyong Lee; Sang-Hyoun Kim; Byong-Hun Jeon; Jaeyoung Choi; Yeomin Yoon; Eun Ha Choi; Min Jang (Chemical Engineering Journal, 2023)

Algal biochar mediated detoxification of plant biomass hydrolysate: Mechanism study and valorization into polyhydroxyalkanoates - Shashi Kant Bhatia; Ranjit Gurav; Do-Hyun Cho; Byungchan Kim; Hee Ju Jung; Su Hyun Kim; Tae-Rim Choi; Hyun-Joong Kim; Yung-Hun Yang (Bioresource Technology, 2023)

Advances in physicochemical pretreatment strategies for lignocellulose biomass and their effectiveness in bioconversion for biofuel production - Bikram Basak; Ramesh Kumar; A.V.S.L. Sai Bharadwaj; Tae Hyun Kim; Jung Rae Kim; Min Jang; Sang-Eun Oh; Hyun-Seog Roh; Byong-Hun Jeon (Bioresource Technology, 2023)

Anti-Osteoarthritic Effects of Cartilage-Derived Extracellular Matrix in a Rat Osteoarthritis Model - Sang-Hun Lee; Sung-Han Jo; Seon-Hwa Kim; Chang-Su Kim; Sang-Hyug Park (Tissue Engineering and Regenerative Medicine, 2023)

Interdecadal change in the relationship between the western North Pacific subtropical high and the ENSO - Jung-Eun Esther Kim; Changhyun Yoo; Sang-Hun Park (Theoretical and Applied Climatology, 2023)

Protective effect of 7-hydroxyl-1-methylindole-3-acetonitrile on the intestinal mucosal damage response to inflammation in mice with DSS-induced colitis - Kyung-Sook Chung; Sang-Eun Park; Jung-Hun Lee; Su-Yeon Kim; Hee-Soo Han; Yong Sup Lee; Seang-Hwan Jung; Eungyeong Jang; Sangmin Lee; Kyung-Tae Lee (Chemico-Biological Interactions, 2023)

Review of chemical pretreatment of lignocellulosic biomass using low-liquid and low-chemical catalysts for effective bioconversion - A.V.S.L Sai Bharadwaj; Subhabrata Dev; Jingshun Zhuang; Yunxuan Wang; Chang Geun Yoo; Byong-Hun Jeon; Srijan Aggarwal; Seung Hyun Park; Tae Hyun Kim (Bioresource Technology, 2023)

Exposure assessment for pesticide residues in agricultural products consumed in the Republic of Korea during 2016–2020 - Tae-Hun Kim; Su Chin Park; Ji Eun Kim; Hyun Jun Yeon; Ju Ho Kim; Young Soek Park; Soo-Hwaun Kim; Yoon-Hee Oh; Gune-Hee Jo (Environmental Science and Pollution Research, 2023)

Correction to: Transplantation of PSA-NCAM-Positive Neural Precursors from Human Embryonic Stem Cells Promotes Functional Recovery in an Animal Model of Spinal Cord Injury - Do-Hun Kim; Hyun-Ju Cho; Chul-Yong Park; Myung Soo Cho; Dong-Wook Kim (Tissue Engineering and Regenerative Medicine, 2022)

Bone Regeneration with 3D-Printed Hybrid Bone Scaffolds in a Canine Radial Bone Defect Model - Yoon Jae Lee; Yeon Hee Ryu; Su Jin Lee; Suk-Ho Moon; Ki Joo Kim; Byeong Ju Jin; Kyoung-Don Lee; Jung Kyu Park; Jin Woo Lee; Seung-Jae Lee; Hun-Jin Jeong; Jong Won Rhie (Tissue Engineering and Regenerative Medicine, 2022)

Transplantation of PSA-NCAM-Positive Neural Precursors from Human Embryonic Stem Cells Promotes Functional Recovery in an Animal Model of Spinal Cord Injury - Do-Hun Kim; Hyun-Ju Cho; Chul-Yong Park; Myung Soo Cho; Dong-Wook Kim (Tissue Engineering and Regenerative Medicine, 2022)

Correction to: Interpreting complex geochemistry of groundwater in a coastal paddy field near a mine using isotopic signatures of sulfate and water - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2022)

Overexpression of the ginseng GH18 gene confers salinity tolerance in Arabidopsis - Gayoung Noh; Ji-Hyun Kim; Sung Won Cho; Young-Hun Kim; Ju-Young Jung; Woo-Jong Hong; Ki-Hong Jung; Gyulim Park; Hong-Joo Son; Ick Hyun Jo; Young Hun Song; Sun Tae Kim; et al. (Plant Biotechnology Reports, 2022)

New parameterization of air-sea exchange coefficients and its impact on intensity prediction under major tropical cyclones - Woojeong Lee; Sung-Hun Kim; Il-Ju Moon; Michael M. Bell; Isaac Ginis (Frontiers in Marine Science, 2022)
Understanding and quantifying air-sea exchanges of enthalpy and momentum fluxes are crucial for the advanced prediction of tropical cyclone (TC) intensity. Here, we present a new parameterization of air-sea fluxes at extreme wind speeds from 40 m s −1 to 75 m s −1 , which covers the range of major TCs. Our approach assumes that the TC can reach its maximum potential intensity (MPI) if there are no influences of external forces such as vertical wind shear or other environmental constraints.This method can estimate the ratio of the enthalpy and momentum exchange coefficient ( C k / C d ) under the most intense TCs without direct flux measurements. The estimation showed that C k / C d increases with wind speed at extreme winds above 40 m s −1 . Two types of surface layer schemes of the Hurricane Weather and Research Forecast (HWRF) were designed based on the wind speed dependency of the C k / C d found at high winds: (i) an increase of C k / C d based on decreasing C d (Cd_DC) and (ii) an increase of C k / C d based on increasing C k (Ck_IC). The modified surface layer schemes were compared to the original HWRF scheme (using nearly fixed C d and C k at extreme winds; CTRL) through idealized experiments and real-case predictions. The idealized experiments showed that Cd_DC reduced frictional dissipation in the air-sea interface as well as significantly reduced sea surface cooling, making the TC stronger than other schemes. As a result, Cd_DC reduced the mean absolute error and negative bias by 15.0% (21.0%) and 19.1% (32.0%), respectively, for all lead times of Hurricane Irma in 2017 (Typhoon Mangkhut in 2018) compared to CTRL. This result suggests that new parameterization of C k / C d with decreasing C d at high winds can help improve TC intensity prediction, which currently suffers from underestimating the intensity of the strongest TCs.

Effects of isoflurane anesthesia on addictive behaviors in rats - Seong Shoon Yoon; Bong Hyo Lee; Seong Ho Lee; Seong Hun Choi; Seon-Ju Jeong; Sang Chan Kim; Chae Ha Yang (Psychopharmacology, 2022)

Effects of the reduced air-sea drag coefficient in high winds on the rapid intensification of tropical cyclones and bimodality of the lifetime maximum intensity - Sung-Hun Kim; Hyoun-Woo Kang; Il-Ju Moon; Sok Kuh Kang; Pao-Shin Chu (Frontiers in Marine Science, 2022)
The air-sea drag coefficient ( C d ) is closely related to tropical cyclone (TC) intensification. Several recent studies suggested that the C d decreases in winds greater than 33 m s −1 . The effects of C d reduction in high winds on TC intensity, especially rapid intensification (RI) and the lifetime maximum intensity (LMI) distribution, were investigated by analyzing the wind-dependent C d -based ocean vertical mixing and the energy budget. In addition, to consider the uncertainty of the Cd in extreme winds (above 50 m s −1 ), three types of C d fitting that decrease after 33 m s −1 , which show different trends after 50 m s −1 (increase, flat, and decrease), were adopted. The results were then compared with those for the control fitting (saturated after 33 m s −1 ) and show that the reduced C d in high winds drives an increase in net energy by reducing frictional dissipation and suppressing sea surface cooling. This extra energy prevents the TC from achieving a steady-state, causing the bimodality of simulated maximum potential intensity. The observed steady-state probability (intensification rate and RI probability) in the C d reduced wind range were significantly lower (higher) than in the others. These results suggest that C d reduction might potentially induce the RI and LMI bimodality.

Reconstruction of long-term sea-level data gaps of tide gauge records using a neural network operator - Eun-Joo Lee; Kiduk Kim; Jae-Hun Park (Frontiers in Marine Science, 2022)
The coastal sea level is an important factor in understanding and clarifying the physical processes in coastal seas. However, missing values and outliers of the sea level that occur for various reasons often disrupt the continuity of its time series. General-purpose time-series analysis and prediction methods are not tolerant of missing values, which is why researchers have attempted to fill these gaps. The disadvantage of conventional time-series reconstruction techniques is the low accuracy when missed sea-level records are longer than the timescales of coastal processes. To solve this problem, we used an artificial neural network, which is a novel tool for creating multivariate and nonlinear regression equations. The trained neural network weight set was designed to enable long-term reconstruction of sea level by acting as a one-step prediction operator. In addition, a data assimilation technique was developed and adapted to ensure seamless continuity between predicted and observed sea-level records. The application of our newly developed method to 3-day gaps of seal level records at 16 tide gauge stations around the Korean peninsula confirms that it can successfully reconstruct missing values with root-mean-squared errors of 0.5–1.1 cm on average.

Motion Control System Design for Barge-Type Surface Ships Using Tugboats - Dong-Hun Lee; Thinh Huynh; Young-Bok Kim; Jung-Suk Park (Journal of Marine Science and Engineering, 2022)
Barge ships are designed to transport and assemble heavy and massive pieces of equipment at sea. Active propulsion systems are not installed in this type of ship, so the desirable motion and positioning of these ships can only be achieved with the assistance of several tugboats. In this study, the dynamical characteristics of barge conveying systems were formulated and robust control systems were designed to ensure efficient barge operation. To achieve these objectives, we first developed a mathematical model of a barge ship, which incorporated a novel conveying system configuration using tugboats. We then designed a robust controller for the tugboats that used the sliding mode law to deliver the desired barge motion performance. Finally, the usefulness of the proposed configuration and controller was verified via simulation studies using another system with an H∞ controller. The proposed sliding mode controller showed superiority, especially in terms of robustness against disturbances.

Geochemical signatures of organic matter associated with gas generation in the Pohang Basin, South Korea - Dong-Hun Lee; Seung-Hee Kim; Jiyoung Choi; Nyeon-Keon Kang; In Gul Hwang; Kyung-Hoon Shin (Geosciences Journal, 2022)

Variations in food resource usage among eight fish species inhabiting inside and outside Jinju Bay, Korea - Se Hun Myoung; Jin-Koo Kim; Seok Nam Kwak; Joo Myun Park (Environmental Biology of Fishes, 2022)

Biotransformation of C20- and C22-polyunsaturated fatty acids to 11S- and 13S-hydroxy fatty acids by Escherichia coli expressing 11S-lipoxygenase from Enhygromyxa salina - Jin Lee; Tae-Hun Kim; Kyung-Chul Shin; Tae-Eui Lee; Min-Ju Kim; Deok-Kun Oh (Biotechnology Letters, 2022)

Selective Serotonin Reuptake Inhibitor Promotes Bone-Tendon Interface Healing in a Rotator Cuff Tear Rat Model - Jong Pil Yoon; Jee Wook Yoon; Hun‐Min Kim; Joo Han Oh (Tissue Engineering and Regenerative Medicine, 2022)

Impact of High Methane Flux on the Properties of Pore Fluid and Methane-Derived Authigenic Carbonate in the ARAON Mounds, Chukchi Sea - Ji-Hoon Kim; Myong-Ho Park; Dong-Hun Lee; Hirotsugu Minami; Young-Keun Jin; Akihiro Hachikubo; Jin Hur; Jong-Sik Ryu; Moo-Hee Kang; Kwangchul Jang; Masato Kida; Yongwon Seo; et al. (Frontiers in Marine Science, 2022)
We investigated the pore fluid and methane-derived authigenic carbonate (MDAC) chemistry from the ARAON Mounds in the Chukchi Sea to reveal how methane (CH 4 ) seepage impacts their compositional and isotopic properties. During the ARA07C and ARA09C Expeditions, many in situ gas hydrates (GHs) and MDACs were found near the seafloor. The fluid chemistry has been considerably modified in association with the high CH 4 flux and its related byproducts (GHs and MDACs). Compared to Site ARA09C-St 08 (reference site), which displays a linear SO 4 2- downcore profile, the other sites (e.g., ARA07C-St 13, ARA07C-St 14, ARA09C-St 04, ARA09C-St 07, and ARA09C-St 12) that are found byproducts exhibit concave-up and/or kink type SO 4 2- profiles. The physical properties and fluid pathways in sediment columns have been altered by these byproducts, which prevents the steady state condition of the dissolved species through them. Consequently, chemical zones are separated between bearing and non-bearing byproducts intervals under non-steady state condition from the seafloor to the sulfate-methane transition (SMT). GH dissociation also significantly impacts pore fluid properties (e.g., low Cl - , enriched δD and δ 18 O). The upward CH 4 with depleted δ 13 C from the thermogenic origin affects the chemical signatures of MDACs. The enriched δ 18 O fluid from GH dissociation also influences the properties of MDACs. Thus, in the ARAON Mounds, the chemistry of the fluid and MDAC has significantly changed, most likely responding to the CH 4 flux and GH dissociation through geological time. Overall, our findings will improve the understanding and prediction of the pore fluid and MDAC chemistry in the Arctic Ocean related to CH 4 seepage by global climate change.

Activation of galactose utilization by the addition of glucose for the fermentation of agar hydrolysate using Lactobacillus brevis ATCC 14869 - Godfrey Mwiti; In-Seok Yeo; Kyung-Hun Jeong; Hyung-Seok Choi; Jaehan Kim (Biotechnology Letters, 2022)

Weakening of the Kuroshio Upstream by Cyclonic Cold Eddies Enhanced by the Consecutive Passages of Typhoons Danas, Wipha, and Francisco (2013) - Chanhyung Jeon; D. Randolph Watts; Hong Sik Min; Dong Guk Kim; Sok Kuh Kang; Il-Ju Moon; Jae-Hun Park (Frontiers in Marine Science, 2022)
An array of five pressure-recording inverted echo sounder (PIES) moorings spanning a distance of 420 km around the subtropical countercurrent and North Equatorial Current regions of the western Pacific detected extraordinary sea level drops from November to December 2013. In October 2013, three typhoons, namely, Danas, Wipha, and Francisco, consecutively passed east of the PIES sites, which significantly strengthened pre-existing cyclonic cold eddies to create the observed sea level drops. The typhoon-strengthened cold eddies propagated westward over approximately 1000 km for approximately 4 months and eventually met the Kuroshio offshore Taiwan. The approaching eddies interacted with the Kuroshio upstream for ~3 months and reduced the Kuroshio intensity by up to 24% in February–May 2014, the lowest record for the last 26 years of satellite measurements. Our results can provide a new mechanism linking typhoon-to-eddy-to-Kuroshio variability through oceanic processes.

Kelps in Korea: from population structure to aquaculture to potential carbon sequestration - Eun Kyoung Hwang; Ga Hun Boo; Louis Graf; Charles Yarish; Hwan Su Yoon; Jang Kyun Kim (Algae, 2022)
Korea is one of the most advanced countries in kelp aquaculture. The brown algae, Undaria pinnatifida and Saccharina japonica are major aquaculture species and have been principally utilized for human food and abalone feed in Korea. This review discusses the diversity, population structure and genomics of kelps. In addition, we have introduced new cultivar development efforts considering climate change, and potential carbon sequestration of kelp aquaculture in Korea. U. pinnatifida showed high diversity within the natural populations but reduced genetic diversity in cultivars. However, very few studies of S. japonica have been conducted in terms of population structure. Since studies on cultivar development began in early 2000s, five U. pinnatifida and one S. japonica varieties have been registered to the International Union for the Protection of New Varieties of Plants (UPOV). To meet the demands for seaweed biomass in various industries, more cultivars should be developed with specific traits to meet application demands. Additionally, cultivation technologies should be diversified, such as integrated multi-trophic aquaculture (IMTA) and offshore aquaculture, to achieve environmental and economic sustainability. These kelps are anticipated to be important sources of blue carbon in Korea.

Decreasing or increasing trends? Evidence of long-term change in river discharge over the northern Korean Peninsula, 1951–2010 - Jong-Hun Kim; Myong-Bong Jo; Nam-Chol O; Tong-Ho Ri; Jong-Hye Choe; Song-Il Phi (Journal of Earth System Science, 2022)

Universal Stress Protein (USP) Enhances Plant Growth and Development by Promoting Cell Expansion - Eun Seon Lee; Kieu Anh Thi Phan; Sang Eun Jun; Joung Hun Park; Seol Ki Paeng; Ho Byoung Chae; Seong Dong Wi; Su Bin Bae; Kee Ryeon Kang; Gyung-Tae Kim; Sang Yeol Lee (Journal of Plant Biology, 2022)

Sacubitril/valsartan reduces endoplasmic reticulum stress in a rat model of doxorubicin-induced cardiotoxicity - Byung Sik Kim; In-Hwa Park; A-Hyeon Lee; Hyun-Jin Kim; Young-Hyo Lim; Jeong-Hun Shin (Archives of Toxicology, 2022)

Application of the Korean Framework of Wetland Management Effectiveness Evaluation - Nak-Hyun Choi; Jung-Hun Yeum; Han Kim (Wetlands, 2022)

Selection and Characterization of Probiotic Bacteria Exhibiting Antiadipogenic Potential in 3T3-L1 Preadipocytes - Chul Sang Lee; Mi Hyun Park; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2022)

Autophagy inducers lead to transient accumulation of autophagosomes in Arabidopsis roots - Jeong Hun Kim; Hyera Jung; Ye Eun Choi; Taijoon Chung (Plant Cell Reports, 2022)

Physicochemical and isotopic properties of ambient aerosols and precipitation particles during winter in Seoul, South Korea - Hanna Choi; Heejo Lee; Dong-Hun Kim; Kang-Kun Lee; Yongcheol Kim (Environmental Science and Pollution Research, 2022)

Seed-Specifically Overexpressed Arabidopsis Cytochrome P450 85A2 Promotes Vegetative and Reproductive Growth and Development of Arabidopsis thaliana - Myeong Hun Yeon; Chan-Ho Park; Ye Eun Lee; Jeehee Roh; Seong-Ki Kim (Journal of Plant Biology, 2022)

Glycosidic flavonoids and their potential applications in cancer research: a review - Abuyaseer Abusaliya; Sang Eun Ha; Pritam Bhagwan Bhosale; Hun Hwan Kim; Min Yeong Park; Preethi Vetrivel; Gon Sup Kim (Molecular & Cellular Toxicology, 2022)
Purpose of review Every year, the cancer patient registry increases, and the leading cause of death in a global context. Plant-based molecules are gaining attention in cancer research due to the side effects of chemotherapy. A glycosidic derivative of flavonoid (GDF) plays a significant role in cancer proliferation mechanisms. GDF inhibits cell proliferation by elevating the expression of apoptotic proteins, altering the expression of nuclear factor-kappa B (NF- κB), and decreasing mitochondrial membrane potential (Δψm) in cancer cells. Recent findings Reported studies on the flavonoids orientin, vitexin, prunetionoside, chrysin, and scutellarein increased attention and are being widely investigated for their potential role in different parts of cancer research. Prunetionoside is a flavonoid with high cytotoxic potential and capable of inducing necroptosis in AGS gastric cancer cells. Similarly, scutellarein is a flavonol, induces an extrinsic apoptotic pathway and downregulates the expression level of cyclin proteins in HepG2 liver cancer cells. Vitexin is reported to be capable of deregulating the expression levels of p-Akt, p-mTOR, and p-PI3K in A549 lung cancer cells. Orientin inhibits IL-8 expression and invasion in MCF-7 breast cancer cells by suppressing MMP-9 in the presence of TPA via STAT3/AP-1/ERK/PKCα-mediated signaling pathways. It also induces mitochondria-mediated intrinsic apoptosis and G0/G1 cell cycle arrest in HT29 colon cancer cells. Chrysin is a flavonoid present in honey that has been shown to play an important role in cervical and colon cancer by suppressing the AKT/mTOR/PI3K pathway and increasing ROS accumulation, LDH leakage, respectively.

Risk factors of septic shock development and thirty-day mortality with a predictive model in adult candidemia patients in intensive care units - Jin Woong Suh; Min Ja Kim; Jong Hun Kim (Infectious Diseases, 2021)

The Responsiveness of Gait and Balance Outcomes to Disease Progression in Friedreich Ataxia - Sarah C. Milne; Seok Hun Kim; Anna Murphy; Jane Larkindale; Jennifer Farmer; Ritchie Malapira; Mary Danoudis; Jessica Shaw; Tyagi Ramakrishnan; Fatemeh Rasouli; Eppie M. Yiu; Nellie Georgiou-Karistianis; et al. (The Cerebellum, 2021)

Spatial Distribution, Growth Conditions and Local Utilization for Conservation Strategy of an Endangered Species Azolla japonica - SeokHyeon Oh; Byoung Woo Kim; SangEun Kwak; Hun Park; Hojun Rim; Uhram Song (Journal of Plant Biology, 2021)

Dietary supplementations of Bacillus probiotic improve digestibility, growth performance, innate immunity, and water ammonia level for Pacific white shrimp, Litopenaeus vannamei - Chorong Lee; Soohwan Kim; Jaehyeong Shin; Min-Gi Kim; Buddhi E. Gunathilaka; Sung Hun Kim; Ji Eun Kim; Seung-Cheol Ji; Jee Eun Han; Kyeong-Jun Lee (Aquaculture International, 2021)

High-resolution magnetic resonance imaging for the follow-up of intracranial arterial dissections - Sang-Hun Lee; Keon-Yeup Kim; Jin-Man Jung (Acta Neurologica Belgica, 2021)

Dose-independent pharmacokinetics of loganin in rats: effect of intestinal first-pass metabolism on bioavailability - Hwi Jin Park; Sung Hun Bae; So Hee Kim (Journal of Pharmaceutical Investigation, 2021)

Giant Y79 retinoblastoma cells contain functionally active T-type calcium channels - Sooyun Kim; Segundo Jose Guzman; Dong Hyun Jo; Chang Sik Cho; Jeong Hun Kim (Pflügers Archiv - European Journal of Physiology, 2021)

Interpreting complex geochemistry of groundwater in a coastal paddy field near a mine using isotopic signatures of sulfate and water - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2021)

Determination of soil contamination sources in mining area using Zn/Cd ratios with mobile Cd - Duk-Min Kim; Oh-Hun Kwon; Youn Soo Oh; Jin-Soo Lee (Environmental Geochemistry and Health, 2021)

Downregulation of PyHRG1, encoding a novel secretory protein in the red alga Pyropia yezoensis, enhances heat tolerance - Narae Han; Jiwoong Wi; Sungoh Im; Ka-Min Lim; Hun-Dong Lee; Won-Joong Jeong; Geun-Joong Kim; Chan Song Kim; Eun-Jeong Park; Mi Sook Hwang; Dong-Woog Choi (Algae, 2021)
An increase in seawater temperature owing to global warming is expected to substantially limit the growth of marine algae, including Pyropia yezoensis, a commercially valuable red alga. To improve our knowledge of the genes involved in the acquisition of heat tolerance in P. yezoensis, transcriptomes sequences were obtained from both the wild-type SG104 P. yezoensis and heat-tolerant mutant Gy500. We selected 1,251 differentially expressed genes that were up- or downregulated in response to the heat stress condition and in the heat-tolerant mutant Gy500, based on fragment per million reads expression values. Among them, PyHRG1 was downregulated under heat stress in SG104 and expressed at a low level in Gy500. PyHRG1 encodes a secretory protein of 26.5 kDa. PyHRG1 shows no significant sequence homology with any known genes deposited in public databases to date. However, PyHRG1 homologs were found in other red algae, including other Pyropia species. When PyHRG1 was introduced into the single-cell green alga Chlamydomonas reinhardtii, transformed cells overexpressing PyHRG1 showed severely retarded growth. These results demonstrate that PyHRG1 encodes a novel red algae-specific protein and plays a role in heat tolerance in algae. The transcriptome sequences obtained in this study, which include PyHRG1, will facilitate future studies to understand the molecular mechanisms involved in heat tolerance in red algae.

Desorption technologies for remediation of cesium-contaminated soils: a short review - Sang-Min Park; Jong-Gook Kim; Hye-Bin Kim; Young-Hun Kim; Kitae Baek (Environmental Geochemistry and Health, 2021)

Identification of novel candidate genes implicated in odontogenic potential in the developing mouse tooth germ using transcriptome analysis - Yeo-Kyeong Shin; Seongmin Cheon; Sung-Duk Kim; Jung-Sun Moon; Jae-Young Kim; Sun-Hun Kim; Chungoo Park; Min-Seok Kim (Genes & Genomics, 2021)

Novel Method for the Estimation of Vertical Temperature Profiles Using a Coastal Acoustic Tomography System - Yeongbin Park; Chanhyung Jeon; Hajin Song; Youngseok Choi; Jeong-Yeob Chae; Eun-Joo Lee; Jin Sung Kim; Jae-Hun Park (Frontiers in Marine Science, 2021)
Systems based on remote sensing technology, which use reciprocal acoustic signals to continuously monitor changes in the coastal oceanic environment, are referred to as coastal acoustic tomography (CAT) systems. These systems have been applied in regions in which heavy ship traffics, fishing and marine aquaculture activities make it difficult to establish in situ oceanic sensor moorings. Conventionally, CAT measurements were used to successfully produce horizontal maps of the depth-averaged current velocity and temperature in these coastal regions without attempting to produce a vertical temperature profile. This prompted us to propose a new method for vertical temperature profile estimation (VTPE) from CAT data using the available sea surface temperature (SST), near-bottom temperature (NBT), and water depth. The VTPE method was validated using data-assimilated and tide-included high-resolution ocean model outputs, including tide data, by comparing the estimated and simulated temperatures. Measurements were performed in the southern coastal region of Korea, where two CAT stations were moored to establish a continuous coastal ocean monitoring system. The validation results revealed that the algorithm performed well across all seasons. Sensitivity tests of the VTPE method with reasonable realistic random errors in the SST, NBT, and acoustic travel time measurements demonstrate that the method is applicable to CAT observation data because the monthly mean root-mean-squared difference (RMSD) for the vertical profiles for February, May, August, and November were 0.23, 0.30, 0.50, and 0.24°C, respectively. The VTPE method was applied to the CAT observation datasets acquired in February and August. The transceivers at the CAT stations were at depths 11 and 6 m on average. The RMSD between the estimated and observed temperatures in the middle layer (∼3 m depth) between two stations in February and August were 0.08 and 0.60°C, respectively, the accuracy of which is sufficient in largely time-varying coastal environments. We provide a novel method for continuous coastal subsurface environmental monitoring without interrupting maritime traffic, fishing, and marine aquaculture activities.

Antiobesity Effect of Novel Probiotic Strains in a Mouse Model of High-Fat Diet–Induced Obesity - Chul Sang Lee; Mi Hyun Park; Byoung Kook Kim; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2021)

Challenges in Monitoring Atmospheric CO2 Concentrations in Seoul Using Low-Cost Sensors - Chaerin Park; Sujong Jeong; Hoonyoung Park; Jung-Hun Woo; Sojung Sim; Jongho Kim; Junghoon Son; Hayoung Park; Yongseung Shin; Jin-ho Shin; Seung-Mi Kwon; Won-young Lee (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Genetic analysis of porcine parvoviruses detected in South Korean wild boars - Gyu-Nam Park; Sok Song; Ra Mi Cha; SeEun Choe; Jihye Shin; Song-Yi Kim; Bang-Hun Hyun; Bong-Kyun Park; Dong-Jun An (Archives of Virology, 2021)

Treadmill Exercise Alleviates Brain Iron Dyshomeostasis Accelerating Neuronal Amyloid-β Production, Neuronal Cell Death, and Cognitive Impairment in Transgenic Mice Model of Alzheimer’s Disease - Dong-Hun Choi; Ki-Chun Kwon; Dong-Joo Hwang; Jung-Hoon Koo; Hyun-Seob Um; Hong-Sun Song; Ji-Sun Kim; Yongchul Jang; Joon-Yong Cho (Molecular Neurobiology, 2021)

Geochemical and Microbial Signatures of Siboglinid Tubeworm Habitats at an Active Mud Volcano in the Canadian Beaufort Sea - Dong-Hun Lee; Jung-Hyun Kim; Yung Mi Lee; Ji-Hoon Kim; Young Keun Jin; Charles Paull; Jong-Sik Ryu; Kyung-Hoon Shin (Frontiers in Marine Science, 2021)
During the ARA08C expedition in 2017, sediment push cores were collected at an active mud volcano (420 m water depth) in the Canadian Beaufort Sea from two visually discriminative siboglinid tubeworm (ST) habitats that were colonized densely and less densely (ST1 and ST2, respectively). In this study, we investigated the biogeochemical and microbial community characteristics at ST1 by analyzing the geochemical properties, microbial lipids, and nucleic acid signatures, and comparing them with the data previously reported from ST2. The two ST sites showed distinct differences in vertical geochemical gradients [methane, sulfate, dissolved inorganic carbon (DIC), total organic carbon, and total sulfur], with a higher methane flux recorded at ST1 (0.05 mmol cm –2 y –1 ) than at ST2 (0.01 mmol cm –2 y –1 ). Notably, the δ 13 C values of DIC were more depleted at ST1 than at ST2, resulting in a higher proportion of DIC derived from the anaerobic oxidation of methane (AOM) at ST1 than at ST2. Moreover, both the ST1 and ST2 sites revealed the dominance of AOM-related lipid biomarkers (especially sn -2-hydroxyarchaeol), showing highly 13 C-depleted values. The 16S rRNA analyses showed the presence of AOM-related archaea, predominantly anaerobic methanotrophic archaea (ANME)-3 at ST1 and ST2. Our results suggest that AOM-related byproducts (sulfide and DIC) potentially derived from ANME-3 were more abundant at ST1 than at ST2. This variation was attributed to the intensity and persistence of ascending methane. Therefore, our study suggests that AOM-derived byproducts are possibly an essential energy source for tubeworms during chemosynthetic metabolism, shaping different colony types on the seafloor.

Genetic analysis and population genetic structure of hard-shelled mussel, Mytilus coruscus Gould 1861 (Mytiloida: Mytilidae) from the coasts of South Korea based on mitochondrial cytochrome oxidase (COI) gene sequences - Chang Ho Yi; Moongeun Yoon; Ji Min Kim; Il-Hun Kim; In-Young Cho; Hye Suck An (Genes & Genomics, 2021)

Numerical Simulation of Wind Wave Using Ensemble Forecast Wave Model: A Case Study of Typhoon Lingling - Min Roh; Hyung-Suk Kim; Pil-Hun Chang; Sang-Myeong Oh (Journal of Marine Science and Engineering, 2021)
A wave forecast numerical simulation was performed for Typhoon Lingling around the Korean Peninsula and in the East Asia region using sea winds from 24 members produced by the Ensemble Prediction System for Global (EPSG) of Korea Meteorological Administration (KMA). Significant wave height was observed by the ocean data buoys used to verify data of the ensemble wave model, and the results of the ensemble members were analyzed through probability verification. The forecast performance for the significant wave height improved by approximately 18% in the root mean square error in the three-day lead time compared to that of the deterministic model, and the difference in performance was particularly distinct towards mid-to-late lead times. The ensemble spread was relatively appropriate, even in the longer lead time, and each ensemble model runs were all stable. As a result of the probability verification, information on the uncertainty that could not be provided in the deterministic model could be obtained. It was found that all the Relative Operating Characteristic (ROC) curves were 0.9 or above, demonstrating good predictive performance, and the ensemble wave model is expected to be useful in identifying and determining hazardous weather conditions.

KIF11 inhibition decreases cytopathogenesis and replication of influenza A virus - Dong-In Kim; Ji-Hun Kang; Eui-Ho Kim; Young-Jin Seo (Molecular & Cellular Toxicology, 2021)

Variation of Semidiurnal Internal Tides along the Southeastern Coast of Korea Induced by Typhoons - Jeong-Yeob Chae; Chanhyung Jeon; Pyeongjoong Kim; Naoki Hirose; Ahyoung Ku; Jae-Hun Park (Journal of Marine Science and Engineering, 2021)
Typhoon-induced strong winds can dramatically change the oceanic environment, occasionally resulting in sudden stratification changes. In July 2015, two consecutive typhoons, Chanhom and Nangka, passed over the Yellow and East/Japan Seas within a week. Remarkable temperature variations were observed near the southeastern coast of Korea, caused by typhoon-induced upwelling and downwelling events, which altered the energy of semidiurnal internal tides. During the typhoon-induced downwelling event, the energy of semidiurnal internal tides near the southeastern coast of Korea varied independently from the barotropic tidal forcing. Data-assimilated numerical simulation results reveal that the pycnocline, which is typically tilted toward the coast, enables the semidiurnal internal tidal energy to propagate toward shallow regions after being generated off the coast. Meanwhile, the downwelling event deepens the pycnocline near the coast and reflects and concentrates the semidiurnal internal tide energy near the bottom off the coast. A simple mechanism using the ratio between the wave characteristic slope and the bottom slope is proposed to explain the observed variations of semidiurnal internal tide energy near the coast. This paper demonstrates a case study showing that typhoon passage can modify the energetics of internal tides, which has the potential to cause unusual short-term coastal environmental changes.

Phytochemical analysis of aerial part of Ikonnikovia kaufmanniana and their protection of DNA damage - Aizhamal Baiseitova; Janar Jenis; Jeong Yoon Kim; Zuo Peng Li; Ki Hun Park (Natural Product Research, 2021)

Application of Column Chromatography for Accurate Determination of the Carbon Isotopic Compositions of n-alkanes in Diverse Environmental Samples - Dong-Hun Lee; Jung-Hyun Kim; Kyung-Hoon Shin (Ocean Science Journal, 2021)

Effect of extraction solvent on in vitro anti-inflammatory, antioxidant activity, total phenol and flavonoid contents in Codonopsis lanceolata - Hee-Ock Boo; Jeong-Hun Park; Hag-Hyun Kim; Soo-Jeong Kwon; Sun-Hee Woo (Journal of Crop Science and Biotechnology, 2021)

Bone Generation Following Repeated Administration of Recombinant Bone Morphogenetic Protein 2 - Hye-Ju Son; Mi Nam Lee; Yuri Kim; Hyuck Choi; Byung-Chul Jeong; Sin-Hye Oh; Jung-Woo Kim; Seung-Hee Kwon; Sun-Hun Kim; Soo-Chang Song; Shee Eun Lee; Jeong-Tae Koh (Tissue Engineering and Regenerative Medicine, 2021)

Regulatory role of insulin-like growth factor-binding proteins in odontogenic mineralization in rats - Jung-Sun Moon; Yoo-Sung Nam; Jee-Hae Kang; Dong-Wook Yang; Dae-Yoon Kim; Su-Young Lee; Hyun-Mi Ko; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2021)

DREB2 Family Transcription Factors Promote the Expression of Phytocystatin1 in Arabidopsis thaliana During Seed Germination - Taeyoon Kim; Trang Thi Nguyen; Juwan Baek; Young Hun Song; Jong Chan Hong; Chae Oh Lim (Journal of Plant Biology, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

The pine wood nematode Bursaphelenchus xylophilus and molecular diagnostic methods - Jin-Pyo Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2021)

Dual role of reactive oxygen species in autophagy and apoptosis induced by compound PN in prostate cancer cells - Hyeun Deok Choi; Kwang-Youn Kim; Kwang Il Park; Sang-Hun Kim; Sul-Gi Park; Sun-Nyoung Yu; Young-Woo Kim; Dong Seob Kim; Kyung Tae Chung; Soon-Cheol Ahn (Molecular & Cellular Toxicology, 2021)

Treatment with silicon fertilizer induces changes in root morphological traits in soybean (Glycine max L.) during early growth - Yong Suk Chung; Se-Hun Kim; Chang- Wook Park; Chae -In Na; Yoonha Kim (Journal of Crop Science and Biotechnology, 2020)

Application of Jerusalem artichoke and lipid-extracted algae hydrolysate for docosahexaenoic acid production by Aurantiochytrium sp. KRS101 - Sung-Woon Heo; Young Taek Oh; Z-Hun Kim; Yong Keun Chang; Bongsoo Lee (Journal of Applied Phycology, 2020)

A short review of the pinewood nematode, Bursaphelenchus xylophilus - Bit-Na Kim; Ji Hun Kim; Ji-Young Ahn; Sunchang Kim; Byung-Kwan Cho; Yang-Hoon Kim; Jiho Min (Toxicology and Environmental Health Sciences, 2020)

Development of Entering Order and Work-Volume Assignment Algorithms for the Management of Piping Components in Offshore Structure Construction - Jung Goo Park; Ho Jung Kim; Jong Hun Woo (Journal of Marine Science and Engineering, 2020)
In the early 2010s, with rising oil prices and increasing purchase orders for offshore structures for deep-sea resource development, the shipyards that took these orders suffered unexpected losses. Unlike the construction of commercial carrier vessels, the construction of offshore structures necessary to develop deep-sea resources is difficult to manage due to the complexity of the outfitting process of the topside structure, which is a plant for gas and oil production and treatment. Piping components in particular, which comprise most of the design items, are difficult to manage because they involve 2 to 3 times the man-hours and up to 10 times the quantity of items compared to commercial carrier vessels. Due to not only high man-hours and quantity but also large fluctuations caused by design changes and long procurement lead times, process delays that result in delayed compensation frequently occurred. In response, Samsung Heavy Industries developed an integrated management system for piping components. This study describes the entering order optimization algorithm and work-volume assignment optimization algorithm, which are the core algorithms of this system. The entering order optimization algorithm determines the optimal installation order considering the procurement status of the piping components and the installation readiness status of the installation work site, through which it determines the entering order of the piping components. The algorithm seeks to accelerate the completion rate of installation of the piping components. Next, to minimize delivery delays of sub-contractors to the shipyard, this study developed a work-volume assignment optimization algorithm that can equalize the load on multiple sub-contractors considering the raw material readiness status and the production capacity of the sub-contractors, in terms of materials that must be ordered from external sub-contractors among the piping components whose entering order was determined. Finally, applying the algorithm developed using actual shipyard data resulted in an accelerated completion rate of installation and improved balance of load in terms of volume assigned to the sub-contractors.

Correction to: GC/MS analysis and anti-inflammatory effect of leaf extracts from Hibiscus syriacus through inhibition of NF-κB and MAPKs signaling in LPS-stimulated RAW264.7 macrophages - Hyun Ji Eo; Hae Yun Kwon; Da Som Kim; Yeongyeong Kang; Youngki Park; Gwang Hun Park (Plant Biotechnology Reports, 2020)

GC/MS analysis and anti-inflammatory effect of leaf extracts from Hibiscus syriacus through inhibition of NF-κB and MAPKs signaling in LPS-stimulated RAW264.7 macrophages - Hyun Ji Eo; Hae Yun Kwon; Som Da Kim; Yeongyeong Kang; Youngki Park; Gwang Hun Park (Plant Biotechnology Reports, 2020)

Exposure assessment and safe intake guidelines for heavy metals in consumed fishery products in the Republic of Korea - Tae-Hun Kim; Ju Ho Kim; Min Dil Le Kim; Won Duck Suh; Ji Eun Kim; Hyun Jun Yeon; Young Soek Park; Soo-Hwaun Kim; Yoon-Hee Oh; Gune-Hee Jo (Environmental Science and Pollution Research, 2020)

Anidulafungin Versus Micafungin in the Treatment of Candidemia in Adult Patients - Jin Woong Suh; Sun Bean Kim; Young Kyung Yoon; Jang Wook Sohn; Min Ja Kim; Jong Hun Kim (Mycopathologia, 2020)

Characterization of genetic variation and antioxidant properties in strawberry (Fragaria × ananassa Duch.) mutant genotypes - Jaihyunk Ryu; Woon Ji Kim; Sang Hun Kim; Kang-Seop Lee; Han-Jig Jo; Ee-Youb Kim; Sang Hoon Kim; Si-Yong Kang; Jeong-Hee Lee; Bo-Keun Ha (Genetic Resources and Crop Evolution, 2020)

Aptamer-linked immobilized sorbent assay for detecting GMO marker, phosphinothricin acetyltransferase (PAT) - Woo-Ri Shin; Mun-Jong Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2020)

Wax-printed well pads and colorimetric LAMP detection of ApxIA toxin gene - SeonHyung Lee; Ji Hun Kim; Beom-Ku Han; Won-Il Kim; Byung-Kwan Cho; Sung Min Woo; Yang-Hoon Kim; Ji-Young Ahn (Molecular & Cellular Toxicology, 2020)

Association between the IL-6, IL-10, and TNFα gene polymorphisms and preterm-birth in Korean women - Seung Hun Han; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2020)

Anti-inflammatory and Anti-osteoporotic Potential of Lactobacillus plantarum A41 and L. fermentum SRK414 as Probiotics - Chul Sang Lee; Sae Hun Kim (Probiotics and Antimicrobial Proteins, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Birth, Growth, Maturation, and Demise of Plant Autophagic Vesicles - Jeong Hun Kim; Hyera Jung; Taijoon Chung (Journal of Plant Biology, 2020)

Evaluation of NDVI Estimation Considering Atmospheric and BRDF Correction through Himawari-8/AHI - Noh-Hun Seong; Daeseong Jung; Jinsoo Kim; Kyung-Soo Han (Asia-Pacific Journal of Atmospheric Sciences, 2020)
Satellite-based vegetation indices are an essential element in understanding the Earth’s surface. In this study, we estimated the normalized difference vegetation index (NDVI) using Himawari-8/Advanced Himawari Imager (AHI) data and analyzed the sensitivity of products to atmospheric and surface correction. We used the Second Simulation of a Satellite Signal in the Solar Spectrum (6S) radiative transfer model for atmospheric correction, and kernel-based semi-empirical bidirectional reflectance distribution function (BRDF) model to remove surface anisotropic effects. From this, top-of-atmosphere, top-of-canopy, and normalized NDVIs were produced. A sensitivity analysis showed that the normalized NDVI had the lowest number of missing values compared with the others and almost no low peaks during the study period. These results were validated by Terra and Aqua/Moderate Resolution Imaging Spectroradiometer (MODIS) and Project for On-Board Autonomy/Vegetation (PROBA) NDVI product, showing the root mean square error (RMSE) and bias of 0.09 and + 0.04 (MODIS) and 0.09 and − 0.04 (PROBA), respectively. These results also satisfied the FP7 Geoland2/BioPar project-defined user requirements (threshold: 0.15; target: 0.10).

Protective effect of Lactobacillus casei HY2782 against particulate matter toxicity in human intestinal CCD-18Co cells and Caenorhabditis elegans - Joo Yeon Kim; So Young Lee; Seung-Hee Jung; Mi Ri Kim; Il-Dong Choi; Jung-Lyoul Lee; Jae-Hun Sim; Cheol-Ho Pan; Kyungsu Kang (Biotechnology Letters, 2020)

A new species of marine algae from Korea based on morphology and molecular data: Gelidium palmatum sp. nov. (Gelidiales, Rhodophyta) - Ga Hun Boo; Kyeong Mi Kim (Algae, 2020)

Exchange protein directly activated by cAMP (Epac) 1 plays an essential role in stress-induced exercise capacity by regulating PGC-1α and fatty acid metabolism in skeletal muscle - Wai-Kin So; Hyoung Kyu Kim; Yingxian Chen; Seung Hun Jeong; Patrick Ka Kit Yeung; Billy C. K. Chow; Jin Han; Sookja K. Chung (Pflügers Archiv - European Journal of Physiology, 2020)

Anti-inflammatory activity of the extracts from Rodgersia podophylla leaves through activation of Nrf2/HO-1 pathway, and inhibition of NF-κB and MAPKs pathway in mouse macrophage cells - Ha Na Kim; Jeong Dong Kim; Su Bin Park; Ho-Jun Son; Gwang Hun Park; Hyun Ji Eo; Hyun-Seok Kim; Jin Boo Jeong (Inflammation Research, 2020)

Anti-inflammatory effect of bee venom in phthalic anhydride-induced atopic dermatitis animal model - Yu Jin Lee; Myung Jin Oh; Dong Hun Lee; Yong Sun Lee; Jiin Lee; Deok-Hyun Kim; Cheol-Hoon Choi; Min Jong Song; Ho Sueb Song; Jin Tae Hong (Inflammopharmacology, 2020)

Improvement China Point Source for Improving Bottom-Up Emission Inventory - Youjung Jang; Yungu Lee; Jinseok Kim; Younha Kim; Jung-Hun Woo (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Bacterial endosymbiont of Oligobrachia sp. (Frenulata) from an active mud volcano in the Canadian Beaufort Sea - Yung Mi Lee; Hyun-Ju Noh; Dong-Hun Lee; Jung-Hyun Kim; Young Keun Jin; Charles Paull (Polar Biology, 2019)

Synthesis and anti-endoplasmic reticulum stress activity of N-substituted-2-arylcarbonylhydrazinecarbothioamides - Hoon Choi; Wheesahng Yun; Jung-hun Lee; Seoul Jang; Sang Won Park; Dong Hwan Kim; Kyoung Pyo Seon; Jung-mi Hyun; Kwiwan Jeong; Jin-mo Ku; Tae-gyu Nam (Medicinal Chemistry Research, 2019)

Downregulated UCHL1 Accelerates Gentamicin-Induced Auditory Cell Death via Autophagy - Yeon Ju Kim; Kyung Kim; Yun Yeong Lee; Oak-Sung Choo; Jeong Hun Jang; Yun-Hoon Choung (Molecular Neurobiology, 2019)

Plant and microalgae consortium for an enhanced biodegradation of sulfamethazine - Jiu-Qiang Xiong; Byong-Hun Jeon; Sanjay P. Govindwar; Mayur B. Kurade; Swapnil M. Patil; Jung-Han Park; Ki-Hyun Kim (Environmental Science and Pollution Research, 2019)

The relationship among meteorological, agricultural, and in situ news-generated big data on droughts - Ji-Wan Lee; Chung-Gil Jung; Jee-Hun Chung; Seong-Joon Kim (Natural Hazards, 2019)

Clinicopathological and Radiological Features of Chronic Rhinosinusitis with Eosinophilic Mucin in Chungcheong Province of Korea - Soo Kyoung Park; Ki Wan Park; Ji-Hun Mo; Byoung Joon Baek; Woo Sub Shim; Hahn Jin Jung; Yong Min Kim; Ki Sang Rha (Mycopathologia, 2019)

Alteration of microRNA 340-5p and Arginase-1 Expression in Peripheral Blood Cells during Acute Ischemic Stroke - Hanna Yoo; Jinkwon Kim; Ae-Ri Lee; Ji-Min Lee; Ok-Joon Kim; Jin-Kyeoung Kim; Seung-Hun Oh (Molecular Neurobiology, 2019)

Fibroblast growth factor 21 deficiency aggravates obesity-induced hypothalamic inflammation and impairs thermogenic response - Luthfiyyah Mutsnaini; Chu-Sook Kim; Jiye Kim; Yeonsoo Joe; Hun Taeg Chung; Hye-Seon Choi; Eun Roh; Min-Seon Kim; Rina Yu (Inflammation Research, 2019)

A 90-Day Repeated Oral Dose Toxicity Study of Alismatis Rhizoma Aqueous Extract in Rats - Mu-Jin Lee; Ho-Kyung Jung; Ki-Ho Lee; Ji-Hun Jang; Mi-Ok Sim; Tea-Gyeong Seong; Byung-Kwan Ahn; Jin-Han Shon; Seong-Ho Ham; Hyun-Woo Cho; Yong-Min Kim; Sung-Jin Park; et al. (Toxicological Research, 2019)

The associations of TAC1 gene polymorphisms with major depressive disorder - Eunsoo Won; Kyu-Man Han; Aram Kim; Min-Soo Lee; Yong-Ku Kim; Hun Soo Chang; Byung-Joo Ham (Molecular & Cellular Toxicology, 2019)

Prolonged shedding of type 55 human adenovirus in immunocompetent adults with adenoviral respiratory infections - Kyungmin Huh; Inseon Kim; Jaehun Jung; Ji Eun Lee; Byung Woo Jhun; Se Hun Gu; Dong Hyun Song; Eun Young Lee; Ho Jung Jeong; Hongseok Yoo (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Concentrations of particulate matter, carbon dioxide, VOCs and risk assessment inside Korean taxis and ships - Ho-Hyun Kim; Gee-Young Park; Jeong-Hun Lee (Environmental Science and Pollution Research, 2019)

Possible impact of the diabatic heating over the Indian subcontinent on heat waves in South Korea - Maeng‐Ki Kim; Ji‐Seon Oh; Cheol‐Kyu Park; Seung‐Ki Min; Kyung‐On Boo; Jeong‐Hun Kim (International Journal of Climatology, 2019)
We investigate the impact of the diabatic heating (Q1) over the Indian subcontinent and Tibetan Plateau (TP) sensible heat on the heat waves in South Korea in July and August over a recent 42‐year period. In particular, we emphasize the role of the convective activity across the region from northeastern Pakistan to northwestern India (PWI) induced by the heat from the TP, especially over the western and eastern TP. A composite analysis indicates that the composite differences between the heat‐wave summers (HWS) and non‐heat‐wave summers (NHWS) resemble the circum‐global teleconnection (CGT) pattern, which generates a high‐pressure anomaly over the Korean Peninsula, producing favourable conditions for heat waves in South Korea. The first coupled mode of the geopotential height at 250 hPa with the daily maximum temperature (TM) for July and August in South Korea is consistent with the composite pattern, suggesting that the diabatic heating over the Indian subcontinent induces a high‐pressure anomaly over the Korean Peninsula through a CGT‐like mechanism. The regression analysis of the wind vectors in the upper troposphere also indicates that the diabatic heating over the PWI region and associated TP sensible heating generates the strong convection over the PWI region, which corresponds to the anomalous anticyclonic circulation at 250 hPa over the western TP and the cyclonic circulation at 850 hPa over the PWI region. Moreover, the correlation patterns of the 250‐hPa geopotential height with the normalized rainfall amount index (IMRI) over the PWI region and the wave activity flux pattern confirm that the strong convective activity over the PWI region contributes to the anomalous high pressure and heat waves over the Korean Peninsula.

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Association of glutathione S-transferase M1 and T1 null/present polymorphism with physical performance in the Korean population - In Wook Hwang; Kicheol Kim; Bit Na Kwon; Hyung Jun Kim; Seung Hun Han; Noo Ri Lee; Eun Ji Choi; Hyun Ik Cho; Han Jun Jin (Genes & Genomics, 2019)

Determination of Mycoplasma hyopneumoniae-Specific IgG, IgG1, and IgG2a Titers in BALB/c Mice Induced by Mineral Oil-Based Oil-in-Water Emulsion Adjuvants Prepared Using a Self-Emulsifying Drug Delivery System - Rakesh Bastola; Jo-Eun Seo; Gyubin Noh; Taekwang Keum; Ju Hun Kim; Jong Il Shin; Sooyeun Lee; Sangkil Lee (AAPS PharmSciTech, 2019)

Combined Treatment with Low-Level Laser and rhBMP-2 Promotes Differentiation and Mineralization of Osteoblastic Cells under Hypoxic Stress - Jin-Ho Heo; Jeong-Hun Choi; In-Ryoung Kim; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2018)

Physiological Characteristics and Related Biochemical Parameters of Snow Algae from King George Island, Antarctica - Bo Kyung Kim; HyoungMin Joo; Boyeon Lee; Dong-Hun Lee; In-Young Ahn; Sun-Yong Ha (Ocean Science Journal, 2018)

Cytotoxic Effect on Human Cancer Cells and Antioxidant Activity of Extracts of Codonopsis lanceolata Root using Different Solvent Fractions - Hee Ock Boo; Jeong Hun Park; Hag Hyun Kim; Soo Jeong Kwon; Sun Hee Woo (Journal of Crop Science and Biotechnology, 2018)

Size-dependent characteristics of diurnal particle concentration variation in an underground subway tunnel - Sang-Hee Woo; Jong Bum Kim; Gwi-Nam Bae; Moon Se Hwang; Gil Hun Tahk; Hwa Hyun Yoon; Soon-Bark Kwon; Duckshin Park; Se-Jin Yook (Environmental Monitoring and Assessment, 2018)

Complete mitochondrial genome of the invasive semi-aquatic mammal, nutria Myocastor coypus (Rodentia; Myocastoridae) - Do-Hun Lee; Moo-Seung Lee; Young-Chae Kim; Il Ryong Kim; Hye Kwon Kim; Dae Gwin Jeong; Jung Ro Lee; Ji Hyung Kim (Conservation Genetics Resources, 2018)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Impact of biogenic emissions on early summer ozone and fine particulate matter exposure in the Seoul Metropolitan Area of Korea - Hyeon-Kook Kim; Chang-Keun Song; Kyung Man Han; Yang Dam Eo; Chul Han Song; Rokjin Park; Sung-Chul Hong; Sang-Kyun Kim; Jung-Hun Woo (Air Quality, Atmosphere & Health, 2018)

Molecular characterization of proton beam-induced mutations in soybean using genotyping-by-sequencing - Woon Ji Kim; Jaihyunk Ryu; Juhyun Im; Sang Hun Kim; Si-Yong Kang; Jeong-Hee Lee; Sung-Hwan Jo; Bo-Keun Ha (Molecular Genetics and Genomics, 2018)

Improvement of biomass and fatty acid productivity in ocean cultivation of Tetraselmis sp. using hypersaline medium - Hanwool Park; Daewoo Jung; Jongchan Lee; Philhan Kim; Yonghee Cho; Injae Jung; Z-Hun Kim; Sang-Min Lim; Choul-Gyun Lee (Journal of Applied Phycology, 2018)

Efficient spoofing identification using baseline vector information of multiple receivers - Seong-Hun Seo; Byung-Hyun Lee; Sung-Hyuck Im; Gyu-In Jee; Kwan-Sung Kim (GPS Solutions, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Thermoresponsive and Biodegradable Amphiphilic Block Copolymers with Pendant Functional Groups - Bo Keun Lee; Jung Hyun Noh; Ji Hoon Park; Seung Hun Park; Jae Ho Kim; Se Heang Oh; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Correction to: Development of 21 polymorphic microsatellite markers for the black-banded sea krait, Laticauda semifasciata (Elapidae: Laticaudinae), and cross-species amplification for two other congeneric species - Young Se Hyun; Il-Hun Kim; Ha Yeun Song; Daesik Park; Mamoru Toda; Tein-Shun Tsai; Hye Suck An (Genes & Genomics, 2018)

Comparison of Measurements from Pressure-recording Inverted Echo Sounders and Satellite Altimetry in the North Equatorial Current Region of the Western Pacific - Chanhyung Jeon; Jae-Hun Park; Dong Guk Kim; Eung Kim; Dongchull Jeon (Ocean Science Journal, 2018)

Evaluation of Physiological Functionalities and Anti-inflammatory Activity on in vitro Cultured Adventitious Root of Platycodon grandiflorum - Hee Ock Boo; Jeong Hun Park; Hag Hyun Kim; Soo Jeong Kwon; Sun Hee Woo (Journal of Crop Science and Biotechnology, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

A Scalable High-Performance I/O System for a Numerical Weather Forecast Model on the Cubed-Sphere Grid - Junghan Kim; Young Cheol Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Beneficial Effects of Cynaroside on Cisplatin-Induced Kidney Injury In Vitro and In Vivo - Jong-Hyun Nho; Ho-Kyung Jung; Mu-Jin Lee; Ji-Hun Jang; Mi-Ok Sim; Da-Eun Jeong; Hyun-Woo Cho; Jong-Choon Kim (Toxicological Research, 2018)

Variation of temperature-dependent sound velocity in unconsolidated marine sediments: Laboratory measurements - Sora Kim; Gwang Soo Lee; Daechoul Kim; Jooyoung Hahn; Woo-Hun Ryang (Marine Georesources & Geotechnology, 2018)

Autophagy-related (ATG) 11, ATG9 and the phosphatidylinositol 3-kinase control ATG2-mediated formation of autophagosomes in Arabidopsis - Sangwoo Kang; Kwang Deok Shin; Jeong Hun Kim; Taijoon Chung (Plant Cell Reports, 2018)

Development of 21 polymorphic microsatellite markers for the black-banded sea krait, Laticauda semifasciata (Elapidae: Laticaudinae), and cross-species amplification for two other congeneric species - Young Se Hyun; Il-Hun Kim; Ha Yeun Song; Daesik Park; Mamoru Toda; Tein-Shun Tai; Hye Suck An (Genes & Genomics, 2018)

The use of cefepime as a carbapenem-sparing antibiotic for treating uncomplicated acute pyelonephritis caused by extended-spectrum β-lactamase producing Escherichia coli - Jin Woong Suh; Kyung Sook Yang; Sun Bean Kim; Jong Hun Kim; Jang Wook Sohn; Min Ja Kim; Young Kyung Yoon (Infectious Diseases, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Multi-locus phylogenetic analyses support the monophyly and the Miocene diversification of Iksookimia (Teleostei: Cypriniformes: Cobitidae) - Ye-Seul Kwan; Daemin Kim; Myeong-Hun Ko; Wan-Ok Lee; Yong-Jin Won (Systematics and Biodiversity, 2018)

Interfacial Reaction Between Ultra Low C Steel and Gas Generated from Refractory Material Used for Submerged Entry Nozzle for Continuous Casting - Joo-Hyeok Lee; Sung-Kwang Kim; Myeong-Hun Kang; Youn-Bae Kang (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Current Understanding of Stem Cell and Secretome Therapies in Liver Diseases - Dongkyu Kim; Gun-Sik Cho; Choongseong Han; Dong-Hyuk Park; Hee-Kyung Park; Dong-Hun Woo; Jong-Hoon Kim (Tissue Engineering and Regenerative Medicine, 2017)

Effect of Drug Carrier Melting Points on Drug Release of Dexamethasone-Loaded Microspheres - Ji Hoon Park; Doo Yeon Kwon; Ji Yeon Heo; Seung Hun Park; Joon Yeong Park; Bong Lee; Jae Ho Kim; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2017)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Chryseobacterium ginsengiterrae sp. nov., with Beta-Glucosidase Activity Isolated from Soil of a Ginseng Field - Jong-Hun Noh; Van-An Hoang; Yeon-Ju Kim; Jong-Pyo Kang; Deok-Chun Yang (Current Microbiology, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Novel reassortant clade 2.3.4.4 avian influenza A (H5N8) virus in a grey heron in South Korea in 2017 - Chanjin Woo; Jung-Hoon Kwon; Dong-Hun Lee; Youngsik Kim; Kwanghee Lee; Seong-Deok Jo; Ki dong Son; Jae-Ku Oem; Seung-Jun Wang; Yongkwan Kim; Jeonghwa Shin; Chang-Seon Song; et al. (Archives of Virology, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Neuronal nitric oxide synthase modulation of intracellular Ca2+ handling overrides fatty acid potentiation of cardiac inotropy in hypertensive rats - Chun Li Jin; Ming Zhe Yin; Jin Chul Paeng; Seunggyun Ha; Jeong Hoon Lee; Peng Jin; Chun Zi Jin; Zai Hao Zhao; Yue Wang; Keon Wook Kang; Chae Hun Leem; Jong-Wan Park; et al. (Pflügers Archiv - European Journal of Physiology, 2017)

Phytochemical profile and angiotensin I converting enzyme (ACE) inhibitory activity of Limonium michelsonii Lincz - Janar Jenis; Jeong Yoon Kim; Zia Uddin; Yeong Hun Song; Hyeong-Hwan Lee; Ki Hun Park (Journal of Natural Medicines, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Stability of Coatings on Sulfide Minerals in Acidic and Low-Temperature Environments - Chan-Ung Kang; Byong-Hun Jeon; Rahul Kumar; Seong-Sook Park; Hyun-Sung Park; Sun-Joon Kim (Mine Water and the Environment, 2017)

Recombinant human bone morphogenic protein-2 Induces the Differentiation and Mineralization of Osteoblastic Cells Under Hypoxic Conditions via Activation of Protein Kinase D and p38 Mitogen-Activated Protein Kinase Signaling Pathways - Woo-Hun Ha; Hwa-Sik Seong; Na-Rae Choi; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2017)

A comparative study on generating simulated Landsat NDVI images using data fusion and regression method—the case of the Korean Peninsula - Mi Hee Lee; Soo Bong Lee; Yang Dam Eo; Sun Woong Kim; Jung-Hun Woo; Soo Hee Han (Environmental Monitoring and Assessment, 2017)

Functional characterization of cytochrome P450 monooxygenases in the cereal head blight fungus F usarium graminearum - Ji Young Shin; Duc‐Cuong Bui; Yoonji Lee; Hyejin Nam; Soyun Jung; Miao Fang; Jin‐Cheol Kim; Theresa Lee; Hun Kim; Gyung Ja Choi; Hokyoung Son; Yin‐Won Lee (Environmental Microbiology, 2017)
Summary Fusarium graminearum is a prominent plant pathogenic fungus causing Fusarium head blight in major cereal crops worldwide. To understand the molecular mechanisms underlying fungal development and virulence, large collections of F. graminearum mutants have been constructed. Cytochrome P450 monooxygenases (P450s) are widely distributed in organisms and are involved in a diverse array of molecular/metabolic processes; however, no systematic functional analysis of P450s has been attempted in filamentous fungi. In this study, we constructed a genome‐wide deletion mutant set covering 102 P450s and analyzed these mutants for changes in 38 phenotypic categories, including fungal development, stress responses and responses to several xenobiotics, to build a comprehensive phenotypic dataset. Most P450 mutants showing defective phenotypes were impaired in a single phenotypic trait, demonstrating that our mutant library is a good genetic resource for further fungal genetic studies. In particular, we identified novel P450s specifically involved in virulence (5) and both asexual (1) and sexual development (2). Most P450s seem to play redundant roles in the degradation of xenobiotics in F. graminearum . This study is the first phenome‐based functional analysis of P450s, and it provides a valuable genetic resource for further basic and applied biological research in filamentous fungi and other plant pathogens.

Simulations of the Population Dynamics of Jellyfish Polyps Living on Artificial Substrates in Coastal Areas - Hong Sung Jin; Dongyeob Han; Jung-Hun Kim; Hyun-Jae Shin; Yang Ho Yoon; Chang-hoon Han (Thalassas: An International Journal of Marine Sciences, 2017)

Autophagic flux analysis of Arabidopsis seedlings exposed to salt stress - Hyera Jung; Jeong Hun Kim; Kwang Deok Shin; Jimi Kim; Han Nim Lee; Taijoon Chung (Journal of Plant Biology, 2017)

Heavy metal stabilization in contaminated soil by treatment with calcined cockle shell - Mohammad Nazrul Islam; Golam Taki; Xuan Phuc Nguyen; Young-Tae Jo; Jun Kim; Jeong-Hun Park (Environmental Science and Pollution Research, 2017)

Significant association of the GABRP polymorphisms with ulcerative colitis patients - Hun Soo Kim; Eun Heui Jin; Ji-Su Mo; Soo-Cheon Chae (Genes & Genomics, 2017)

In silico study on Arabidopsis BAG gene expression in response to environmental stresses - Ganesh M. Nawkar; Punyakishore Maibam; Joung Hun Park; Su Gyeong Woo; Cha Young Kim; Sang Yeol Lee; Chang Ho Kang (Protoplasma, 2017)

Long-term evaluation of the BMPs scenarios in reducing nutrient surface loads from paddy rice cultivation in Korea using the CREAMS-PADDY model - Inhong Song; Jung-Hun Song; Jeong Hoon Ryu; Kyeung Kim; Jeong-Ryeol Jang; Moon Seong Kang (Paddy and Water Environment, 2017)

Distinguishing tendon and ligament fibroblasts based on 1H nuclear magnetic resonance spectroscopy - Hun Yeong Ban; Ji Won Shin; Song-I Chun; Yun Gyeong Kang; Yanru Wu; Ji Eun Kim; Eun Jin Lee; Mi Jin Kim; Chi-Woong Mun; Jung-Woog Shin (Tissue Engineering and Regenerative Medicine, 2016)

Age determination and growth rate of Mactra chinensis (Bivalvia: Mactridae) by external rings and chondrophore growth bands - Jung Yeon Kim; Jong Hun Na; Chul-Woong Oh (Ocean Science Journal, 2016)

Human chorionic gonadotropin (hCG) sub-chronic administration mediated MMP-9 activities and cytokine association deteriorate experimental autoimmune encephalomyelitis (EAE) condition in mice model - Joon-Seung Han; Khandoker Asiqur Rahaman; Ji-Eun Seo; Mahbub Hasan; Kyung-Tae Lee; Hophil Min; Kang Mi Lee; Ju-Hyung Park; Ho Jun Kim; Ki Hun Kim; Junghyun Son; Jaeick Lee; et al. (Journal of Pharmaceutical Investigation, 2016)

Geophysical evidence and inferred triggering factors of submarine landslides on the western continental margin of the Ulleung Basin, East Sea - Deniz Cukur; Seong-Pil Kim; Gee-Soo Kong; Jang-Jun Bahk; Senay Horozal; In-Kwon Um; Gwang-Soo Lee; Tae-Soo Chang; Hun-Jun Ha; David Völker; Jung-Ki Kim (Geo-Marine Letters, 2016)

Paddy Field Modelling System For Water Quality Management - Jung‐Hun Song; Jeong Hoon Ryu; Jihoon Park; Sang Min Jun; Inhong Song; Jeongryeol Jang; Sang Min Kim; Moon Seong Kang (Irrigation and Drainage, 2016)
The objective of this study was to develop a paddy field modelling system for predicting pollutant (nutrient) loads and evaluating various best management practices (BMPs) on paddy fields. The system consists of a pre‐processing component, the CREAMS‐PADDY (Chemicals, Runoff, and Erosion from Agricultural Management Systems for PADDY) model, and a post‐processing component. The CREAMS‐PADDY was selected as the core model. The pre‐processing component included manipulation of meteorological data, management of input parameters such as spatial characteristics and farming methods, batch running, and implementing various scenarios. The post‐processing component contained visualization of water and nutrient balance components and statistical analyses for calibration, validation and application. To evaluate the applicability of the developed system, reduction effects on water control methods in paddy fields were simulated. Model parameters related to hydrology and water quality were calibrated and validated by comparing model predictions with field data collected over 2 years. The simulation results indicated that reducing nutrient loss through surface drainage by water‐saving irrigation and raising drainage outlet heights could protect downstream water quality. The simulation system will be a useful tool for planning BMPs to reduce nutrient loads from paddy fields in various regions including Korea. Copyright © 2016 John Wiley & Sons, Ltd.

Cardiac inotropy, lusitropy, and Ca2+ handling with major metabolic substrates in rat heart - Zai Hao Zhao; Jae Boum Youm; Yue Wang; Jeong Hoon Lee; Jae Hwi Sung; Joon-Chul Kim; Sun Hee Woo; Chae Hun Leem; Sung Joon Kim; Lan Cui; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2016)

Inhibition of pyrite oxidation by surface coating: a long-term field study - Chan-Ung Kang; Byong-Hun Jeon; Seong-Sook Park; Jin-Soo Kang; Kang-Ho Kim; Dong-Kwan Kim; Ui-Kyu Choi; Sun-Joon Kim (Environmental Geochemistry and Health, 2016)

Erratum to: The continuous performance test (rCPT) for mice: a novel operant touchscreen test of attentional function - Chi Hun Kim; Martha Hvoslef-Eide; Simon R. O. Nilsson; Mark R. Johnson; Bronwen R. Herbert; Trevor W. Robbins; Lisa M. Saksida; Timothy J. Bussey; Adam C. Mar (Psychopharmacology, 2016)

Genomic structure, expression and association study of the porcine FSD2 - Kyu-Sang Lim; Kyung-Tai Lee; Si-Woo Lee; Han-Ha Chai; Gulwon Jang; Ki-Chang Hong; Tae-Hun Kim (Molecular Biology Reports, 2016)

Mitochondria-targeted DsRed2 protein expression during the early stage of bovine somatic cell nuclear transfer embryo development - Hyo-Jin Park; Sung-Hun Min; Hoonsung Choi; Junghyung Park; Sun-Uk Kim; Seunghoon Lee; Sang-Rae Lee; Il-Keun Kong; Kyu-Tae Chang; Deog-Bon Koo; Dong-Seok Lee (In Vitro Cellular & Developmental Biology - Animal, 2016)

RNAi-mediated Soybean mosaic virus (SMV) resistance of a Korean Soybean cultivar - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Hyun Hee Im; Dong Hee Lee; Kook-Hyung Kim; Jai-Heon Lee; Doh-Hoon Kim; Hong Kyu Choi; Ho Won Jung; Young-Soo Chung (Plant Biotechnology Reports, 2016)

Use of nonhuman primates for the development of bioengineered female reproductive organs - Jun-Won Yun; Yoon Young Kim; Jae Hun Ahn; Byeong-Cheol Kang; Seung-Yup Ku (Tissue Engineering and Regenerative Medicine, 2016)

Predicting chlorophyll- a using Landsat 8 OLI sensor data and the non-linear RANSAC method – a case study of Nakdong River, South Korea - Hyeong Hun Kim; Byoung Chul Ko; Jae Yeal Nam (International Journal of Remote Sensing, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Genetic segregation and differentiation of a common subtidal alga Pterocladia lucida (Gelidiales, Rhodophyta) between Australia and New Zealand - Ga Hun Boo; Wendy A. Nelson; Maren Preuss; Jung Yeon Kim; Sung Min Boo (Journal of Applied Phycology, 2016)

Condensin I and II behaviour in interphase nuclei and cells undergoing premature chromosome condensation - Tao Zhang; James R. Paulson; Muhammed Bakhrebah; Ji Hun Kim; Cameron Nowell; Paul Kalitsis; Damien F. Hudson (Chromosome Research, 2016)

Population structure of the Korean gizzard shad, Konosirus punctatus (Clupeiformes, Clupeidae) using multivariate morphometric analysis - Se Hun Myoung; Jin-Koo Kim (Ocean Science Journal, 2016)

Behavior, PET and histology in novel regimen of MPTP marmoset model of Parkinson’s disease for long-term stem cell therapy - Jun-Won Yun; Jae-Bum Ahn; Euna Kwon; Jae Hun Ahn; Hyung Woo Park; Hwon Heo; Jin-Sung Park; Hyeonjin Kim; Sun Ha Paek; Byeong-Cheol Kang (Tissue Engineering and Regenerative Medicine, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Umbilical cord mesenchymal stem cell-conditioned media prevent muscle atrophy by suppressing muscle atrophy-related proteins and ROS generation - Chan-Mi Park; Mi Jin Kim; Sun-Mi Kim; Jin-Ho Park; Z-Hun Kim; Yong-Soo Choi (In Vitro Cellular & Developmental Biology - Animal, 2016)

A three-dimensional hierarchical scaffold fabricated by a combined rapid prototyping technique and electrospinning process to expand hematopoietic stem/progenitor cells - Yun Gyeong Kang; Ji Won Shin; So Hee Park; Young Mi Kim; Seo Rin Gu; Yanru Wu; Hun Yeong Ban; Jung-Woog Shin (Biotechnology Letters, 2016)

Erratum to: The role of the dorsal hippocampus in two versions of the touchscreen automated paired associates learning (PAL) task for mice - Chi Hun Kim; Christopher J. Heath; Brianne A. Kent; Alexa E. Horner; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

Risk of Fungal Endophthalmitis Associated with Cataract Surgery: A Mini-Review - Tonya C. Smith; Russell J. Benefield; Jong Hun Kim (Mycopathologia, 2015)

Development of liquid chromatography tandem mass spectrometry method for determination of spironolactone in human plasma: application to a bioequivalence study of Daewon Spiracton tablet® (spironolactone 50 mg) - Jeong-Hun Lee; Tae-Gil An; Su Jung Kim; Wang-Seob Shim; Kyung-Tae Lee (Journal of Pharmaceutical Investigation, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Distribution and long-term trends in various fog types over South Korea - Miloslav Belorid; Chong Bum Lee; Jea-Chul Kim; Tae-Hun Cheon (Theoretical and Applied Climatology, 2015)

The continuous performance test (rCPT) for mice: a novel operant touchscreen test of attentional function - Chi Hun Kim; Martha Hvoslef-Eide; Simon R. O. Nilsson; Mark R. Johnson; Bronwen R. Herbert; Trevor W. Robbins; Lisa M. Saksida; Timothy J. Bussey; Adam C. Mar (Psychopharmacology, 2015)

Trial-unique, delayed nonmatching-to-location (TUNL) touchscreen testing for mice: sensitivity to dorsal hippocampal dysfunction - Chi Hun Kim; Carola Romberg; Martha Hvoslef-Eide; Charlotte A. Oomen; Adam C. Mar; Christopher J. Heath; Andrée-Anne Berthiaume; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

The role of the dorsal hippocampus in two versions of the touchscreen automated paired associates learning (PAL) task for mice - Chi Hun Kim; Christopher J. Heath; Brianne A. Kent; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

Removal of Iopromide and Its Intermediates from Ozone-Treated Water Using Granular Activated Carbon - Yong-Tae Ahn; Dong-Wan Cho; Akhil N. Kabra; Min-Kyu Ji; Yeojoon Yoon; Jaewon Choi; Il-Hwan Choi; Joon-Wun Kang; Jung Rae Kim; Byong-Hun Jeon (Water, Air, & Soil Pollution, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Algal biomass and biodiesel production by utilizing the nutrients dissolved in seawater using semi-permeable membrane photobioreactors - Z-Hun Kim; Hanwool Park; Young-Jin Ryu; Dong-Woo Shin; Seong-Joo Hong; Hai-Linh Tran; Sang-Min Lim; Choul-Gyun Lee (Journal of Applied Phycology, 2015)

A MALDI-MS-based quantitative targeted glycomics (MALDI-QTaG) for total N-glycan analysis - Kyoung-Jin Kim; Yoon-Woo Kim; Cheol-Hwan Hwang; Han-Gyu Park; Yung-Hun Yang; Miyoung Koo; Yun-Gon Kim (Biotechnology Letters, 2015)

Comparison of the toxicity of aluminum oxide nanorods with different aspect ratio - Eun-Jung Park; Gwang-Hee Lee; Jae-hun Shim; Myung-Haing Cho; Byoung-Seok Lee; Yong-Bum Kim; Jae-Ho Kim; Younghun Kim; Dong-Wan Kim (Archives of Toxicology, 2015)

Raloxifene inhibits cloned Kv4.3 channels in an estrogen receptor-independent manner - Yun Ju Chae; Dae Hun Kim; Hong Joon Lee; Ki-Wug Sung; Oh-Joo Kwon; Sang June Hahn (Pflügers Archiv - European Journal of Physiology, 2015)

Toxic metal content in 52 frequently prescribed herbal medicines on the Korean market - Donggyu Kim; Kwang-Ho Hwang; Mokyoung Lee; Jung-Hun Kim; Kweon Jung; Seung-Kook Park (Food Additives & Contaminants Part B-Surveillance, 2015)

Reduction of Nitrate in Groundwater by Fe(0)/Magnetite Nanoparticles Entrapped in Ca-Alginate Beads - Dong-Wan Cho; Hocheol Song; Bokseong Kim; Franklin W. Schwartz; Byong-Hun Jeon (Water, Air, & Soil Pollution, 2015)

Predisposing roles of paraoxonase-1 genetic variants in Korean ischemic stroke patients - Yunkyung Cho; Jung Oh Kim; Young Joo Jeon; Gun Ho Choi; Jee Soo Shin; Sung Hwan Cho; Seung Hun Oh; In Bo Han; Byoung Soo Shin; Ok Joon Kim; Nam Keun Kim (Genes & Genomics, 2015)

Generation of high resolution sea surface temperature using multi-satellite data for operational oceanography - Chan-Su Yang; Sun-Hwa Kim; Kazuo Ouchi; Ji-Hun Back (Acta Oceanologica Sinica, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Development of an advanced external fixation device for rat femur defect - Deuk Young Oh; Jang-Youn Choi; Ki Joo Kim; Jung Hun Park; Dong-Woo Cho; Jong Won Rhie (Tissue Engineering and Regenerative Medicine, 2015)

Effects of reduced vertical mixing under sea ice on Atlantic meridional overturning circulation (AMOC) in a global ice-ocean model - Sang Yeob Kim; Ho Jin Lee; Jae-Hun Park; Young Ho Kim (Ocean Science Journal, 2015)

Development of the Operational Oceanographic System of Korea - Kwang-Soon Park; Ki-Young Heo; Kicheon Jun; Jae-Il Kwon; Jinah Kim; Jin-Yong Choi; Kyoung-Ho Cho; Byoung-Ju Choi; Seung-Nam Seo; Young Ho Kim; Sung-Dae Kim; Chan-Su Yang; et al. (Ocean Science Journal, 2015)

Prognostic value of hepatoma-derived growth factor-related protein 3 (HRP-3) methylation in non-small cell lung cancer - Young Hun Kim; Won Kee Lee; Jae Yong Park; Dong Sun Kim (Genes & Genomics, 2015)

Serology and clinical relevance of Corynebacterium pseudotuberculosis in native Korean goats (Capra hircus coreanae) - Byeong Yeal Jung; Seung-Hun Lee; Ha-Young Kim; Jae-Won Byun; Dong-Ho Shin; Daekeun Kim; Dongmi Kwak (Tropical Animal Health and Production, 2015)

Systemic Review of Published Literature on Candida Infection Following Total Hip Arthroplasty - Seung-Ju Kim; Jeungmin Huh; Robert Odrobina; Jong Hun Kim (Mycopathologia, 2015)

Genetic characterization of porcine epidemic diarrhea virus in Korea from 1998 to 2013 - Seong-Hee Kim; Jung-Min Lee; Jongsun Jung; In-Joong Kim; Bang-Hun Hyun; Hyun-Il Kim; Choi-Kyu Park; Jae-Ku Oem; Yeon-Hee Kim; Myoung-Heon Lee; Kyoung-Ki Lee (Archives of Virology, 2015)

The AtLRK10L1.2, Arabidopsis ortholog of wheat LRK10, is involved in ABA-mediated signaling and drought resistance - Chae Woo Lim; Seung Hwan Yang; Ki Hun Shin; Sung Chul Lee; Sang Hyon Kim (Plant Cell Reports, 2015)

Alternative splicing of mini-exons in the Arabidopsis leaf rust receptor-like kinase LRK10 genes affects subcellular localisation - Ki Hun Shin; Seung Hwan Yang; Jun Yong Lee; Che Woo Lim; Sung Chul Lee; John W. S. Brown; Sang Hyon Kim (Plant Cell Reports, 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

Deinococcus radioresistens sp. nov., a UV and gamma radiation-resistant bacterium isolated from mountain soil - Sathiyaraj Srinivasan; Jae-Jin Lee; Sang-Yong Lim; Min-Ho Joe; Seong-Hun Im; Myung Kyum Kim (Antonie van Leeuwenhoek, 2015)

Mercury contamination and exposure assessment of fishery products in Korea - Hye-Ran Yang; Na-Young Kim; Lae-Hong Hwang; Ju-Sung Park; Jung-Hun Kim (Food Additives & Contaminants Part B-Surveillance, 2015)

A comparison of the effects of repetitive transcranial magnetic stimulation (rTMS) by number of stimulation sessions on hemispatial neglect in chronic stroke patients - Yong Kyun Kim; Jae Hwan Jung; Sung Hun Shin (Experimental Brain Research, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Menopause and Blood Mercury Levels: The Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2011 - Jin-Sung Yuk; Jung Hun Lee; Jin-Dong Jeon; Tai June Kim; Myung-Hwa Lee; Won I. Park (Biological Trace Element Research, 2014)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Polycyclic aromatic hydrocarbons exposure in residents living near a cement factory with kilns - YongMin Cho; Geun-Bae Kim; Yong-Sung Cho; Min Seok Choi; Seung-Hun Ryu; Seung Hyun Choi; Young-Koo Park; Jae Wook Choi (International Archives of Occupational and Environmental Health, 2014)

Toxicity of atrazine and its bioaccumulation and biodegradation in a green microalga, Chlamydomonas mexicana - Akhil N. Kabra; Min-Kyu Ji; Jaewon Choi; Jung Rae Kim; Sanjay P. Govindwar; Byong-Hun Jeon (Environmental Science and Pollution Research, 2014)

Posaconazole Salvage Treatment for Invasive Fungal Infection - Jong Hun Kim; Kali Williams (Mycopathologia, 2014)

Hypoxia-mediated retinal neovascularization and vascular leakage in diabetic retina is suppressed by HIF-1α destabilization by SH-1242 and SH-1280, novel hsp90 inhibitors - Dong Hyun Jo; Hongchan An; Dong-Jo Chang; Yi-Yong Baek; Chang Sik Cho; Hyoung Oh Jun; So-Jung Park; Jin Hyoung Kim; Ho-Young Lee; Kyu-Won Kim; Jeewoo Lee; Hyun-Ju Park; et al. (Journal of Molecular Medicine, 2014)

Genetic diversity and population structure of the gizzard shad, Konosirus punctatus (Clupeidae, Pisces), in Korean waters based on mitochondrial DNA control region sequences - Se Hun Myoung; Jin-Koo Kim (Genes & Genomics, 2014)

2-Cyclopropylimino-3-Methyl-1,3-Thiazoline Hydrochloride Inhibits Microglial Activation by Suppression of Nuclear Factor-Kappa B and Mitogen-Activated Protein Kinase Signaling - Eun-A Kim; Jiyoung Choi; A. Reum Han; Chang Hun Cho; Soo Young Choi; Jee-Yin Ahn; Sung-Woo Cho (Journal of Neuroimmune Pharmacology, 2014)

Geoacoustic model at the DH-1 long-core site in the Korean continental margin of the East Sea - Woo-Hun Ryang; Yi-Kyun Kwon; Seong-Pil Kim; Dae-Choul Kim; Jin-Hyuk Choi (Geosciences Journal, 2014)

Blood levels of cadmium and lead in residents near abandoned metal mine areas in Korea - Dong-UK Park; Dae-Seon Kim; Seung-Do Yu; Kyeong-Min Lee; Seung-Hun Ryu; Soo-Geun Kim; Won-Ho Yang; Doo-Yong. Park; Yeong-Seoub Hong; Jung-Duck Park; Byung-Kook Lee; Jai-Dong Moon; et al. (Environmental Monitoring and Assessment, 2014)

Assessment of natural and calcined starfish for the amelioration of acidic soil - Deok Hyun Moon; Jae E. Yang; Kyung Hoon Cheong; Agamemnon Koutsospyros; Jeong-Hun Park; Kyoung Jae Lim; Sung Chul Kim; Rog-Young Kim; Yong Sik Ok (Environmental Science and Pollution Research, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

UBL1 of F usarium verticillioides links the N ‐end rule pathway to extracellular sensing and plant pathogenesis - John B. Ridenour; Jonathon E. Smith; Robert L. Hirsch; Peter Horevaj; Hun Kim; Sandeep Sharma; Burton H. Bluhm (Environmental Microbiology, 2014)
Summary F usarium verticillioides produces fumonisin mycotoxins during colonization of maize. Currently, molecular mechanisms underlying responsiveness of F . verticillioides to extracellular cues during pathogenesis are poorly understood. In this study, insertional mutants were created and screened to identify genes involved in responses to extracellular starch. In one mutant, the restriction enzyme‐mediated integration cassette disrupted a gene ( UBL1 ) encoding a UBR ‐Box/ RING domain E 3 ubiquitin ligase involved in the N ‐end rule pathway. Disruption of UBL1 in F . verticillioides (Δ ubl1 ) influenced conidiation, hyphal morphology, pigmentation and amylolysis. Disruption of UBL1 also impaired kernel colonization, but the ratio of fumonisin B 1 per unit growth was not significantly reduced. The inability of a Δ ubl1 mutant to recognize an N ‐end rule degron confirmed involvement of UBL1 in the N ‐end rule pathway. Additionally, U bl1 physically interacted with two G protein α subunits of F . verticillioides , thus implicating UBL1 in G protein‐mediated sensing of the external environment. Furthermore, deletion of the UBL1 orthologue in F . graminearum reduced virulence on wheat and maize, thus indicating that UBL1 has a broader role in virulence among F usarium species. This study provides the first linkage between the N ‐end rule pathway and fungal pathogenesis, and illustrates a new mechanism through which fungi respond to the external environment.

CD39-mediated effect of human bone marrow-derived mesenchymal stem cells on the human Th17 cell function - Jong Joo Lee; Hyun Jeong Jeong; Mee Kum Kim; Won Ryang Wee; Won Woo Lee; Seung U. Kim; Changmin Sung; Yung Hun Yang (Purinergic Signalling, 2014)

Ginsenoside Re Rescues Methamphetamine-Induced Oxidative Damage, Mitochondrial Dysfunction, Microglial Activation, and Dopaminergic Degeneration by Inhibiting the Protein Kinase Cδ Gene - Eun-Joo Shin; Seung Woo Shin; Thuy-Ty Lan Nguyen; Dae Hun Park; Myung-Bok Wie; Choon-Gon Jang; Seung-Yeol Nah; Byung Wook Yang; Sung Kwon Ko; Toshitaka Nabeshima; Hyoung-Chun Kim (Molecular Neurobiology, 2014)

Molecular evidence for hybrid origin of Aster chusanensis, an endemic species of Ulleungdo, Korea - Hyunchur Shin; Sang-Hun Oh; Yongseok Lim; Chang-Woo Hyun; Seong-Hyun Cho; Yong-In Kim; Young-Dong Kim (Journal of Plant Biology, 2014)

Taxonomy and distribution of selected species of the agarophyte genus Gelidium (Gelidiales, Rhodophyta) - Ga Hun Boo; Kyeong Mi Kim; Wendy A. Nelson; Rafael Riosmena-Rodríguez; Kyung Ju Yoon; Sung Min Boo (Journal of Applied Phycology, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

Mitochondrial cox1 and cob sequence diversities in Gelidium vagum (Gelidiales, Rhodophyta) in Korea - Kyung Ju Yoon; Kyeong Mi Kim; Ga Hun Boo; Kathy Ann Miller; Sung Min Boo (Algae, 2014)

Two new records of Valenciennea helsdingenii (Perciformes: Gobiidae) and Chromis margaritifer (Perciformes: Pomacentridae) from Jeju Island, Korea - Jung-Goo Myoung; Se Hun Myoung; In-Seo Hwang; Byung-il Kim; Jin-Koo Kim (Ocean Science Journal, 2014)

Development and characterization of polymorphic microsatellite marker for an endangered freshwater fish in Korea, Gobiobotia brevibarba - Keun-Sik Kim; Hyo-Ryeon Lee; Sang-Yong Park; Myeong Hun Ko; In-Chul Bang (Conservation Genetics Resources, 2014)

Does size difference in allogeneic cancellous bone granules loaded with differentiated autologous cultured osteoblasts affect osteogenic potential? - Sang-Uk Lee; Yang-Guk Chung; Seok-Jung Kim; Il-Hoan Oh; Yong-Sik Kim; Sung-Hun Ju (Cell and Tissue Research, 2014)

Combination of percutaneous radiofrequency ablation and systemic chemotherapy are effective treatment modalities for metachronous liver metastases from gastric cancer - Jun-Eul Hwang; Seung-Hun Kim; Joon Jin; Ji-Yun Hong; Min-Jee Kim; Sung-Hoon Jung; Hyun-Jeong Shim; Woo-kyun Bae; Eu-Chang Hwang; Jin-Woong Kim; Sang-Soo Shin; Oh Jeong; et al. (Clinical & Experimental Metastasis, 2014)

The effects of functionalized titanium with alendronate and bone morphogenic protein-2 for improving osteoblast activity - Sung Eun Kim; Young-Pil Yun; Kyeongsoon Park; Hak-Jun Kim; Deok-Won Lee; Jung Wook Kim; Dae Hyeok Yang; Dong Hun Suh (Tissue Engineering and Regenerative Medicine, 2013)

Erratum to: Rice cell wall polysaccharides: Structure and biosynthesis - Chang-Sik Oh; Hun Kim; Chanhui Lee (Journal of Plant Biology, 2013)

Polymorphism analysis of tyrosine hydroxylase (TH) in military working dogs - Jungwoo Eo; Bong-Hwan Choi; Yi-Deun Jung; Yun-Jeong Kwon; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2013)

Monitoring by LC-MS/MS of 48 compounds of sildenafil, tadalafil, vardenafil and their analogues in illicit health food products in the Korean market advertised as enhancing male sexual performance - Ji Hyune Lee; Nam Sook Kim; Kyoung Moon Han; Sung Hun Kim; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants: Part A, 2013)

Retinyl retinoate, a retinoid derivative improves acne vulgaris in double-blind, vehicle-controlled clinical study - Bora Kim; Hyunjung Kim; Jin Eun Kim; Seung Hun Lee (Tissue Engineering and Regenerative Medicine, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Rice cell wall polysaccharides: Structure and biosynthesis - Chang-Sik Oh; Hun Kim; Chanhui Lee (Journal of Plant Biology, 2013)

Mitochondrial UQCRB regulates VEGFR2 signaling in endothelial cells - Hye Jin Jung; Yonghyo Kim; Junghwa Chang; Sang Won Kang; Jeong Hun Kim; Ho Jeong Kwon (Journal of Molecular Medicine, 2013)

Geoacoustic model of the transverse acoustic variability experiment area in the northern East China Sea - Woo-Hun Ryang; Seong-Pil Kim; Seongil Kim; Dae-Choul Kim (Geosciences Journal, 2013)

Porcine insulin-like growth factor 1 (IGF1) gene polymorphisms are associated with body size variation - Pengxia Niu; Sang-Wook Kim; Bong-Hwan Choi; Tae-Hun Kim; Jong-Joo Kim; Kwan-Suk Kim (Genes & Genomics, 2013)

Molecular and immunohistochemical characterization of the chitinase gene from Pieris rapae granulovirus - Seunghan Oh; Dong Hyun Kim; Bharat Bhusan Patnaik; Yong Hun Jo; Mi Young Noh; Hyo Jeong Lee; Kwang Ho Lee; Kwang Ho Yoon; Wan-Jong Kim; Ju Young Noh; Heon Cheon Jeong; Yong Seok Lee; et al. (Archives of Virology, 2013)

CoCl2 induces apoptosis through the mitochondria- and death receptor-mediated pathway in the mouse embryonic stem cells - Jin-Ha Lee; Seong-Ho Choi; Min-Woo Baek; Mi-Hwa Kim; Heong-Jun Kim; Sun-Hun Kim; Sang-Jin Oh; Hong-Ju Park; Won-Jae Kim; Ji-Yeon Jung (Molecular and Cellular Biochemistry, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Carpesium abrotanoides extract inhibits cyclooxygenase-2 expression induced by toll-like receptor agonists - Do-Won Jeong; Eun-Kyeong Lee; Chung-Ho Lee; Se Jin Lim; Gyo-Jeong Gu; Ji Hun Paek; Songmun Kim; Soon Sung Lim; Hyung-Sun Youn (Toxicology and Environmental Health Sciences, 2013)

Genome-wide copy number variation in Hanwoo, Black Angus, and Holstein cattle - Jung-Woo Choi; Kyung-Tai Lee; Xiaoping Liao; Paul Stothard; Hyeon-Seung An; Sungmin Ahn; Seunghwan Lee; Sung-Yeoun Lee; Stephen S. Moore; Tae-Hun Kim (Mammalian Genome, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

Cerebellar Atrophy in Patients with Subcortical-Type Vascular Cognitive Impairment - Cindy W. Yoon; Sang Won Seo; Jun-Sung Park; Ki-Chang Kwak; Uicheul Yoon; Mee Kyung Suh; Geon Ha Kim; Ji Soo Shin; Chi Hun Kim; Young Noh; Hanna Cho; Min-Jeong Kim; et al. (The Cerebellum, 2013)

Saponins from soy bean and mung bean inhibit the antigen specific activation of helper T cells by blocking cell cycle progression - Suk Jun Lee; Joonbeom Bae; Sunhee Kim; Seonah Jeong; Chang-Yong Choi; Sang-Pil Choi; Hyun-Sook Kim; Woon-Won Jung; Jee-Young Imm; Sae Hun Kim; Taehoon Chun (Biotechnology Letters, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Variability of the Dokdo Abyssal Current observed in the Ulleung Interplain Gap of the East/Japan Sea - Yun-Bae Kim; Kyung-Il Chang; Jae-Hun Park; Jong Jin Park (Acta Oceanologica Sinica, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Geochemistry and S r – N d – P b isotopic constraints on the petrogenesis of C enozoic lavas from the P ali A ike and M orro C hico area (52° S ), southern P atagonia, S outh A merica - Mi Kyung Choo; Mi Jung Lee; Jong Ik Lee; Kyu Han Kim; Kye‐Hun Park (Island Arc, 2012)
Geochemical and isotopic analyses ( S r – N d – P b ) of late M iocene to Q uaternary plateau lavas from the P ali A ike and M orro C hico areas (52° S ) were undertaken to constrain the melting processes and mantle sources that contributed to magma generation and the geodynamic evolution of southernmost P atagonia, S outh A merica. The P ali A ike and M orro C hico lavas are alkaline ( P ali A ike, 45–49 wt.% S i O 2 ; 4.3–5.9 wt.% Na 2 O + K 2 O ) and subalkaline ( M orro C hico, 50.5–50.8 wt.% SiO 2 ; 4.0–4.4 wt.% Na 2 O + K 2 O ), relatively primitive ( P ali A ike, 9.5–13.7 wt.% M g O ; M orro C hico, 7.6–8.8 wt.% M g O ) mafic volcanic rocks that have typical intraplate ocean island basalt‐like signatures. Incompatible trace element ratios and isotopic ratios of the P ali A ike and M orro C hico lavas differ from those of the majority of N eogene southern P atagonian slab window lavas in showing more enriched characteristics and are similar to high‐μ ( HIMU )‐like basalts. The rare earth element ( REE ) modeling to constrain mantle melting percentages suggests that these lavas were produced by low degrees of partial melting (1.0–2.0% for P ali A ike lavas and about 2.6–2.7% for M orro C hico lavas) of a garnet lherzolite mantle source. The major systematic variations of S r– N d– P b isotopes in southern P atagonian lavas are related to geographic location. The P ali A ike and M orro C hico lavas from the southernmost part of P atagonia have lower 87 Sr / 86 Sr and higher 143 Nd / 144 Nd and 206 P b/ 204 P b ratios, relative to most of the southern P atagonian lavas erupted north of 49.5° S , pointing to a HIMU ‐like signature. An isotopically depleted and HIMU ‐like asthenospheric domain may have been the main source of magmas in the southernmost part of P atagonia (e.g. P ali A ike, M orro C hico, and C amusu A ike volcanic field), suggesting the presence of a major discontinuity in the isotopic composition of the asthenosphere in southern P atagonia. On the basis of geochemical and isotope data and the available geological and geotectonic reconstructions, a link between the HIMU asthenospheric mantle domain beneath southernmost Patagonia and the HIMU mega‐province of the southwestern P acific O cean is proposed.

Biological control potentials of insect-parasitic nematode Rhabditis blumi (Nematoda: Rhabditida) for major cruciferous vegetable insect pests - Hae Woong Park; Hyeong Hwan Kim; Sung Hun Youn; Taek Su Shin; Anwar L. Bilgrami; Myoung Rae Cho; Chul Soo Shin (Applied Entomology and Zoology, 2012)

Effects of substrate concentrations on performance of serially connected microbial fuel cells (MFCs) operated in a continuous mode - Anup Gurung; Jungrae Kim; Sokhee Jung; Byong-Hun Jeon; Jae E. Yang; Sang-Eun Oh (Biotechnology Letters, 2012)

Association of kinase insert domain receptor (KDR -604, 1192, and 1719) polymorphisms with cerebral white matter lesions - Su Yeoun Kim; Young Joo Jeon; Seung Hun Oh; Hyun Sook Kim; Ok Joon Kim; Doyeun Oh; Mingull Jeung; Byung Soo Shin; Young Seok Park; Nam Keun Kim (Genes & Genomics, 2012)

Edible Seaweed, Eisenia bicyclis, Protects Retinal Ganglion Cells Death Caused by Oxidative Stress - Kyung-A Kim; Sang Min Kim; Suk Woo Kang; Sang Il Jeon; Byung Hun Um; Sang Hoon Jung (Marine Biotechnology, 2012)

mRNA sequence analysis and quantitative expression of the ADAMTS4 gene in the thoroughbred horse - Jae-Woo Moon; Kung Ahn; Jin-Han Bae; Gyu-Hwi Nam; Byung-Wook Cho; Kyung-Do Park; Hak-Kyo Lee; Young-Mok Yang; Tae-Hun Kim; Hwan-Hoo Seong; Kyudong Han; Heui-Soo Kim (Genes & Genomics, 2012)

Identification and characterization of transposable element-mediated chimeric transcripts from porcine Refseq and EST databases - Hong-Seok Ha; Jae-Woo Moon; Jeong-An Gim; Yi-Deun Jung; Kung Ahn; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

Linear Delivery of Verapamil via Nanofibrous Sheet-Based System - Ji Eun Lee; Chun Gwon Park; Byeong Moo An; Myung Hun Kim; Min Park; Seung Ho Lee; Young Bin Choy (Pharmaceutical Research, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Association between OPG, RANK and RANKL gene polymorphisms and susceptibility to acute coronary syndrome in Korean population - WON-SEOK CHOE; HACK-LYOUNG KIM; JUNG-KYU HAN; YOUNG-EUN CHOI; BORAMI SEO; HYUN-JAI CHO; HAN-KWANG YANG; KYU-JOO PARK; JIN-SHIK PARK; HUN-JUN PARK; PUM-JOON KIM; SANG-HONG BAEK; et al. (Journal of Genetics, 2012)

In vitro CpG methylation and garcinol reduce PERV LTR promoter activity - Hong-Seok Ha; Young-Choon Lee; Sang-Je Park; Yi-Deun Jung; Kung Ahn; Jae-Woo Moon; Kyudong Han; Keon-Bong Oh; Tae-Hun Kim; Hwan-Hoo Seong; Heui-Soo Kim (Genes & Genomics, 2012)

Cryptonemia rotunda (Halymeniales) and Schizymenia apoda (Nemastomatales), two new records of red algae from Korea - Su-Yeon Kim; Tae-Ho Seo; Jeong-Kwang Park; Ga-Hun Boo; Kyeong-Mi Kim; Sung-Min Boo (Algae, 2012)

Determination of PDE-5 inhibitors and appetite suppressants in adulterated dietary supplements using LC/PDA and LC/MS - So-ra Park; Jin Gyun Lee; Si Hun Roh; Gyudong Kim; Chan Hyeok Kwon; Hee Ra Park; Ki Sung Kwon; Deukjoon Kim; Sung Won Kwon (Food Additives & Contaminants Part B-Surveillance, 2012)

Abnormal effects of unpurified and purified multi-walled carbon nanotubes in A549, Jurkat and THP-1 cell lines - Young Hun Kim; Hyeoung Woo Park; Zae Young Ryoo; Hyun-Shik Lee; Do-Hyung Kim; Sanggyu Lee (Molecular & Cellular Toxicology, 2012)

mRNA-centric semantic modeling for finding molecular signature of trace chemical in human blood - Ga-Hee Shin; Yeon-Kyung Kang; Seung-Hun Lee; Seung Jun Kim; Seung Yong Hwang; Suk-Woo Nam; Jae-Chun Ryu; Byeong-Chul Kang (Molecular & Cellular Toxicology, 2012)

Anti-inflammatory effect of sweetfish-derived protein and its enzymatic hydrolysate on LPS-induced RAW264.7 cells via inhibition of NF-κB transcription - Nak-Yun Sung; Pil-Moon Jung; Minchul Yoon; Jeong-Soo Kim; Jong-il Choi; Hye Gwang Jeong; Ju-Woon Lee; Jae-Hun Kim (Fisheries Science, 2012)

Analysis of volatile organic compounds released during food decaying processes - Nhu-Thuc Phan; Ki-Hyun Kim; Eui-Chan Jeon; Uk-Hun Kim; Jong Ryeul Sohn; Sudhir Kumar Pandey (Environmental Monitoring and Assessment, 2012)

A novel function of Streptomyces integration host factor (sIHF) in the control of antibiotic production and sporulation in Streptomyces coelicolor - Yung-Hun Yang; Eunjung Song; Joost Willemse; Sung-Hee Park; Woo-Seong Kim; Eun-jung Kim; Bo-Rahm Lee; Ji-Nu Kim; Gilles P. van Wezel; Byung-Gee Kim (Antonie van Leeuwenhoek, 2012)

Performance of a conical jellyfish exclusion device installed in a trawl net - Chang-Doo Park; Kyounghoon Lee; Seong-Hun Kim; Yasuzumi Fujimori (Fisheries Science, 2012)

Novel PPARγ partial agonists with weak activity and no cytotoxicity; identified by a simple PPARγ ligand screening system - Min-Chul Cho; Dong-Hun Lee; Eun Jin Kim; Jee-young Lee; Jeong-Woo Kang; Jong Hwan Song; Youhoon Chong; Yangmi Kim; Jin-Tae Hong; Do-Young Yoon (Molecular and Cellular Biochemistry, 2011)

A Comparative Study on Toxicity Identification of Industrial Effluents Using Daphnia magna - Xianliang Yi; Eunhee Kim; Hun-Je Jo; Taejun Han; Jinho Jung (Bulletin of Environmental Contamination and Toxicology, 2011)

Meteorological responses to Mt. Baekdu volcanic eruption over east asia in an offline global climate-chemistry model: A pilot study - Byung-Kwon Moon; Daeok Youn; Rokjin J. Park; Sang-Wook Yeh; Won-Mo Kim; Young-Ho Kim; Jaein I. Jeong; Jung-Hun Woo; Eul Gyu Im; Chang-Keun Song (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Detection of human parechoviruses in children with gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2011)

Oxidized phosphatidylcholine induces migration of bone marrow-derived mesenchymal stem cells through Krüppel-like factor 4-dependent mechanism - Sang Hun Shin; Hae Young Song; Min Young Kim; Eun Kyung Do; Jung Sub Lee; Jae Ho Kim (Molecular and Cellular Biochemistry, 2011)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Treadmill exercise suppresses muscle cell apoptosis by increasing nerve growth factor levels and stimulating p-phosphatidylinositol 3-kinase activation in the soleus of diabetic rats - Chang-Hun Chae; Sung-Lim Jung; Sang-Hyun An; Chan-Kyoung Jung; Sang-Nam Nam; Hyun-Tae Kim (Journal of Physiology and Biochemistry, 2011)

Stability of Fe- and Mn-(oxyhydr)oxides in Common Soil Dispersion Solutions - Phung N. Manh; Moonis Ali Khan; Byong-Hun Jeon; Jae Gon Kim; Giehyeon Lee (Water, Air, & Soil Pollution, 2011)

A new cloning strategy for generating multiple repeats of a repetitive polypeptide based on non-template PCR - Hun-Su Chu; Jung Ryum; Seo-Young Park; Byung-Gee Kim; Dong-Myung Kim; Jong-In Won (Biotechnology Letters, 2011)

Genetic characterization of H1 avian influenza viruses isolated from migratory birds and domestic ducks in Korea - Ok-Mi Jeong; Yong-Joo Kim; Jun-Gu Choi; Hyun-Mi Kang; Min-Chul Kim; Jun-Hun Kwon; Youn-Jeong Lee (Virus Genes, 2011)

Emergence of norovirus GII-4/2008 variant and recombinant strains in Seoul, Korea - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2011)

Abiotic subsurface behaviors of As(V) with Fe(II) - Sang-Hun Lee; Woosik Jung; Byong-Hun Jeon; Jae-Young Choi; Sunjoon Kim (Environmental Geochemistry and Health, 2011)

Investigation of porcine FABP3 and LEPR gene polymorphisms and mRNA expression for variation in intramuscular fat content - Xiaoping Li; Sang-Wook Kim; Jung-Suck Choi; Yoon-Mi Lee; Cheol-Koo Lee; Bong-Hwan Choi; Tae-Hun Kim; Yang-Il Choi; Jong-Joo Kim; Kwan-Suk Kim (Molecular Biology Reports, 2010)

JNK-mediated transcriptional upregulation of RhoB is critical for apoptosis of HCT-116 colon cancer cells by a novel diarylsulfonylurea derivative - Dong-Myung Kim; Misun Won; Chung-Sook Chung; Semi Kim; Hyeon Joo Yim; Sang-Hun Jung; ShinWu Jeong (Apoptosis, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

A cytological observation of the fluid in the primo-nodes and vessels on the surfaces of mammalian internal organs - Baeckkyoung Sung; Min Su Kim; Byung-Cheon Lee; Seong-Hun Ahn; Sung-Yeoun Hwang; Kwang-Sup Soh (Biologia, 2010)

Genetic characterization of rotavirus in children in South Korea from 2007 to 2009 - Tae-Hee Han; Cheol-Hwan Kim; Ju-Young Chung; Sang-Hun Park; Eung-Soo Hwang (Archives of Virology, 2010)

Impaired retinal vascular development in anencephalic human fetus - Jin Hyoung Kim; Young Suk Yu; Kyu-Won Kim; Jeong Hun Kim (Histochemistry and Cell Biology, 2010)

Regulation of bone formation using rapamycin-induced BMP2 expression system: influence of implanted cell number - Dong-Jin Lim; Bae Keun Park; Won Gu Jang; Kkot-Nim Lee; Renny Franceschi; Sun-Hun Kim; Shee-Eun Lee; Jeong-Tae Koh (Molecular & Cellular Toxicology, 2010)

Iron deficiency in children with mitochondrial disease - Hye Eun Kwon; Jung Hun Lee; Young Mock Lee; Hoon Chul Kang; Joon Soo Lee; Heung Dong Kim (Metabolic Brain Disease, 2010)

Nutritional improvement of the endothelial control of vascular tone by polyphenols: role of NO and EDHF - Valérie B. Schini-Kerth; Cyril Auger; Jong-Hun Kim; Nelly Étienne-Selloum; Thierry Chataigneau (Pflügers Archiv - European Journal of Physiology, 2010)

Erratum to: Robot-assisted modifications of gait in healthy individuals - Seok Hun Kim; Sai K. Banala; Elizabeth A. Brackbill; Sunil K. Agrawal; Vijaya Krishnamoorthy; John P. Scholz (Experimental Brain Research, 2010)

Robot-assisted modifications of gait in healthy individuals - Seok Hun Kim; Sai K. Banala; Elizabeth A. Brackbill; Sunil K. Agrawal; Vijaya Krishnamoorthy; John P. Scholz (Experimental Brain Research, 2010)

Technical issues in modeling surface-drifter behavior on the East China Sea shelf - Shin’ichiro Kako; Atsuhiko Isobe; Shun Yoshioka; Pil-Hun Chang; Takeshi Matsuno; Sang-Hyun Kim; Joon-Soo Lee (Journal of Oceanography, 2010)

The effects of various antioxidants on the development of parthenogenetic porcine embryos - Hyung Soo Yuh; Dong Hun Yu; Mi Jung Shin; Hei Jung Kim; Ki Beom Bae; Dong Seok Lee; Hwi Cheul Lee; Won Kyong Chang; Soo Bong Park; Sang Gyu Lee; Hum Dai Park; Ji Hong Ha; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Phylogenetic Relationship of Physocarpus insularis (Rosaceae) Endemic on Ulleung Island: Implications for Conservation Biology - Sang-Hun Oh; Luna Chen; Sung-Hee Kim; Young-Dong Kim; Hyunchur Shin (Journal of Plant Biology, 2010)

1,3-Dichloro-2-propanol induces apoptosis via both calcium and ROS in mouse melanoma cells - Sun Young Park; Young Hun Kim; Young Hee Kim; Sang-Joon Lee (Biotechnology Letters, 2010)

Molecular epizootiology of infectious bursal disease (IBD) in Korea - Woo-Jin Jeon; Kang-Seuk Choi; Dong-Woo Lee; Eun-Kyoung Lee; Sang-Ho Cha; Sun-Hee Cho; Jun-Hun Kwon; Yeo-sung Yoon; Sun-Joong Kim; Jae-Hong Kim; Hyuk-Joon Kwon (Virus Genes, 2009)

Detection of Human Bocavirus-2 in children with acute Gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; En-Jung Kim; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2009)

Detection of low-abundant novel transcripts in mouse hematopoietic stem cells - Hyeng-Soo Kim; Junmo Hwang; Young-Hun Kim; Seonggon Kim; Jae-Woong Lee; Hyung-Sik Kang; Kil Soo Kim; Ji-Hong Ha; Jin Woong Chung; Kyu-Tae Chang; Zae Young Ryoo; Sanggyu Lee (Molecular Genetics and Genomics, 2009)

High expression of Snail mRNA in blood from hepatocellular carcinoma patients with extra-hepatic metastasis - Ae Lyoung Min; Jong Young Choi; Hyun Young Woo; Jin Dong Kim; Jung Hyun Kwon; Si Hyun Bae; Seung Kew Yoon; Seung Hun Shin; Yeun Jun Chung; Chan Kwon Jung (Clinical & Experimental Metastasis, 2009)

A volumetric study of the corpus callosum in 20s and 40s Korean people - Beob-Yi Lee; Jin-Hun Sohn; Mi-Hyun Choi; Su-Jeong Lee; Hyo-Seong Kim; Jae-Woong Yang; Jin-Seung Choi; Hyung-Sik Kim; Jeong-Han Yi; Gye-Rae Tack; Soon-Cheol Chung (Brain Structure and Function, 2009)

Red and Blue Photons Can Enhance the Production of Astaxanthin from Haematococcus pluviatis - Z-Hun Kim; Ho-Sang Lee; Choul-Gyun Lee (Algae, 2009)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

Vertical structure of low-frequency currents in the southwestern East Sea (Sea of Japan) - Yun-Bae Kim; Kyung-Il Chang; Kuh Kim; Jae-Hun Park; Jae-Hak Lee (Journal of Oceanography, 2009)

Kinetic and regulatory properties of plant ADP-glucose pyrophosphorylase genetically modified by heterologous expression of potato upreg mutants in vitro and in vivo - Si-Myung Lee; Tae-Hun Ryu; Su-Il Kim; Thomas Okita; Donghern Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Temporal Variations in Seaweed Biomass in Korean Coasts: Woejodo and Jusamdo, Jeonbuk - Han-Gil Choi; Ki-Hun Lee; Xiao Qin Wan; Hyun-Il Yoo; Hyang-Ha Park; Jeong-Ha Kim; Ik-Kyo Chung (Algae, 2008)

Purification and partial characterization of antifungal metabolite from Paenibacillus lentimorbus WJ5 - Young-Keun Lee; M. Senthilkumar; Jung-Hun Kim; K. Swarnalakshmi; K. Annapurna (World Journal of Microbiology and Biotechnology, 2008)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Improving the yield of soluble 6xHis-tagged interferon-α via the addition of repressor of the araBAD promoter system in Escherichia coli - Kyung-Hwan Jung; Young-Seo Park; Ji-Hyeon Yeon; Sung-Hun Kim; Sun Kyun Yoo; Byeong-Churl Jang (Biotechnology Letters, 2008)

Overexpression of OgPAE1 from wild rice confers fungal resistance against Botrytis cinerea - Eun Hee Jeon; Eun Sook Chung; Jung Hun Pak; Jae Sung Nam; Sung Ki Cho; Sang Hyun Shin; Doh Hoon Kim; Gyung Tae Kim; Jai Heon Lee; Kyung Ho Kang; Young Soo Chung (Journal of Plant Research, 2008)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Beneficial effects of cardiac rehabilitation and exercise after percutaneous coronary intervention on hsCRP and inflammatory cytokines in CAD patients - Young-Joo Kim; Young-Oh Shin; Jun-Sang Bae; Jeong-Beom Lee; Joo-Hyun Ham; Youn-Jung Son; Jung-Kyu Kim; Chul Kim; Byoung-Kwon Lee; Jae-Keun Oh; Timothy Othman; Young-Ki Min; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Analysis of metabolite profile data using batch-learning self-organizing maps - Jae Kwang Kim; Myoung Rae Cho; Hyung Jin Baek; Tae Hun Ryu; Chang Yeon Yu; Myong Jo Kim; Eiichiro Fukusaki; Akio Kobayashi (Journal of Plant Biology, 2007)

MMP2 role in breast cancer brain metastasis development and its regulation by TIMP2 and ERK1/2 - Odete Mendes; Hun-Taek Kim; Gina Lungu; George Stoica (Clinical & Experimental Metastasis, 2007)

Heavy water labeling method for measuring the effect of genistein on mammary gland carcinogenesis - Hyeon-A Kim; Kyu-Shik Jeong; Dae-Hun Park; Jeong-Ae Lee; Won-Il Jeong; Yoo Kyeong Kim (Molecular and Cellular Biochemistry, 2007)

2′,5,7-Trihydroxy-4′,5′-(2,2-dimethylchromeno)-8-(3-hydroxy-3-methylbutyl) flavanone purified from Cudrania tricuspidata induces apoptotic cell death of human leukemia U937 cells - Yoon-Hwa Rho; Soo-Hyun Yoon; Eun-Kyung Kim; Ji-Young Kang; Byong-Won Lee; Ki-Hun Park; Young-Seuk Bae (Natural Product Research, 2007)

DNMT3b 39179G‎T Polymorphism and the Risk of Adenocarcinoma of the Colon in Koreans - Young-Seoub Hong; Hye-Jung Lee; Chang-Hun You; Mee-Sook Roh; Jong-Young Kwak; Myeong-Jin Lee; Joon-Youn Kim (Biochemical Genetics, 2007)

Expression of an Arabidopsis CAX2 variant in potato tubers increases calcium levels with no accumulation of manganese - Chang Kil Kim; Jeung-Sul Han; Hyun-Suk Lee; Joung-Youl Oh; Thoshiro Shigaki; Sung Hun Park; Kendal Hirschi (Plant Cell Reports, 2006)

Proapoptotic activity of NAG-1 is cell type specific and not related to COX-2 expression - Tae Jung Jang; Nam II Kim; Chang Hun Lee (Apoptosis, 2006)

In-situ electrochemical measurements of total concentration and speciation of heavy metals in acid mine drainage (AMD): assessment of the use of anodic stripping voltammetry - Hun-Bok Jung; Seong-Taek Yun; Soon-Oh Kim; Myung Chae Jung; Chil-Sup So; Yong-Kwon Koh (Environmental Geochemistry and Health, 2006)

Fractal Stochastic Modeling of Spiking Activity in Suprachiasmatic Nucleus Neurons - Sung-IL Kim; Jaeseung Jeong; Yongho Kwak; Yang In Kim; Seung Hun Jung; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Rapid Identification of Lactobacillus acidophilus by Restriction Analysis of the 16S–23S rRNA Intergenic Spacer Region and Flanking 23S rRNA Gene - Kyoung-Sik Han; Younghoon Kim; Seungkook Choi; Sejong Oh; Sungsu Park; Sae-Hun Kim; Kwang-Youn Whang (Biotechnology Letters, 2005)

Occupational hand–arm vibration syndrome in Korea - Cheolin Yoo; Ji-Ho Lee; Choong-Ryeol Lee; Yangho Kim; Hun Lee; Younghee Choi; Young Wook Kim; Chang Ho Chae; Hyokyoung Kim; Sang Baek Koh; Euna Kim; Lu Jin Lee; et al. (International Archives of Occupational and Environmental Health, 2005)

Expression of MMP2, MMP9 and MMP3 in Breast Cancer Brain Metastasis in a Rat Model - Odete Mendes; Hun-Taek Kim; George Stoica (Clinical & Experimental Metastasis, 2005)

A Polymeric Nanoparticle Consisting of mPEG-PLA-Toco and PLMA-COONa as a Drug Carrier: Improvements in Cellular Uptake and Biodistribution - Yilwoong Yi; Jae Hong Kim; Hye-Won Kang; Hun Seung Oh; Sung Wan Kim; Min Hyo Seo (Pharmaceutical Research, 2005)

Up-regulation of astrocyte cyclooxygenase-2, CCAAT/enhancer-binding protein, glucose-related protein 78, eukaryotic initiation factor 2α, and c-Jun N-terminal kinase by a neurovirulent murine retrovirus - Hun-Taek Kim; Wenan Qiang; Na Liu; Virginia L Scofield; Paul KY Wong; George Stoica (Journal of NeuroVirology, 2005)

Dehydration behaviors of interlayer water in systhetic Buserites - Hun Soo Choi; Soo Jin Kim; Jeong Jin Kim (Geosciences Journal, 2004)

Variation of Species Composition of Benthic Algae and Whitening in the Coast of Dokdo Island during Summer - Mi-Gyeong Kim; Jae-Gi Sin; Jae-Hun Cha (Algae, 2004)

Antiviral Effects of Sulfated Exopolysaccharide from the Marine Microalga Gyrodinium impudicum Strain KG03 - Joung Han Yim; Sung Jin Kim; Se Hun Ahn; Chong Kyo Lee; Ki Tae Rhie; Hong Kum Lee (Marine Biotechnology, 2004)

Possible involvement of both endoplasmic reticulum– and mitochondria-dependent pathways in MoMuLV- ts 1–induced apoptosis in astrocytes - Na Liu; Xianghong Kuang; Hun-Taek Kim; George Stoica; Wenan Qiang; Virginia Lee Scofield; Paul KY Wong (Journal of NeuroVirology, 2004)

ACCUMULATION OF HEAVY METALS IN KOREAN MARINE SEAWEEDS - Sin-Yeong Kim; M. Sidharthan; Yong-Hun Yu; Chi-Yeong Im; Hyeong-Ju Jin; Jong-Su Yu; Hyeon-Ung Sin (Algae, 2003)

Isolation and Characterization of Bacteria Capable of Degrading Phenol and Reducing Nitrate Under Low-Oxygen Conditions - Seung-Hun Baek; Kyoung-Ho Kim; Cheng-Ri Yin; Che Ok Jeon; Wan-Taek Im; Kwang-Kyu Kim; Sung-Taik Lee (Current Microbiology, 2003)

A High-Throughput Combinatorial Approach for the Discovery of a Cremophor EL-Free Paclitaxel Formulation - Hongming Chen; Zhong Zhang; Chris McNulty; Cameron Olbert; Hye Jeong Yoon; Jang Won Lee; Sung Chul Kim; Min Hyo Seo; Hun Seung Oh; Anthony V. Lemmo; Stephen J. Ellis; Ken Heimlich (Pharmaceutical Research, 2003)

Geochemistry and tectonic implications of Proterozoic amphibolites in the northeastern part of the Yeongnam massif, South Korea - Yoji Arakawa; Kye‐Hun Park; Nam‐Hoon Kim; Yong‐Sun Song; Hiroshi Amakawa (Island Arc, 2003)
Amphibolites in the Haenggongni area (Haenggongni amphibolite) and the Okbang area (Okbang amphibolite) in northeastern Yeongnam massif, South Korea occur as a sill‐like body or inclusions within the metasedimentary sequences of the Proterozoic Wonnam Group. Major and trace element characteristics demonstrate that both amphibolites have tholeiitic chemical affinity. They are characterized by nearly flat rare earth element (REE) patterns, and low contents of immobile incompatible elements and have low values of Zr/Y, Ti/Y, La/Nb and Ta/Yb ratios, indicating enriched (E)‐type mid‐oceanic ridge basalt (MORB) affinities for their protoliths. This suggests that amphibolite protoliths formed in an extensional rift setting leading up to ocean opening. In combination with the previous studies in Yeongnam massif, three protolith types of amphibolites are assumed (E‐type MORB, within‐plate basalt and volcanic arc basalt). They could have been originated in different tectonic settings and/or different episodes. These characteristics are clearly different from the amphibolites in the Gyeonggi massif and Okcheon belt, in which most of the amphibolites show a within‐plate basalt affinity that developed in continental rift zone.

Simultaneous synthesis of enantiomerically pure (R)-1-phenylethanol and (R)-α-methylbenzylamine from racemic α-methylbenzylamine using ω-transaminase/alcohol dehydrogenase/glucose dehydrogenase coupling reaction - Hyungdon Yun; Yung-Hun Yang; Byung-Kwan Cho; Bum-Yeol Hwang; Byung-Gee Kim (Biotechnology Letters, 2003)

Kidney-Specific Activity of the Bovine Uromodulin Promoter - Hun-Taek Kim; In-Young Song; Jorge Piedrahita (Transgenic Research, 2003)

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)

Phylogenetic Relationship of Microcystis (Cyanophyceae) Based on Partial 16S rRNA Gene Sequences in Korea - Jong-In Kim; Jong-Hun Lim; Jae-Wan Lee; Hae-Bok Lee (Algae, 2002)

Enhanced proteolysis of IκBα and IκBβ proteins in astrocytes by Moloney murine leukemia virus (MoMuLV)- ts 1 infection: A potential mechanism of NF-κB activation - Hun-Taek Kim, Wenan Qiang, Paul K. Y. Wong (Journal of NeuroVirology, 2001)

Genetic Diversity of Apodemus agrarius-Borne Hantaan Virus in Korea - Jin-Won Song; Luck Ju Baek; Sang Hyun Kim; Eun Young Kho; Jong Hun Kim; Richard Yanagihara; Ki-Joon Song (Virus Genes, 2000)

Molecular cloning, expression, and functional characterization of a 2Cys-peroxiredoxin in Chinese cabbage - Na Eun Cheong; Yeon Ok Choi; Kyun Oh Lee; Woe Yeon Kim; Bae Gyo Jung; Yong Hun Chi; Jin Sook Jeong; Kanghwa Kim; Moo Je Cho; Sang Yeol Lee (Plant Molecular Biology, 1999)

Stage-related chondrogenic potential of human limb bud mesenchyme cells, In vitro: Role of protein kinase C - Yoon-Ah Kook; Chang-Duk Jun; Sung-Gak Hong; Joseph Zernik; Eun-Cheol Kim; Sang-Cheol Kim; Shin-Sung Kang; Hun-Taeg Chung (In Vitro Cellular & Developmental Biology - Animal, 1998)

Lack of interactions between amyloid precursor protein and hydrophilic domains of presenilin 1 and 2 using the yeast two hybrid system - Sung-Su Kim; Yoo-Mi Choi; Yoo-Hun Suh (Journal of Molecular Neuroscience, 1997)